Lunar Sosigenes IMP as analyzed with orbital spectrophotometry and polarimetry - Yuriy Shkuratov; Vadym Kaydash; James Head; Kilho Baek; Sungsoo S. Kim; Sergey Velichko; Yehor Surkov; Minsup Jeong; Young-Jun Choi; Chae Kyung Sim; Hao Zhang; Han Zheng; et al. (Icarus, 2026)

Engineering of novel N-TiO2/P-doped graphene oxide nanocomposite: Mechanistic insights into the photocatalytic removal of benzophenone-3 and H2 production - Wisal Ahmad; Suyeon Jeon; Roman Shah; Dilaram Khan; Syed Izaz Ali Shah; Muhammad Anwar; Raed Al-Juboori; Asad Ali; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Spore inoculum size impacts substrate degradation and sporulation but not the secretome during colonization of whole yellow pea (Pisum sativum) by Aspergillus oryzae - Maaike Braat; Nienke Braat; Nadzeya Staliarova; Tomás Vellozo-Echevarría; Hania M. Siwek; Julius F. Kemmer; Kristian Barrett; Anne S. Meyer; Kelly E. Stecker; Han A.B. Wösten (International Journal of Food Microbiology, 2026)

Examination of DNAm PhenoAge as an epigenetic biomarker for perioperative risk in adult spinal deformity surgeries - Michael P. Kelly; Jeffrey Hills; Justin S. Smith; Lawrence G. Lenke; Han Jo Kim; Shay Bess; Breton Line; Virginie Lafage; Renaud Lafage; Eric Klineberg; Ferran Pellise; Khaled Kebaish; et al. (GeroScience, 2026)

Targeting Mitochondrial Dysfunction in Acute Organophosphate Toxicity: A Preliminary Evaluation of Cyclosporine A - David H. Jang; Jarelis Cabrera; Jonathan Starr; Abigail Insana; Angela N. Viaene; John C. Greenwood; Frances S. Shofer; Johannes K. Ehinger; Shih-Han Kao; Todd J. Kilbaugh (Journal of Medical Toxicology, 2026)
Background Organophosphate (OP) compounds are widely used agricultural chemicals that pose significant public health and chemical threat concerns due to their neurotoxic effects. Although OP toxicity has classically been attributed to acetylcholinesterase inhibition and cholinergic crisis, emerging evidence suggests mitochondrial dysfunction may represent an additional and clinically relevant mechanism of injury. Experimental OP exposure has been associated with impaired electron transport chain activity, reduced ATP production, increased oxidative stress, and disruption of mitochondrial membrane integrity. However, there are currently no established mitochondrial-targeted therapies for OP poisoning. Diisopropyl fluorophosphate (DFP), a well-established OP surrogate, reproduces several neurologic and mitochondrial features of nerve agent exposure. Cyclosporine A (CsA), an inhibitor of the mitochondrial permeability transition pore (mPTP), may represent a potential mitochondrial-targeted intervention. Methods This preliminary translational study employed both in vitro and in vivo models to evaluate mitochondrial respiratory dysfunction following acute DFP exposure and to explore the feasibility of mitochondrial-targeted treatment paradigms using CsA. Human donor-derived peripheral blood mononuclear cells (PBMCs) were used for DFP and CsA dose-finding and mitochondrial respiratory characterization using high-resolution respirometry (Oroboros O2k) with standardized substrate–uncoupler–inhibitor titration (SUIT) protocols. In parallel, a non-survivor Sprague–Dawley rat model of acute DFP exposure was developed incorporating invasive hemodynamic monitoring, controlled ventilation, venous blood gas analysis, and CsA treatment paradigms administered either following DFP exposure or as pretreatment prior to exposure. Brain cortical homogenates were prepared for ex vivo respiratory assessment. Results Preliminary findings demonstrated that DFP exposure was descriptively associated with impaired mitochondrial respiration across multiple oxidative phosphorylation (OXPHOS)- and electron transport system (ETS)-linked respiratory states in both PBMC and rodent models. DFP exposure was additionally associated with physiologic and metabolic derangements, including acidosis and elevated lactate concentrations. Post-DFP CsA administration was associated with partial preservation of mitochondrial respiration across several respiratory states, while the Pre-DFP CsA group demonstrated respiratory profiles more closely approximating control values in select OXPHOS- and ETS-linked states, accompanied by relatively preserved physiologic and metabolic parameters. Conclusions These preliminary findings support the feasibility of integrating mitochondrial respiratory phenotyping into translational models of acute OP toxicity and further support investigation of mitochondrial-targeted strategies in OP-associated mitochondrial dysfunction. The observed respiratory and physiologic trends associated with CsA exposure, particularly in the pretreatment paradigm, provide an exploratory foundation for future preclinical studies evaluating mitochondrial-directed countermeasures in OP poisoning.

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Nicotinic acid enhances heavy metal stress resilience of wastewater anammox communities via NAD+ replenishment - Min Xu; Shiyi Han; Xiaoxin Cao; David S. Ikumi; Di Wu; Changzhi Wang; Huijie Lu (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Soil moisture information in Southeast Australia – A review of long-term field measurements toward enhanced monitoring and predictive applications - I.P. Senanayake; I.-Y. Yeo; M. Khaki; G.R. Hancock; P.G. Dahlhaus; N.J. Robinson; S.-C. Han; J.P. Walker (Geoderma Regional, 2026)

Engineering-grade monitoring of floating-roof oil tanks using amplitude-only TerraSAR-X imagery and dual geometric pipelines - Yi-Keng Chen; Zheng-Shun Su; Ya-Lun S. Tsai; Su-Wei Chang; Jen-Yu Han; Chun-Jia Huang (International Journal of Remote Sensing, 2026)

Characterization of groundwater storage dynamics and responses to meteorological stress and climate teleconnections across river basins and climate zones in Ethiopia - Mekash S. Kifelew; Song Xianfang; Yang Lihu; Dongmei Han; MA Ying; BU Hongmei (Journal of Hydrology, 2026)

Recent advances in ion exchange membrane-based electrochemical hydrogenation of liquid organic hydrogen carrier - Seokjin Hong; Gyeong Ho Han; Inho Nam; Don-Hyung Ha; Soo-Kil Kim; Sung Ki Cho; Hyun S. Park; Jong Hyun Jang; Myoung Hwan Oh; Sang Hyun Ahn (Fuel, 2026)

Extraction and characterization of bioactive oligosaccharides from pulse processing byproducts using subcritical water extraction: a proof-of-concept study - Jasmin S. Yang; T. Truc K. Pham; Andrea J.C. Tam; Han Peng; Tássia B. Pessato; You-Tae Kim; Peter J. Russell; Zhiliang Fan; David A. Mills; Daniela Barile; Juliana Maria Leite Nobrega de Moura Bell (Food Chemistry, 2026)

Explicit dynamic modeling of finite-length spherical joints in FRP bending-active gridshells: Formulation and validation - E.L. Xie; T. Jiang; Z.Y. Xia; Z.T. Han; S. Jin (Engineering Structures, 2026)

In vitro ibuprofen has gene regulatory and anti-inflammatory properties in peripheral blood mononuclear cells of individuals with infection-provoked neurodevelopmental disorders - Velda X. Han; Jessica P. Hayes; Brian Gloss; Ruwani Dissanayake; Xianzhong Lau; Erica Tsang; Hiroya Nishida; Melanie Wong; Shekeeb S. Mohammad; Shrujna Patel; Russell C. Dale (Inflammopharmacology, 2026)
Gene-environment interactions, leading to immune-brain cross-talk and neuroinflammation are increasingly recognised in neurodevelopmental disorders (NDDs), such as autistic regression and paediatric acute onset neuropsychiatric syndrome (PANS). Nonsteroidal anti-inflammatory drugs, including ibuprofen, provides relief to some neuropsychiatric symptoms, however, the therapeutic mechanisms are unclear. We describe the benefit of ibuprofen in 18 children (11 males, ages 5–20 years) with infection-provoked deteriorations compatible with PANS (16/18) or autistic regression (7/18), five met criteria for both. Ibuprofen was well tolerated and led to improved emotional control, obsessive–compulsive symptoms, and aggression during infection-related exacerbations or the chronic phase. Single-cell RNA sequencing (scRNA-seq) was performed on peripheral blood mononuclear cells (PBMCs) in two children and their respective age-, sex- matched controls, before and after 24 h of in vitro ibuprofen and/or paracetamol incubation. A total of 45,134 cells were included. At baseline in both cases, there was dysregulation of immune pathways (response to virus, cell killing) and downregulation of ribosomal and translational pathways. Ibuprofen reversed the pro-inflammatory state in both children with reversal of cell killing pathways (granzyme genes) in Case 1, and reversal of viral pathways (interferon genes) in Case 2. Ibuprofen also reversed translation pathways (ribosomal protein genes), and regulation of translation (including EIF genes). In vitro paracetamol produced similar but weaker effects than ibuprofen. Children with infection-provoked neurodevelopmental episodes have baseline transcriptional and immune dysregulation in peripheral immune cells. We show that ibuprofen has transcriptional and anti-inflammatory effects, and that scRNA-seq in vitro-based studies can inform disease-modifying therapies for individuals with NDDs.

E-cigarette Aerosol Containing Nicotine Increases Aortic Stiffness in Young Mice - Pireyatharsheny Mulorz; Joscha Mulorz; Agnesa Mazrekaj; Hsiang-Han Liu; Wiebke Ibing; Joshua M. Spin; Lasse Bach Steffensen; Hans C. Beck; Uwe Raaz; Kensuke Toyama; Hubert Schelzig; Philip S. Tsao; et al. (Cardiovascular Toxicology, 2026)

Effect of Level of Posterosuperior Cuff Tear Severity on Joint Contact Mechanics in Reverse Total Shoulder Arthroplasty: A Simulation Study - Donghwan Lee; Joo Han Oh; Jinkyu Lee; Sungwook Jung; Jungsung Kim; Namkeun Kim; Choongsoo S. Shin (Annals of Biomedical Engineering, 2026)

Dominant Combustion Sources of PM2.5-bound PAHs and Associated Cancer Risk in Wuhan, Central China - Tingting Wu; Jie Tian; Qiyuan Wang; Yong Zhang; Shaofei Kong; Jianjun Li; Lu Qi; Yan Wang; Yali Liu; Yuemei Han; André S. H. Prévôt; Junji Cao (Aerosol Science and Engineering, 2026)

Erratum to “Validation of bearing capacity methods for working platforms with test and numerical data” [Transp. Geotech. 60 (2026) 101986] - S. Demirdogen; J. Han (Transportation Geotechnics, 2026)

Tapentadol induces progressive hepatic damage via disrupting Hippo–YAP and bile acid–FXR pathways: An integrated experimental and computational perspective - Han Hu; Salim Jamil; Muhammad Bilal Azmat; Mohammed Alissa; Ghfren S. Aloraini; Amal A. Albati; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Synergistic remediation of cadmium-contaminated soil by polysaccharide-producing bacteria and organo-Fe hydroxides co-precipitates: Mechanisms of immobilization and soil structure improvement - Shuangjiao Tang; Yun Li; Nannan Zhai; Xiaochong Wang; Randa S. Makar; Wenxia Wang; Lunguang Yao; Zhaojin Chen; Hui Han (Journal of Environmental Chemical Engineering, 2026)

Air and moisture stabilization of layered sodium cathodes through oxygen-affinitive bismuth substitution - Seunghyeop Baek; Yeongkwang Heo; Hyeongseok Lee; Hyeju Kwon; Jangwook Pyun; Gwonsik Nam; Ki Han Kim; Namhyung Kim; Yong Min Lee; Munseok S. Chae (Chemical Engineering Journal, 2026)

Photocatalytic CO2 reduction: Fundamental principles, mechanistic pathways and material-specific kinetic insights - Syed Izaz Ali Shah; Muhammad Anwar; Wisal Ahmad; Muhammad Ateeq; Amir Zada; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Reliability and validity of the steep ramp test to assess cardiorespiratory fitness in apparently healthy adults - Ingeborg A. Trul-Kreuze; Bart C. Bongers; Darcy Ummels; Caspar Mylius; Anuschka S. Niemeijer; Tim Takken; Marianne K. Nieuwenhuis; Han Houdijk; Moniek Akkerman (European Journal of Applied Physiology, 2026)

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Validation of bearing capacity methods for working platforms with test and numerical data - S. Demirdogen; J. Han (Transportation Geotechnics, 2026)

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

Sour jujube seed: a review of active components from traditional use to modern innovations - Zijun Xue; Nuo Wang; Xiaolin Yu; Weitao Han; Rodrigo Quintana; Baoru Yang; Ying Zhou; Sergey S. Makarov; Anton I. Chudetsky; Jinlong Tian (Food Bioscience, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Retention rate and biological effects of Floy and FRyID tags on juvenile longfin smelt (Spirinchus thaleichthys) - Md. Moshiur Rahman; Szu-Han Chen; Nann A. Fangue; Levi S. Lewis; Tien-Chieh Hung (Fisheries Research, 2026)

Analysis of Helium Monte Carlo Data for the ISS-CREAM Instrument - A. Bagga; S. Aggarwal; Y. Amare; D. Angelaszek; D.P. Bowman; Y.C. Chen; G.H. Choi; M. Copley; L. Derome; Z.M. Dorris; L. Eraud; J.H. Han; et al. (Advances in Space Research, 2026)

Brain macrostructure correlates of financial altruism in older adults without dementia - Laura Fenton; Gali H. Weissberger; Lauren E. Salminen; Anya Samek; Daisy T. Noriega-Makarskyy; Cassidy P. Molinare; Jordan Williams; Emma Oyen; Paige Kim; Jenna Axelrod; Laura Mosqueda; Hussein Yassine; et al. (Brain Imaging and Behavior, 2026)
Greater financial altruism (i.e., the tendency to give money to an anonymous individual) has been previously associated with poorer performance on neuropsychological tests sensitive to cognitive changes occurring in early Alzheimer’s disease (AD). While these findings provide initial support for the idea that financial altruism may be associated with early AD-related brain changes, no study has used MRI to investigate structural brain correlates of financial altruism in older adults. To address this gap in the literature, the current study investigated associations between brain macrostructure and financial altruism in 101 older adults free from dementia (mean age = 68.45±7.15, mean education = 16.61±2.14, 76% female, 73% White) using a high-field 7 Tesla MRI. Results revealed no significant associations between financial altruism and a priori regions of interest (entorhinal cortex, hippocampus, ventromedial prefrontal cortex, dorsolateral prefrontal cortex, and temporoparietal junction) in the entire sample. However, there was a significant interaction between financial altruism and income, whereby greater financial altruism was associated with lower hippocampal volume in those with a reported income below $100,000. Collectively these results suggest that financial altruism in the context of lower income, but not financial altruism in general, may reflect suboptimal brain aging, and perhaps greater risk of conversion to AD.

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Impacts of climate and land-use change on ecosystem services in the agro-pastoral ecotone of western Liaoning - Y. Li; D. Ye; X. Han; S. Xia; J. Jin; X. Jiang; L. Lv (International Journal of Environmental Science and Technology, 2026)

Correction to: Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2026)

Economic and societal indicators in sustainable roadway rating systems – a comparative analysis - Shih-Hsien Yang; Nam Hoai Tran; Andrew S. Chang; Calista Y. Tsai; Han-Ruen Yueh (Environment, Development and Sustainability, 2026)

Corrigendum to “Loss of c-Met signaling sensitizes hepatocytes to lipotoxicity and induces cholestatic liver damage by aggravating oxidative stress” [Toxicology 361–362 (2016) 39–48] - Luis E. Gomez-Quiroz; Daekwan Seo; Yun-Han Lee; Mitsuteru Kitade; Timo Gaiser; Matthew Gillen; Seung-Bum Lee; Ma Concepcion Gutierrez-Ruiz; Elizabeth A. Conner; Valentina M. Factor; Snorri S. Thorgeirsson; Jens U. Marquardt (Toxicology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The fabrication of a novel Fenton-like catalytic ceramic membrane hybrid process for advanced water treatment at neutral pH - Youngkun Chung; Seungyeob Han; Gunhak Oh; Jongsu Seo; Hyojeon Kim; Chewon Son; Michael S. Wong; Duksoo Jang; Seoktae Kang (Journal of Water Process Engineering, 2026)

Retraction notice to “A fully decentralized home energy management system for efficient energy management and photovoltaic with battery energy storage system sizing for grid connected home microgrid” [J. Clean. Product. 514 (2025) 145768] - Jawad Hussain; Yang Han; Amr S. Zalhaf; Qi Huang; Congling Wang (Journal of Cleaner Production, 2026)

Catalytic activation of peracetic acid with tungsten–modified iron oxides for decomposing pharmaceuticals in water - Chaejin Choi; Ayoung Choi; Haesung Lee; Minhee Kim; Noor S. Shah; Javed Ali Khan; Mallikarjuna N. Nadagouda; Changseok Han (Chemical Engineering Journal, 2026)

Dissection of Fusarium head blight resistance in a modified nested association mapping panel of synthetic and bread wheat germplasm - Anil Karmacharya; Dhondup Lhamo; Krishna Acharya; Qijun Zhang; Han-Chang Chang; Shaobin Zhong; Andrew J. Green; Jason D. Fiedler; Mingcheng Luo; Kirk M. Anderson; Amanda R. Peters Haugrud; Elias M. Elias; et al. (Theoretical and Applied Genetics, 2026)

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

Hybridization and incomplete lineage sorting characterize the evolutionary history of two East Asian clades of Stewartia (Theaceae) - Han-Yang Lin; Miao Sun; Jian-Jun Jin; Cheng-Xin Fu; Douglas E. Soltis; Pamela S. Soltis; Yun-Peng Zhao (Molecular Phylogenetics and Evolution, 2026)

Effects of roads on animals and mitigation measures in Asia - Haotong Su; Yun Wang; Qilin Li; Yangang Yang; Abudusaimaiti Maierdiyali; Shuangcheng Tao; Yaping Kong; Jiding Chen; Jiapeng Qu; Yongshun Han; Aili Kang; Shu Chen; et al. (Biological Conservation, 2026)

Coercive male genital structures expose concealed female genitalia in the water strider Chimarrhometra orientalis Distant, 1879 - Dong Yeop Yang; Min Suk Oh; Myeongdong Jo; Byeongho Lee; Jaehyun Choi; Suraj Basnet; Indra Prasad Subedi; Seunghwan Lee; Chang S. Han (Arthropod Structure & Development, 2026)

Gene Flow and Habitat Heterogeneity Shape Coexistence Dynamics of Arctic Charr Morphs in Connected Lakes - Han Xiao; Arnar Pálsson; Zophonías O. Jónsson; Sigurður S. Snorrason (Molecular Ecology, 2026)
Sympatric morphs provide valuable systems for studying incipient divergence despite incomplete reproductive isolation. In connected waterbodies with spatially heterogeneous habitats, one or more morphs may form metapopulation structures, generating eco‐evolutionary dynamics unlike those in single lakes. We studied the phenotypic and genome‐wide differentiation in Arctic charr ( Salvelinus alpinus ) in two Icelandic lakes: Thingvallavatn, known to harbour four distinct morphs, and a smaller downstream lake, Ulfljotsvatn. Our analyses confirm a single origin of charr polymorphism in this system, with all morphs present in both lakes. Relative morph abundances differ between the lakes: PL‐charr dominate in Thingvallavatn, whereas LB‐charr are most abundant in Ulfljotsvatn. Three morphs, large‐ (LB‐), small (SB‐) benthivorous and planktivorous (PL‐) charr, are genetically distinct. The system likely forms a source‐sink structure for both PL‐ and SB‐charr, though migration rates from Thingvallavatn vary remarkably, resulting in distinct population dynamics. Conversely, LB‐charr exhibit genetic differentiation between the lakes, suggesting the presence of a separate population in Ulfljotsvatn. While piscivorous (PI‐) charr appear genetically similar to PL‐charr, evidence suggests hybridisation between PI‐ and LB‐charr in both lakes. Moreover, the higher hybridisation in the downstream lake likely contributes to the observed erosion of genetic separation between LB‐ and PL‐charr in Ulfljotsvatn. These findings suggest that the complex interplay of habitat heterogeneity and morph‐specific migrations shapes the coexistence and eco‐evolutionary dynamics of sympatric charr morphs in the connected lakes. Our study highlights the importance of investigating early divergence in spatially complex systems to advance eco‐evolutionary research.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Dynamic ventilation functional MRI of the lung with sub-millimeter spatial resolution and millisecond temporal resolution - Hongchuang Li; Haidong Li; Li Fan; Ming Zhang; Xiaoling Liu; Xiuchao Zhao; Yeqing Han; Yang Jin; Louis-S. Bouchard; Shiyuan Liu; Xin Zhou (Science Bulletin, 2025)

Nesolynx banabitanae (Hymenoptera: Eulophidae: Tetrastichinae), a new species of hyperparasitoid wasp from West Bengal, India, with SEM analysis of antennal sensilla - Arnob Chakrovorty; Neveen S. Gadallah; Banani Bhattacharjee; Arjan Basu Roy; Sutrishna Halder; Yuanyuan Han (Journal of Asia-Pacific Entomology, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Clinical Efficacy of Stem Cell Therapy in Neurotraumatic and Neurodegenerative Conditions: A Comparative Review - Jun Beom Ku; Ray J. Pak; Sarah S. Ku; Robert D. Holland; Han-Soo Kim (Tissue Engineering and Regenerative Medicine, 2025)

The pore-network-continuum modeling of two-phase flow properties for multiscale digital rocks - Bowen Shi; Jianqi Rong; Han Jiang; Bo Guo; S. Majid Hassanizadeh; Chao-Zhong Qin (Advances in Water Resources, 2025)

Drivers of Sea Level Variability in the Yellow Sea and East Sea (1993–2021): A 29-Year Decomposition Using Satellite Altimetry and Reanalysis Data - MyeongHee Han; Yeon S. Chang; Jeseon Yoo; Hak Soo Lim (Journal of Marine Science and Engineering, 2025)
Understanding and monitoring regional sea level (SL) variability in semi-enclosed marginal seas such as the Yellow Sea (YS) and East Sea (ES) are essential for climate impact assessment, coastal risk management, and regional model validation. This study presents a 29-year (1993–2021) observational analysis of SL and sea level differences (SLDs) around the Korean Peninsula, primarily based on gridded satellite altimetry and complemented by atmospheric and ocean reanalysis datasets. We implemented a reproducible decomposition framework that partitions satellite-derived monthly SL variations into two primary components: a local steric term driven by surface net heat flux, and a residual term representing lateral oceanic transport and other dynamic effects. Results derived from absolute dynamic topography (ADT) climatology revealed pronounced seasonal variability in SLDs between the YS and ES, with peaks in September and a minimum in December. In September, lateral transport contributed to SL increases of approximately 2.1 cm in the YS and 2.8 cm in the ES, whereas in December, atmospheric cooling and enhanced eastward wind stress dominated SL decline in the ES, accompanied by transport-related SL reduction observed in the YS. Furthermore, the relationship between monthly mean SL and inferred volume transport through the Korea, Tsugaru, and Soya Straits revealed region-specific correlations that highlight the spatial complexity of marginal sea dynamics. By integrating multiple freely available datasets and emphasizing seasonal-to-interannual climatology, this study provides a transparent and transferable framework for decomposing sea level variability in the Northwest Pacific.

Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Comprehensive assessment of remarkable heavy metals contamination in road dust in Greater Cairo: Priority control factors based on source apportionment and risk assessment - Said A. Shetaia; Maotian Li; Jing Chen; Yanna Wang; Mohamed S. Elhebiry; Ahmed Abdelaal; Han Su; Zhongyuan Chen; Alaa Salem (Journal of Environmental Management, 2025)

The role of induction heating in catalytic propane dehydrogenation - Ben Ko; Han Wang; Jian-Ping Chen; Carlos Lizandara-Pueyo; Roel S. Sanchez-Carrera; Erdem Sasmaz (Chemical Engineering Journal, 2025)

Dual-functional Ti3C2 MXene/CuFe2O4 composite for visible light-driven degradation of ofloxacin in the presence of HSO5− and production of green H2 via photo-reforming - Jibran Iqbal; Noor S. Shah; Javed Ali Khan; Long Li; Kehan Xu; Zia ul Haq Khan; Aman Ullah; Bilal Masood Pirzada; Huma Ajab; Umar Farooq; Changseok Han (Chemical Engineering Journal, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Field measurements of icing parameters and their application towards ice load maps: An overview - Pavlo Sokolov; Muhammad S. Virk; Xingbo Han; Bjørn Egil Nygaard; Eero O. Molkoselkä; Ville A. Kaikkonen; Anssi J. Mäkynen (Cold Regions Science and Technology, 2025)

Determination of household wastewater PFAS composition and concentrations via neighborhood sampling - Omobayo A. Salawu; Ziwei Han; Naomi L. Senehi; Shannon L. Roback; Adeyemi S. Adeleye (Journal of Hazardous Materials, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Research on carbon peak measurement and potential of China’s logistics industry - S. Han; Z. Zhou; J. Gui (International Journal of Environmental Science and Technology, 2025)

Improving dynamical downscaling simulations of western North Pacific tropical cyclones using bias-corrected CMIP6 data - Ying Han; Zhongfeng Xu; Meng-Zhuo Zhang; Chi-Yung Tam; Vincent S. Cheng; Hon-man Wong; Xiaofeng He; Yi Wang; Si-nan Gu (Climate Dynamics, 2025)

Whole Genome Sequencing Reveals How Plasticity and Genetic Differentiation Underlie Sympatric Morphs of Arctic Charr - Khrystyna Kurta; Mariano Olivera Fedi; Kendall Baker; Tom Barker; Leah Catchpole; Claudio Ciofi; Arianna Cocco; Joanna Collins; Genevieve Diedericks; Maria Angela Diroma; Alex Durrant; Kjetil Hindar; et al. (Molecular Ecology, 2025)
Salmonids have a remarkable ability to form sympatric morphs after postglacial colonisation of freshwater lakes. These morphs often differ in morphology, feeding and spawning behaviour. Here, we explored the genetic basis of morph differentiation in Arctic charr ( n = 283) by first establishing a high‐quality reference genome and then using this in whole genome sequencing of distinct morphs present in two Norwegian and two Icelandic lakes. The four lakes represent the spectrum of genetic differentiation between morphs from one lake with no genetic differentiation between morphs, implying phenotypic plasticity, to two lakes with locus‐specific genetic differentiation, implying incomplete reproductive isolation, and one lake with strong genome‐wide divergence consistent with complete reproductive isolation. As many as 12 putative inversions ranging from 0.45 to 3.25 Mbp in size segregated among the four morphs present in one lake, Thingvallavatn, and these contributed significantly to the genetic differentiation among morphs. None of the putative inversions were found in any of the other lakes, but there were cases of partial haplotype sharing in similar morph contrasts in other lakes. Our findings are consistent with a highly polygenic basis of morph differentiation with population‐specific selection on alleles linked to the development of similar morph phenotypes. The results support a model where morph differentiation is first established through phenotypic plasticity, leading to niche expansion and separation. This may be followed by gradual development of reproductive isolation, locus‐specific differentiation and eventually complete reproductive isolation and genome‐wide divergence.

LP-13 Occurrence and dietary exposure assessment of cyanotoxin in fish consumed in Korea - S. Han; J. Yoon; S. Hyun; J. Seo; J. Kim (Toxicology Letters, 2025)

P31-21 Detection Methods for Injection-Induced Pseudoallergic Reactions - C. Liu; Y. Yi; C. Li; Y. Zhao; Y. Zhang; J. Han; J. Tian; C. Pan; L. Wang; S. Liu; L. Ma; A. Liang (Toxicology Letters, 2025)

A site experiment on the effects of cool coating in a residential community under the tropical climate - Yong Ping Long; E. V. S. Kiran Kumar Donthu; Di Han; Man Di Zhou; Xiao Qin Zhang; Bing Feng Ng; Man Pun Wan (Sustainable Cities and Society, 2025)

Periphytic biofilm (PB) in paddy field: A natural cadmium barrier for rice (Oryza sativa L.) safe production through physiological detoxification and gene regulation - Haiying Lu; Lingyuan Chen; Junzhuo Liu; Xianjin Tang; Chen Chen; Mohamed S. Sheteiwy; Jie Yu; Xukui Wang; Jiangang Han; Yonghong Wu; Dionysios D. Dionysiou (Journal of Hazardous Materials, 2025)

Phosphate-solubilizing bacteria reduce Cd accumulation in spinach by forming P–Ca adhesive films in the roots and altering the structure of soil macroaggregates - Qingzhao Zhao; Jiexun Wang; Haoyuan Li; Ziyi Wang; Randa S. Makar; Lunguang Yao; Zhaojin Chen; Hui Han (Journal of Hazardous Materials, 2025)

A Review of Receptor Model and New Advances in Source Apportionment Techniques for Air Pollution Research - Jie Tian; Qiyuan Wang; Yong Zhang; Yuemei Han; Lu Qi; Manousos Ioannis Manousakas; Tianqu Cui; Kaspar Rudolf Daellenbach; Jay Gates Slowik; André S. H. Prévôt; Junji Cao (Aerosol Science and Engineering, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Single-Session Feasibility of Cough Skill Training in Cerebellar Ataxia - James C. Borders; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2025)

RETRACTED: A fully decentralized home energy management system for efficient energy management and photovoltaic with battery energy storage system sizing for grid connected home microgrid - Jawad Hussain; Yang Han; Amr S. Zalhaf; Qi Huang; Congling Wang (Journal of Cleaner Production, 2025)

A universal mathematical model for forward osmosis systems coupled with experimental validation - Mona Hersi Ahmed Gulied; Sabla Alnouri; Dong Suk Han; Vladimir Stijepović; Aleksandar S. Grujić; Mirko Stijepović (Desalination, 2025)

Blood Cells as a Cellular Biomarker for Mitochondrial Function in a Experimental Model of Acute Carbon Monoxide Poisoning with Treatment - Devesh Bungatavula; John C. Greenwood; Frances S. Shofer; Guthrie Buehler; Shih-Han Kao; Matthew Kelly; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2025)
Introduction Carbon monoxide (CO) is a leading cause of environmental poisoning in the United States with substantial mortality and morbidity. The mechanism of CO poisoning is complex and includes hypoxia, inflammation, and mitochondrial dysfunction. Currently both biomarkers and therapies for CO poisoning are limited and require new approaches. Methods Rats (~ 300 g) were divided into four groups of ten rodents per group (exposure): Control (room air), CO-400 (400 ppm), CO-1000 (1000 ppm) and CO-2000 (2000 ppm). Rodents received the assigned exposure through a secured tracheotomy tube over 120 min followed by 30 min of re-oxygenation at room air for a total of 150 min. Five additional rodents in each group were administered a succinate prodrug (NV354) at the start of exposure for the duration of the experiment until the reoxygenation period as separate experiments. Cortical brain tissue and whole blood were obtained for mitochondrial respiration. Stored plasma and snap frozen tissue stored at -80 o C were used to obtain protein quantification with Western Blotting. Results All animals in the Sham, CO-400, and CO-1000 groups survived until the end of the exposure period; no animals in the CO-2000 groups survived the exposure and were counted as attrition. We observed a dose-dependent decrease in key respiratory states in both isolated brain mitochondria and peripheral blood mononuclear cells (PBMCs), and, PBMCs respiration more positively correlated with isolated brain mitochondria when compared to carboxyhemoglobin (COHb). There was no significant difference in mitochondrial respiratory states in animals treated with NV354 compared to the untreated group. Conclusions The primary findings from this study include: (1) A dose-dependent decrease with key respiration states with higher concentrations of CO; (2) PBMCs had a higher correlation to isolated brain mitochondria respiration when compared to COHb; and (3) there was no treatment effect with the use of NV354.

Hydroxyapatite combined with phosphate-solubilizing bacteria immobilized of Cd and inhibited the absorption of Cd by lettuce - Ke Wang; Junqing Zhang; Weilin Li; Zhongyan Deng; Randa S. Makar; Lunguang Yao; Hui Han (Journal of Environmental Chemical Engineering, 2025)

Nutrient production, water consumption, and stresses of large-scale versus small-scale agriculture: A global comparative analysis based on a gridded crop model - Han Su; Timothy Foster; Rick J. Hogeboom; Diana V. Luna-Gonzalez; Oleksandr Mialyk; Bárbara Willaarts; Yafei Wang; Maarten S. Krol (Global Food Security, 2025)

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Trace element removal from wastewater by agricultural biowastes: A data analysis on removal efficacy and optimized conditions - Muhammad Shahid; Sana Khalid; Zeid A. ALOthman; Abdullah A. Al-Kahtani; Irshad Bibi; Rabia Naz; Natasha Natasha; Nabeel Khan Niazi; Jibran Iqbal; Changseok Han; Noor S. Shah; Behzad Murtaza (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The Mantle Structure of North China Craton and Its Tectonic Implications: Insights from Teleseismic P-Wave Tomography - Weiqian Yu; Wei Wei; James O. S. Hammond; Cunrui Han; He Tan; Haoyu Hao (Journal of Marine Science and Engineering, 2025)
To study the mantle structure of the North China Craton (NCC) and its tectonic implications, in particular, the evolution of the rift systems in the Trans-North China Orogen (TNCO), we used teleseismic data recorded by 250 portable seismic stations to invert for the P-wave velocity (Vp) structures of the mantle beneath the NCC. Our results show a large-scale low-Vp anomaly in the shallow mantle and high-Vp anomalies in the deeper upper mantle beneath the eastern NCC, with fine-scale high-Vp anomalies at the lithosphere–asthenosphere boundary, indicating multi-stage lithospheric delamination during the Cenozoic. In the Yan Mountains (YanM), an east–west striking high-Vp anomaly between 60 to 200 km depths and low heat flow suggest the preservation of a thick mantle root. In the TNCO, high-Vp bodies in the upper mantle and the upper part of the mantle transition zone (MTZ) are imaged. The shallower high-Vp anomaly located beneath the Shanxi–Shaanxi Rift (SSR), along with an overlying local-scale low-Vp anomaly, indicates local hot material upwelling due to lithospheric root removal. The India–Eurasia collision’s far-field effects are proposed to cause lithospheric thickening, subsequent root delamination, and the formation and evolution of the SSR.

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Single-cell nanoencapsulation enables fabrication of probiotics-loaded hydrogel dressing with improved wound healing efficacy in vivo - Jung Suk Kim; Beom Jin Kim; Sang Min Lee; Insung S. Choi; Ji Hun Park; Han-Gon Choi; Sung Giu Jin (Journal of Pharmaceutical Investigation, 2025)

Enhancing rice nitrogen use efficiency via plant-microbe-soil interactions: Insights from 15N tracing - Shending Chen; Chang Zhao; Wenyan Yang; Wenjie Wang; Qinying Zhu; Mengqiu He; Ahmed S. Elrys; Lei Meng; Han Meng; Zucong Cai; Jinbo Zhang; Christoph Müller (Applied Soil Ecology, 2025)

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Maximizing heavy metal removal and precious metal recovery with innovative biowaste-derived biosorbents and biochar - Behzad Murtaza; Roshina Arshad; Moon Kinza; Jianxu Wang; Muhammad Shahid; Muhammad Imran; Noor S. Shah; Qasim Ali; Jibran Iqbal; Changseok Han (Process Safety and Environmental Protection, 2025)

Enhanced bio-electrokinetic remediation of cesium-contaminated soil through an optimized Cr(VI)-resistant alkalophilic bacterial degradation approach - Raja Kumaresan Sarankumar; Shichuang Sun; Kuppusamy Sathishkumar; Sandhanasamy Devanesan; Mohamad S. AlSalhi; Ramalinga Viswanathan Mangalaraja; Arunachalam Arulraj; Fengxiang Han; Xinbo Wang (Journal of Environmental Chemical Engineering, 2025)

Curcumin Improves Hippocampal Cell Bioenergetics, Redox and Inflammatory Markers, and Synaptic Proteins, Regulating Mitochondrial Calcium Homeostasis - Claudia Jara; Angie K. Torres; Han S. Park-Kang; Lisette Sandoval; Claudio Retamal; Alfonso Gonzalez; Micaela Ricca; Sebastián Valenzuela; Michael P. Murphy; Nibaldo C. Inestrosa; Cheril Tapia-Rojas (Neurotoxicity Research, 2025)

Adsorption of cadmium ion from water by using non-toxic iron oxide adsorbent; experimental and statistical modelling analysis - D. Gusain; S. Sahani; Y. C. Sharma; S. S. Han (International Journal of Environmental Science and Technology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

3D deformation analysis in a metropolitan area during ongoing subway construction using time series InSAR - Ajay Saraswat; Ya-Lun S. Tsai; Fang-Chiung Chen; Jen-Yu Han (Tunnelling and Underground Space Technology, 2025)

Tuning 1,3-Butadiene selectivity from ethanol in a tandem reaction with induction heating - Han Wang; Ben Ko; John Minh Quang Pham; Nicholas Wang; Carlos Lizandara-Pueyo; Jian-Ping Chen; Roel S. Sánchez-Carrera; Erdem Sasmaz (Chemical Engineering Journal, 2025)

Trends and classification of aerosol observed from MODIS sensor over Northern Europe and the Arctic - Kyung M. Han; Chang H. Jung; Chul H. Song; Ja H. Koo; Young J. Yoon; Bang Y. Lee; Hyun S. Kim; S. Seo (Atmospheric Pollution Research, 2025)

Development of Zinc-Containing Chitosan/Gelatin Coatings with Immunomodulatory Effect for Soft Tissue Sealing around Dental Implants - Jing Han; Jorine G. F. Sanders; Lea Andrée; Bart A. J. A. van Oirschot; Adelina S. Plachokova; Jeroen J. J. P. van den Beucken; Sander C. G. Leeuwenburgh; Fang Yang (Tissue Engineering and Regenerative Medicine, 2025)
BACKGROUND: Soft tissue integration (STI) around dental implant abutments is a prerequisite to prevent bacterial invasion and achieve successful dental implant rehabilitation. However, peri-implant STI is a major challenge after dental abutment placement due to alterations in the immune microenvironment upon surgical dental implant installation. METHODS: Based on known immunomodulatory effects of zinc, we herein deposited zinc/chitosan/gelatin (Zn/CS/Gel) coatings onto titanium substrates to study their effect on macrophages. First, we exposed macrophages to cell culture media containing different zinc ion (Zn 2+ ) concentrations. Next, we explored the immunomodulatory effect of Zn/CS/Gel coatings prepared via facile electrophoretic deposition (EPD). RESULTS: We found that Zn 2+ effectively altered the secretome by reducing the secretion of pro-inflammatory and enhancing pro-regenerative cytokine secretion, particularly at a Zn 2+ supplementation of approximately 37.5 μM. Zn/CS/Gel coatings released Zn 2+ in a concentration range which effectively stimulated pro-regenerative macrophage polarization as demonstrated by M2 macrophage polarization. Additionally, the impact of these Zn 2+ -exposed macrophages on gingival fibroblasts incubated in conditioned medium showed stimulated adhesion, proliferation, and collagen secretion. CONCLUSION: Our promising results suggest that controlled release of Zn 2+ from Zn/CS/Gel coatings could be applied to immunomodulate peri-implant STI, and to enhance dental implant survival.

Black rice phenolics alleviate T2DM through comprehensive regulation of oxidative stress, metabolic pathways and gut microbiota - Shuyan Xu; Xianbao Li; Natalia S. Podio; Yuna Han; Xiao-Yin Wang; Er Sheng Gong (Food Bioscience, 2024)

Tracing the stepwise warming trend in the tropical Indian Ocean through a 40-year record of oxygen isotope composition in Maldives corals - Ke Lin; Tao Han; Kyle Morgan; Paul S. Kench; Yue-Gau Chen; Xianfeng Wang (Earth and Planetary Science Letters, 2024)

Kidney tissue loading reduces the critical cooling/warming rates of cryoprotective solutions - Zonghu Han; Lakshya Gangwar; Bat-Erdene Namsrai; Joseph S. Rao; Michael L. Etheridge; Jeunghwan Choi; Erik B. Finger; John C. Bischof (Cryobiology, 2024)

A Novel Method for Rock Permeability Determination Based on the Pressure Pulse Decay Method and Inverse Numerical Simulations - Qingquan Liu; Biao Lv; Heinz Konietzky; Giovanni S. Alberti; Kun Sang Lee; Chao Zhang; Peizhung Han; Liang Wang; Yuanping Cheng (Rock Mechanics and Rock Engineering, 2024)

Positive cooperativity in synergistic activation of Wnt proteins - Clemence Bonnet; Christiana S. Han; Sophie X. Deng; Jie J. Zheng (Molecular Biology Reports, 2024)
Background Wnt proteins are crucial for embryonic development, stem cell growth, and tissue regeneration. Wnt signaling pathway is activated when Wnt proteins bind to cell membrane receptors. Methods and results We employed a luciferase reporter assay in HEK293STF cells to measure Wnt protein-induced signaling. We observed that Wnt3a uniquely promotes the Wnt/β-catenin pathway through positive cooperativity. Additionally, MFH-ND, a molecular mimic of Wnt ligands, markedly increased Wnt3a-induced signaling in a dose-responsive manner. This suggests that various Wnt ligands can synergistically enhance Wnt pathway activation. Conclusions The study suggests the likelihood of various Wnt ligands coexisting in a single signalosome on the cell membrane, providing new insights into the complexities of Wnt signaling mechanisms.

Correction: A Fresh Take: Seasonal Changes in Terrestrial Freshwater Inputs Impact Salt Marsh Hydrology and Vegetation Dynamics - Maya S. Montalvo; Emilio Grande; Anna E. Braswell; Ate Visser; Bhavna Arora; Erin C. Seybold; Corianne Tatariw; John C. Haskins; Charlie A. Endris; Fuller Gerbl; Mong-Han Huang; Darya Morozov; et al. (Estuaries and Coasts, 2024)

A Fresh Take: Seasonal Changes in Terrestrial Freshwater Inputs Impact Salt Marsh Hydrology and Vegetation Dynamics - Maya S. Montalvo; Emilio Grande; Anna E. Braswell; Ate Visser; Bhavna Arora; Erin C. Seybold; Corianne Tatariw; John C. Haskins; Charlie A. Endris; Fuller Gerbl; Mong-Han Huang; Darya Morozov; et al. (Estuaries and Coasts, 2024)
Salt marshes exist at the terrestrial-marine interface, providing important ecosystem services such as nutrient cycling and carbon sequestration. Tidal inputs play a dominant role in salt marsh porewater mixing, and terrestrially derived freshwater inputs are increasingly recognized as important sources of water and solutes to intertidal wetlands. However, there remains a critical gap in understanding the role of freshwater inputs on salt marsh hydrology, and how this may impact marsh subsurface salinity and plant productivity. Here, we address this knowledge gap by examining the hydrologic behavior, porewater salinity, and pickleweed ( Sarcocornia pacifica also known as Salicornia pacifica) plant productivity along a salt marsh transect in an estuary along the central coast of California. Through the installation of a suite of hydrometric sensors and routine porewater sampling and vegetation surveys, we sought to understand how seasonal changes in terrestrial freshwater inputs impact salt marsh ecohydrologic processes. We found that salt marsh porewater salinity, shallow subsurface saturation, and pickleweed productivity are closely coupled with elevated upland water level during the winter and spring, and more influenced by tidal inputs during the summer and fall. This seasonal response indicates a switch in salt marsh hydrologic connectivity with the terrestrial upland that impacts ecosystem functioning. Through elucidating the interannual impacts of drought on salt marsh hydrology, we found that the severity of drought and historical precipitation can impact contemporary hydrologic behavior and the duration and timing of the upland-marsh hydrologic connectivity. This implies that the sensitivity of salt marshes to climate change involves a complex interaction between sea level rise and freshwater inputs that vary at seasonal to interannual timescales.

Short-term air pollution and greenness exposures on oxidative stress in urban and peri-urban residents in Beijing: A part of AIRLESS study - Wenhao Qi; Hanbin Zhang; Yiqun Han; Wu Chen; Yanbo Teng; Lia Chatzidiakou; Benjamin Barratt; Rod Jones; Frank Kelly; Tong Zhu; Junfeng Zhang; John S. Ji; et al. (Science of The Total Environment, 2024)

Evolution and legacy of East Asian aurochs - Jiawen Hou; Xiwen Guan; Xiaoting Xia; Yang Lyu; Xin Liu; Yuri Mazei; Ping Xie; Fengqin Chang; Xiaonan Zhang; Jialei Chen; Xinyi Li; Fengwei Zhang; et al. (Science Bulletin, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

FireBox and CharBoss: An alternative to open burning of woody biomass - Paul O. Oyier; Han-Sup Han; Dipita Ghosh; Nathaniel Anderson; Deborah S. Page-Dumroese; Daniel W. McCollum; Joanne M. Tirocke; Derek N. Pierson (Biomass and Bioenergy, 2024)

Daily and seasonal changes of sap flow in Gamhong apple cultivar and estimate the tree-level transpiration using Penman-Monteith reference evapotranspiration - Narayan Bhusal; Louis S. Santiago; Joncheon Lee; Sanghak Jeong; In Hee Park; Byeong-Ho Choi; Hun-Joong Kweon; Su-Gon Han; Tae-Myung Yoon (South African Journal of Botany, 2024)

Elimination of microplastics, PFAS, and PPCPs from biosolids via pyrolysis to produce biochar: Feasibility and techno-economic analysis - Arturo A. Keller; Weiwei Li; Yuki Floyd; James Bae; Kayla Marie Clemens; Eleanor Thomas; Ziwei Han; Adeyemi S. Adeleye (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Assessment of bidirectional impact of stigmatization induced self-medication on COVID-19 and malaria transmissions using mathematical modeling: Nigeria as a case study - Wisdom S. Avusuglo; Qing Han; Woldegebriel Assefa Woldegerima; Ali Asgary; Jianhong Wu; James Orbinski; Nicola Bragazzi; Ali Ahmadi; Jude Dzevela Kong (Mathematical Biosciences, 2024)

New strategy for improving postharvest quality of cherry tomatoes: Synergy of plasma-activated water and Welsh onion leaf protein extracts - Fanglei Zou; Chunming Tan; Zhiyi Chang; Tharushi S. Shinali; Bo Zhang; Lili Zhang; Zixin Han; Wei Wu; Nan Shang (Food Control, 2024)

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

Visible light driven ZnFe2O4 for the degradation of oxytetracycline in the presence of HSO5− at semi-pilot scale and additional H2 production - Jibran Iqbal; Noor S. Shah; Javed Ali Khan; Anood Ibrahim; Bilal Masood Pirzada; Mu. Naushad; Changseok Han (Chemical Engineering Journal, 2024)

Incorporation of mechanistic model outputs as features for data-driven models for yield prediction: a case study on wheat and chickpea - Dhahi Al-Shammari; Yang Chen; Niranjan S. Wimalathunge; Chen Wang; Si Yang Han; Thomas F. A. Bishop (Precision Agriculture, 2024)
Introduction Context Data-driven models (DDMs) are increasingly used for crop yield prediction due to their ability to capture complex patterns and relationships. DDMs rely heavily on data inputs to provide predictions. Despite their effectiveness, DDMs can be complemented by inputs derived from mechanistic models (MMs). Methods This study investigated enhancing the predictive quality of DDMs by using as features a combination of MMs outputs, specifically biomass and soil moisture, with conventional data sources like satellite imagery, weather, and soil information. Four experiments were performed with different datasets being used for prediction: Experiment 1 combined MM outputs with conventional data; Experiment 2 excluded MM outputs; Experiment 3 was the same as Experiment 1 but all conventional temporal data were omitted; Experiment 4 utilised solely MM outputs. The research encompassed ten field-years of wheat and chickpea yield data, applying the eXtreme Gradient Boosting (XGBOOST) algorithm for model fitting. Performance was evaluated using root mean square error (RMSE) and the concordance correlation coefficient (CCC). Results and conclusions The validation results showed that the XGBOOST model had similar predictive power for both crops in Experiments 1, 2, and 3. For chickpeas, the CCC ranged from 0.89 to 0.91 and the RMSE from 0.23 to 0.25 t ha −1 . For wheat, the CCC ranged from 0.87 to 0.92 and the RMSE from 0.29 to 0.35 t ha −1 . However, Experiment 4 significantly reduced the model's accuracy, with CCCs dropping to 0.47 for chickpeas and 0.36 for wheat, and RMSEs increasing to 0.46 and 0.65 t ha −1 , respectively. Ultimately, Experiments 1, 2, and 3 demonstrated comparable effectiveness, but Experiment 3 is recommended for achieving similar predictive quality with a simpler, more interpretable model using biomass and soil moisture alongside non-temporal conventional features.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Associations between structural neuroimaging markers of Alzheimer’s risk and scam susceptibility - Melissa Lamar; Konstantinos Arfanakis; Alifiya Kapasi; S. Duke Han; David A. Bennett; Lei Yu; Patricia A. Boyle (Brain Imaging and Behavior, 2024)

Evolutionary ecology of masting: mechanisms, models, and climate change - Michal Bogdziewicz; Dave Kelly; Davide Ascoli; Thomas Caignard; Francesco Chianucci; Elizabeth E. Crone; Emilie Fleurot; Jessie J. Foest; Georg Gratzer; Tomika Hagiwara; Qingmin Han; Valentin Journé; et al. (Trends in Ecology & Evolution, 2024)

P08-05 The Role and mechanism of O-GlcNAcylation in abnormalities of oocyte maturation and early embryonic development caused by PFOS exposure - Z. Wu; Q. Yuan; H. Qian; S. Han; Q. Xu; Y. Xia; Y. Fan; C. Lu (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Changes in the ability of Listeria monocytogenes to resist thermal treatment and simulated gastric condition after exposure to sequential stresses in minced meat - Hui Yang; Yujie Meng; Xintong Han; Xinru Meng; Baowei Yang; Chunling Zhang; Xin Wang; Jiangtao Yu; Fahad Al-Asmari; Anas S Dablool; Manal Y Sameeh; Chao Shi (Food Research International, 2024)

Proximity Labelling Confirms the Involvement of Papain-Like Cysteine Proteases and Chaperones in Cyclotide Biosynthesis - Meng-Han Lee; Mark A. Jackson; Fabian B. H. Rehm; Deborah S. Barkauskas; Wing L. Ho; Kuok Yap; David J. Craik; Edward K. Gilding (Plant Molecular Biology Reporter, 2024)
Cyclotides are disulfide-rich insecticidal peptides from plants that harbour a cyclic cystine knot motif that imparts them with high stability. Like most ribosomally encoded peptides, cyclotides are produced as precursor proteins that are subsequently processed to maturity through proteolytic activity. Although the final maturation of the prototypic cyclotide kalata B1 (kB1) is known to involve asparaginyl endopeptidases, the role of the in planta folding machinery is less well characterized, as is also the case for in planta N-terminal processing enzyme(s). Here, we used proximity labelling to identify proteins involved in the biosynthesis of kB1 in both a cyclotide-bearing plant species, Petunia × hybrida [Regel], and in Nicotiana benthamiana [Domin] that does not naturally produce cyclotides. Together, several ER resident chaperones, protein disulfide isomerases, a papain-like cysteine protease, and an asparaginyl endopeptidase were identified in the kB1 interactome. We found that overexpression of the identified papain-like cysteine protease resulted in an improvement in the yield of cyclic kB1, while this was not the case for the overexpression of protein disulfide isomerases, despite their interaction being verified using bimolecular fluorescence complementation. Together, these results provide a significant advance in our understanding of the role of auxiliary biosynthetic elements for heterologous cyclotide production in plants.

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Prenatal and postnatal early life exposure to greenness and particulate matter of different size fractions in relation to childhood rhinitis - A multi-center study in China - Liu Yang; Han Chen; Huiyu Gao; Ying Wang; Tianyi Chen; Magnus Svartengren; Dan Norbäck; Jing Wei; Xiaohong Zheng; Ling Zhang; Chan Lu; Wei Yu; et al. (Science of The Total Environment, 2024)

QGeoWEPP: An open-source geospatial interface to enable high-resolution watershed-based soil erosion assessment - Han Zhang; Chris S. Renschler (Environmental Modelling & Software, 2024)

Investigating the role of county-level colorectal cancer screening rates on stage at diagnosis of colorectal cancer in rural Georgia - Meng-Han Tsai; Steven S. Coughlin (Cancer Causes & Control, 2024)

Individual differences in responses to unmanned aerial vehicles among Weddell seals, Leptonychotes weddellii - Jikang Park; Won Young Lee; Chang S. Han (Animal Behaviour, 2024)

Thermodynamic and exergy assessment of a biomass oxy-fuel combustion with supercritical carbon dioxide cycle under various recycle flue gas conditions - Jester Lih Jie Ling; Han Saem Park; Ha Eun Lee; Bhanupratap S. Solanki; See Hoon Lee (Journal of Cleaner Production, 2024)

A field trial for remediation of multi-metal contaminated soils using the combination of fly ash stabilization and Zanthoxylum bungeanum- Lolium perenne intercropping system - Han Zhang; Xiaoyong Lv; Zhaowen Yang; Qian Li; Ping Wang; Shuqiang Zhang; Yaqiong Xu; Xuejia Wang; Esmat F. Ali; Peter S. Hooda; Sang Soo Lee; Ronghua Li; et al. (Journal of Environmental Management, 2024)

The reproductive biology of Fagaceae acorns in the current and future climate - Ganesh K. Jaganathan; Tara Canelo; Shyam S. Phartyal; Jiajin Li; Han Kang; Paweł Chmielarz; Mikołaj K. Wawrzyniak; Ashish Tewari; Shruti Shah; Baolin Liu; Jorge A. Sánchez; Keith Berry (Flora, 2024)

Content Validity of the Modified Functional Scale for the Assessment and Rating of Ataxia (f-SARA) Instrument in Spinocerebellar Ataxia - Michele Potashman; Katja Rudell; Ivanna Pavisic; Naomi Suminski; Rinchen Doma; Maggie Heinrich; Linda Abetz-Webb; Melissa Wolfe Beiner; Sheng-Han Kuo; Liana S. Rosenthal; Theresa Zesiwicz; Terry D. Fife; et al. (The Cerebellum, 2024)
The functional Scale for the Assessment and Rating of Ataxia (f-SARA) assesses Gait, Stance, Sitting, and Speech. It was developed as a potentially clinically meaningful measure of spinocerebellar ataxia (SCA) progression for clinical trial use. Here, we evaluated content validity of the f-SARA. Qualitative interviews were conducted among individuals with SCA1 ( n = 1) and SCA3 ( n = 6) and healthcare professionals (HCPs) with SCA expertise (USA, n = 5; Europe, n = 3). Interviews evaluated symptoms and signs of SCA and relevance of f-SARA concepts for SCA. HCP cognitive debriefing was conducted. Interviews were recorded, transcribed, coded, and analyzed by ATLAS.TI software. Individuals with SCA1 and 3 reported 85 symptoms, signs, and impacts of SCA. All indicated difficulties with walking, stance, balance, speech, fatigue, emotions, and work. All individuals with SCA1 and 3 considered Gait, Stance, and Speech relevant f-SARA concepts; 3 considered Sitting relevant (42.9%). All HCPs considered Gait and Speech relevant; 5 (62.5%) indicated Stance was relevant. Sitting was considered a late-stage disease indicator. Most HCPs suggested inclusion of appendicular items would enhance clinical relevance. Cognitive debriefing supported clarity and comprehension of f-SARA. Maintaining current abilities on f-SARA items for 1 year was considered meaningful for most individuals with SCA1 and 3. All HCPs considered meaningful changes as stability in f-SARA score over 1–2 years, 1–2-point change in total f-SARA score, and deviation from natural history. These results support content validity of f-SARA for assessing SCA disease progression in clinical trials.

Hierarchical S-scheme heterojunction systems: A comprehensive review on outstanding photocatalysts - Huimin Han; Muhammad Raheel Khan; Irshad Ahmad; Ayman Al-Qattan; Ijaz Ali; Md Rezaul Karim; Hossein Bayahia; Farhat S. Khan; Zubair Ahmad; Saad Ullah (Journal of Water Process Engineering, 2024)

Performance and emissions evaluation of a multi-cylinder research engine fueled with ethanol, methanol, gasoline Euro-6, E85, and iso-stoichiometric ternary GEM mixtures operated at lean conditions - Tawfik Badawy; Mebin Samuel Panithasan; James W.G. Turner; Jaeheun Kim; Donghee Han; Jonghyeok Lee; Abdullah S. AlRamadan; Junseok Chang (Fuel, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Purinergic ligands induce extracellular acidification and increased ATP turnover in HepG2 cells - Haotong Chen; Yong Han; Abby Hearne; Anna Monarchino; Jeffrey S. Wiseman (Toxicology in Vitro, 2024)

Spontaneous rupture of the right aortic sinus resulting in a sterile aorto-atrial fistula in a pet rabbit (Oryctolagus cuniculus) - L. Cheung; B.A. Scansen; R. Baden; C.Q. Sloan; M. Garcia; S. Han; M.J. Sadar (Journal of Veterinary Cardiology, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

Identifying the external N and Hg inputs to the estuary ecosystem based on the triple isotopic information (δ15NNO3, Δ17ONO3 and δ18ONO3) - Haryun Kim; Hye Seon Kim; Jihee Kim; Dongwoo Yang; Kitack Lee; Kitae Kim; Giyoung Ock; Hyung-Geun Park; Rebecca S. Robinson; Min-Seob Kim; Geun-Ha Park; Ju-Hyoung Kim; et al. (Marine Pollution Bulletin, 2024)

Water pollution scenarios and response options for China - Haoyuan Feng; Joep F. Schyns; Maarten S. Krol; Mengjie Yang; Han Su; Yaoyi Liu; Yongpeng Lv; Xuebin Zhang; Kai Yang; Yue Che (Science of The Total Environment, 2024)

Photocatalytic hydrogen production from seawater splitting: Current status, challenges, strategies and prospective applications - Van-Han Dang; Tuan-Anh Nguyen; Minh-Vien Le; Dinh Quan Nguyen; Yen Han Wang; Jeffery C.-S. Wu (Chemical Engineering Journal, 2024)

Defensive glands in Stylotermitidae (Blattodea, Isoptera) - Himanshu Thakur; Surbhi Agarwal; Aleš Buček; Jaromír Hradecký; Hana Sehadová; Vartika Mathur; Ulugbek Togaev; Thomas van de Kamp; Elias Hamann; Ren-Han Liu; Kuldeep S. Verma; Hou-Feng Li; et al. (Arthropod Structure & Development, 2024)

Indoor particulate matter concentrations and air cleaner intervention association with biomarkers in former smokers with COPD - Ashraf Fawzy; Han Woo; Sarath Raju; Daniel C. Belz; Nirupama Putcha; Marlene S. Williams; Meredith C. McCormack; Kirsten Kohler; Nadia N. Hansel (Environmental Research, 2024)

PFAS release from the subsurface and capillary fringe during managed aquifer recharge - Tonoy K. Das; Ziwei Han; Swapnil Banerjee; Onja D. Raoelison; Adeyemi S. Adeleye; Sanjay K. Mohanty (Environmental Pollution, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

Polyketides from Neohelicosporium griseum: structure assignment and bioactivity investigation - Lijuan Zhang; Jian Ma; Mingfei Yang; Tianming Zhao; Mei Yan Han; Dege Zheng; Ausana Mapook; Yongzhong Lu; Ruvishika S. Jayawardena (Medicinal Chemistry Research, 2024)

Central effects of mouth rinses on endurance and strength performance - Shi Han Tan; Teng Keen Khong; Victor S. Selvanayagam; Ashril Yusof (European Journal of Applied Physiology, 2024)

Metformin treatment of juvenile mice alters aging-related developmental and metabolic phenotypes in sex-dependent and sex-independent manners - Yun Zhu; Morgan Engmann; David Medina; Xiuqi Han; Pratyusa Das; Andrzej Bartke; Buffy S. Ellsworth; Rong Yuan (GeroScience, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Review of risk assessment for navigational safety and supported decisions in arctic waters - X. Yang; Z.Y. Lin; W.J. Zhang; S. Xu; M.Y. Zhang; Z.D. Wu; B. Han (Ocean & Coastal Management, 2024)

Spray-induced gene silencing as a potential tool to control rubber tree powdery mildew disease - Xueren Cao; Qiaohui Han; Jonathan S. West (Physiological and Molecular Plant Pathology, 2024)

Unique bi-continuous phase structure can facilitate the development of fire-resistant surface - Han Zhang; Ling Zhang; Zhen Zhang; Tingting Chen; Jun Zhang; Shaida S. Rumi; Noureddine Abidi (Chemical Engineering Journal, 2024)

The role of pattern recognition receptors in crustacean innate immunity - Bharat Bhusan Patnaik; Snigdha Baliarsingh; Arup Sarkar; A. S. Sahul Hameed; Yong Seok Lee; Yong Hun Jo; Yeon Soo Han; Jyotirmaya Mohanty (Reviews in Aquaculture, 2024)
Crustacean species are among the most valued seafood with socioeconomic and ecological implications in the global fisheries sector. Microbial infections to the farming stock due to continued expansion and aquaculture puts global crustacean production at risk. Understanding and reviewing the complex innate immune system of crustaceans would be pivotal in formulating informed decisions for the control and management of epidemic diseases, thus making the global crustacean aquaculture industry sustainable. Under the purview of innate immunity in crustaceans, pattern recognition receptors (PRRs) represent the sensors capable of discriminating non‐self pathogenic modules and invoking the activation of immune responses. The immunity to infections can be manifested at cellular (via phagocytosis, apoptosis, nodulation and encapsulation) and humoral (effected by prophenoloxidase cascade, lectins, antimicrobial proteins) levels leading to the elimination of pathogens or subversion of the pathogenic implications. In this review, we discuss the participatory role of 12 types of PRRs identified from crustacean species with an exhaustive focus on structural and functional specificities in binding to pathogens and possible execution of the immune activity. Moreover, we have elaborated on the PRRs‐associated or possible signalling cascades (Toll‐NFκB, IMD‐NFκB and JAK‐STAT) in crustacean species that could bridge our understanding of the resistance or susceptibility of the host to varied pathogenic infections thus providing clues to the regulatory mechanisms involved in pathogenesis of infectious diseases and mechanisms of immunity.

Public tap water perceptions and potable reuse acceptance: A cognitive dissonance theoretical understanding - Jesse L. Barnes; Anjala S. Krishen; Han-fen Hu (Journal of Cleaner Production, 2023)

Model-guided design and optimization of CPA perfusion protocols for whole organ cryopreservation - Zonghu Han; Joseph S. Rao; Srivasupradha Ramesh; Jan Hergesell; Bat-Erdene Namsrai; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

SUCCESSFUL TRANSPLANT OF KIDNEYS AFTER VITRIFICATION AND NANOWARMING - Zonghu Han; Joseph S. Rao; Lakshya Gangwar; Bat-Erdene Namsrai; Jacqueline Pasek-Allen; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

Superior performance of an anion exchange membrane water electrolyzer: Sequential electrodeposited Co-based oxygen evolution catalyst - Sanghwi Han; Hyun S. Park; Jeyong Yoon (Chemical Engineering Journal, 2023)

Sensorimotor Cough Dysfunction in Cerebellar Ataxias - Emilie R. Lowell; James C. Borders; Sarah E. Perry; Avery E. Dakin; Jordanna S. Sevitz; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Green chemical and hybrid enzymatic pretreatments for lignocellulosic biorefineries: Mechanism and challenges - Rijuta Ganesh Saratale; Vinoth Kumar Ponnusamy; Grzegorz Piechota; Bartłomiej Igliński; S. Shobana; Jeong-Hoon Park; Ganesh Dattatraya Saratale; Han Seung Shin; J. Rajesh Banu; Vinod Kumar; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Localized conditional induction of brain arteriovenous malformations in a mouse model of hereditary hemorrhagic telangiectasia - Lea Scherschinski; Chul Han; Yong Hwan Kim; Ethan A. Winkler; Joshua S. Catapano; Tyler D. Schriber; Peter Vajkoczy; Michael T. Lawton; S. Paul Oh (Angiogenesis, 2023)
Background Longitudinal mouse models of brain arteriovenous malformations (AVMs) are crucial for developing novel therapeutics and pathobiological mechanism discovery underlying brain AVM progression and rupture. The sustainability of existing mouse models is limited by ubiquitous Cre activation, which is associated with lethal hemorrhages resulting from AVM formation in visceral organs. To overcome this condition, we developed a novel experimental mouse model of hereditary hemorrhagic telangiectasia (HHT) with CreER-mediated specific, localized induction of brain AVMs. Methods Hydroxytamoxifen (4-OHT) was stereotactically delivered into the striatum, parietal cortex, or cerebellum of R26 CreER ; Alk1 2f/2f ( Alk1 -iKO) littermates. Mice were evaluated for vascular malformations with latex dye perfusion and 3D time-of-flight magnetic resonance angiography (MRA). Immunofluorescence and Prussian blue staining were performed for vascular lesion characterization. Results Our model produced two types of brain vascular malformations, including nidal AVMs (88%, 38/43) and arteriovenous fistulas (12%, 5/43), with an overall frequency of 73% (43/59). By performing stereotaxic injection of 4-OHT targeting different brain regions, Alk1 -iKO mice developed vascular malformations in the striatum (73%, 22/30), in the parietal cortex (76%, 13/17), and in the cerebellum (67%, 8/12). Identical application of the stereotaxic injection protocol in reporter mice confirmed localized Cre activity near the injection site. The 4-week mortality was 3% (2/61). Seven mice were studied longitudinally for a mean (SD; range) duration of 7.2 (3; 2.3−9.5) months and demonstrated nidal stability on sequential MRA. The brain AVMs displayed microhemorrhages and diffuse immune cell invasion. Conclusions We present the first HHT mouse model of brain AVMs that produces localized AVMs in the brain. The mouse lesions closely resemble the human lesions for complex nidal angioarchitecture, arteriovenous shunts, microhemorrhages, and inflammation. The model’s longitudinal robustness is a powerful discovery resource to advance our pathomechanistic understanding of brain AVMs and identify novel therapeutic targets.

Ferrous-immobilized iron saccharide complexes for electro-synthesis of ammonia via NORR - Siranuysh Badalyan; Anush Mnoyan; Alexey V. Sobolev; Iana S. Soboleva; Igor A. Presniakov; Jae-Rang Youn; Taeyoul Han; DongYeon Kim; Kyubock Lee (Chemical Engineering Journal, 2023)

Cell-Free DNA as a Biomarker in a Rodent Model of Chlorpyrifos Poisoning Causing Mitochondrial Dysfunction - Shih-Han Kao; Frances S. Shofer; John C. Greenwood; Oladunni Alomaja; Abhay Ranganathan; Sarah Piel; Clementina Mesaros; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

Low-cost urban carbon monitoring network and implications for china: a comprehensive review - Hongzhi Jiang; Yang Han; Amr S. Zalhaf; Ping Yang; Congling Wang (Environmental Science and Pollution Research, 2023)

P24-13: Round Robin Study in Korea on alternative test method for evaluating skin irritation potential of medical devices - J. Yi; Y.S. Park; J.E. Im; H.-W. Moon; J.H. Kim; K.J. Kim; H.S. Yoon; Y. Lee; H.J. Ko; I.S. Kim; J.S. Kim; J.-S. Han; et al. (Toxicology Letters, 2023)

P19-07: 13-week repeated-dose oral toxicity study in rats treated with a mixture of Cirsium japonicum and Brassica oleracea extracts - W.-J. Im; M.-H. Yang; H. Park; J.-S. Han; J.-W. Cho; M.H. Yoo; Y.-B. Kim (Toxicology Letters, 2023)

P09-32: The mechanism of PGE2 on apoptosis of rat ovarian granulosa cells induced by MEHP - S. Ren; X. Han; X. Li; X. Li; L. Ye (Toxicology Letters, 2023)

A newly isolated Bacillus megaterium OQ560352 promotes maize growth in saline soils by altering rhizosphere microbial communities and organic phosphorus utilization - Qili Zhu; Jiachao Zhou; Min Sun; Hongshun Li; Yejun Han; Jimin Lv; Yanfeng Li; Xixing Zhang; Timothy S. George; Wei Liu; Zihao Wang; Yingxiang Sun (Rhizosphere, 2023)

Perfluorooctanoic acid dominates the molecular-level effects of a mixture of equal masses of perfluorooctanoic acid and perfluorooctane sulfonic acid in earthworm - Ziwei Han; Bolaji F. Oyeyemi; Jenny E. Zenobio; Omobayo A. Salawu; Adeyemi S. Adeleye (Journal of Hazardous Materials, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Spatial and temporal water chemistry variations of hydraulic fracturing flowback and produced waters from the Duvernay Formation - Xiaomeng Wang; Nicholas Utting; Michael S. Reid; Chunqing Jiang; Daniel S. Alessi; Jun Han; Lisa Duffin; Chenxing Sun (Applied Geochemistry, 2023)

Age-related reductions in within-individual variation increase the repeatability of mating behaviour - Chang S. Han; Niels J. Dingemanse (Behavioral Ecology and Sociobiology, 2023)

An integrated watershed-scale framework to model nitrogen transport and transformations - Han Qiu; Jie Niu; Dean G. Baas; Mantha S. Phanikumar (Science of The Total Environment, 2023)

SARS-CoV-2 3CL-protease inhibitors derived from ML300: investigation of P1 and replacements of the 1,2,3-benzotriazole - Alice Hooper; Jonathan D. Macdonald; Brenna Reilly; Joshua Maw; Aidan P. Wirrick; Sang Hoon Han; A. Abigail Lindsey; Emma G. Rico; Todd Romigh; Christopher M. Goins; Nancy S. Wang; Shaun R. Stauffer (Medicinal Chemistry Research, 2023)

Rebound effect of carbon emissions of new energy vehicle consumption: a case study of Beijing - J. Zhou; W. Fang; X. Han; Q. Sun; D. Liu; S. Liu (International Journal of Environmental Science and Technology, 2023)

Deconstructing the causes of July sea level variability in the East Sea from 1994 to 2021 - MyeongHee Han; Yeon S. Chang; Jeseon Yoo (Frontiers in Marine Science, 2023)
In 2021 the East Sea experienced its highest July sea level (65.09 cm), as well as the highest July sea surface and atmospheric temperatures, in the 29 years between 1993 and 2021. We present several methodologies to identify the more important causes of sea level change (SLC) in a semi-enclosed sea and explore the critical fluctuation of ocean mass transport divergence during a period of rapid sea level rise. Based on satellite altimeter data in the East Sea, the SLC, as reflected in the absolute dynamic topography (ADT), which is the ADT difference between the last and first days of a month, was 7.18 cm in July 2021. This may reflect a combination of oceanic and atmospheric factors: ocean heat transport divergence among the Korea, Tsugaru, and Soya Straits was found to contribute 2.32 cm of SLC, atmospheric heat flux at the sea surface contributed 2.87 cm of SLC, and mass divergence (including errors) accounted for 1.98 cm of SLC. The monthly mean sea level (ADT) variation in the East Sea should be examined in terms of the oceanic and atmospheric fluxes, and the SLC sources can additionally be divided into heat and others (mass + errors). The proportional contribution of heat to SLC from 1994 to 2021 was 97.4%. Although the contributions of mass and errors were small, there were substantial temporal fluctuations, as their standard deviation reached up to 96.7% of that of SLC in ADT. In the near future, a more precise analysis of the contributions of mass and errors to SLC is required.

Sulfonated graphene oxide-based pervaporation membranes inspired by a tortuous brick and mortar structure for enhanced resilience against silica scaling and organic fouling - Hasan Fareed; Kyunghoon Jang; Woojin Lee; In S. Kim; Seunghee Han (Chemosphere, 2023)

Molecular identification and functional analysis of Niemann-Pick type C2 proteins，carriers for semiochemicals and other hydrophobic compounds in the brown dog tick, Rhipicephalus linnaei - Dejuan Liang; Huaqing Chen; Liping An; Yao Li; Peizhen Zhao; Archana Upadhyay; Bill S. Hansson; Jianguo Zhao; Qian Han (Pesticide Biochemistry and Physiology, 2023)

Investigating bonding mechanism of rubberized RAP asphalt mastic from rheological and physiochemical perspectives - Ahmed S. Mohamed; Yifeng Han; Zhenglong Cao; Xiyong Xu; Feipeng Xiao (Journal of Cleaner Production, 2023)

Cecropin P1 antimicrobial peptide modulates differential expression of immune relevant genes in rainbow trout (Oncorhynchus mykiss) gill cell line, RTgill-W1 - Yueh-Chiang Han; Brian S. Shepherd (Fish & Shellfish Immunology, 2023)

BasinMaker 3.0: A GIS toolbox for distributed watershed delineation of complex lake-river routing networks - Ming Han; Hongren Shen; Bryan A. Tolson; James R. Craig; Juliane Mai; Simon G.M. Lin; Nandita B. Basu; Frezer S. Awol (Environmental Modelling & Software, 2023)

Evolution of debris flow activities in the epicentral area, 10 years after the 2008 Wenchuan earthquake - S. Zhang; J.Y. Peng; M.P. Zhang; Y.B. Chen; Y.Y. Han; C.X. Su; D.Y. Zhuang (Engineering Geology, 2023)

Retinal microvasculature is a potential biomarker for acute mountain sickness - Yuan Xie; Diya Yang; Alex S. Huang; Yiquan Yang; Ying Han; Yunxiao Sun; Kai Cao; Huaizhou Wang; Shizheng Wu; Qiang Zhu; Guozhong Wang; Tianyi Wu; et al. (Science China Life Sciences, 2023)

Recent trends in management strategies for two major maize borers: Ostrinia nubilalis and Sesamia nonagrioides - Gülay Kaçar; Ana Butrón; Dimitrios Kontogiannatos; Peng Han; Maria Fernanda G. V. Peñaflor; Gema P. Farinós; Fangneng Huang; William D. Hutchison; Bruno H. S. de Souza; Rosa Ana Malvar; Anna Kourti; Ricardo Ramirez-Romero; et al. (Journal of Pest Science, 2023)

MXenes: from past to future perspectives - Massoud Malaki; Xiantao Jiang; Hanlin Wang; Ramakrishna Podila; Han Zhang; Paolo Samorì; Rajender S. Varma (Chemical Engineering Journal, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Galectin-3-centered paracrine network mediates cardiac inflammation and fibrosis upon β-adrenergic insult - Guomin Hu; Jimin Wu; Huijun Gu; Xiangning Deng; Wenli Xu; Shan Feng; Shuaixing Wang; Yao Song; Zhengda Pang; Xiuling Deng; Aleksandr E. Vendrov; Nageswara R. Madamanchi; et al. (Science China Life Sciences, 2023)

Soil grit influences the effects of earthworms (Lumbricus terrestris) on seed damage - Shu Han Gan; Michael J. McTavish; Robert S. Bourchier; Sandy M. Smith (Applied Soil Ecology, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Comparing “apples” and “oranges” in the Woodford Shale: Pitfalls of the thermal maturity gradient approach for constraining evolution of mudrock porosity - Elizabeth T. Baruch; Stefan C. Löhr; Shujun Han; David N. Dewhurst; Alan S. Collins (Marine and Petroleum Geology, 2023)

Molecular Analysis and Sex-specific Response of the Hepcidin Gene in Yellow Perch (Perca Flavescens) Following Lipopolysaccharide Challenge - Xing Lu; Yueh-Chiang Han; Brian S. Shepherd; Ying Xiang; Dong-Fang Deng; Bryan T. Vinyard (Probiotics and Antimicrobial Proteins, 2023)

Identification of nitrate sources in tap water sources across South Korea using multiple stable isotopes: Implications for land use and water management - Hyejung Jung; Yun S. Kim; Jisu Yoo; So Jeong Han; Jeonghoon Lee (Science of The Total Environment, 2023)

Thermomechanically micronized sugar beet pulp: Emulsification performance and the contribution of soluble elements and insoluble fibrous particles - Jiawei Lin; Zhong-Sheng Tang; Charles S. Brennan; Jayani Chandrapala; Wenhong Gao; Zhong Han; Xin-An Zeng (Food Research International, 2023)

Mechanistic understanding of aging behaviors of critical-material-free Li4Ti5O12//LiNi0.9Mn0.1O2 cells with fluorinated carbonate-based electrolytes for safe energy storage with ultra-long life span - Yicheng Zhang; Glenn Teeter; Nikita S. Dutta; Sarah Frisco; Sang-Don Han (Chemical Engineering Journal, 2023)

Life cycle-carbon footprints for environmental performance/labeling of crop-based food products: analyses of complementary functional units and hotspots - N. C. O; S. C. Pak; R. J. Ri; H. I. Han (International Journal of Environmental Science and Technology, 2023)

Alteration in Cerebral Metabolism in a Rodent Model of Acute Sub-lethal Cyanide Poisoning - Oladunni Alomaja; Frances S. Shofer; John C. Greenwood; Sarah Piel; Carly Clayman; Clementina Mesaros; Shih-Han Kao; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Cometabolic decomposition of trichloroethylene by recombinant hydroxyquinol 1,2-dioxygenase - Jimin Yu; Mayulee Suwannakaew; Chatchai Rodwihok; Sangwoon Woo; Sung Yoon Park; Yejee Lim; Han S. Kim (Chemical Engineering Journal, 2023)

Correction to: Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2023)

Application of photogrammetry and in-situ test technology in the stability evaluation of gangue dump slope - Han Liu; Shu Jisen; Gerson S. V. Tovele; Chen Tao; Chen Shuzhao; Broohm Kote Mawugnon; Liu Peng (Bulletin of Engineering Geology and the Environment, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Probing the nature of soil organic matter - Zhe (Han) Weng; Johannes Lehmann; Lukas Van Zwieten; Stephen Joseph; Braulio S. Archanjo; Bruce Cowie; Lars Thomsen; Mark J. Tobin; Jitraporn Vongsvivut; Annaleise Klein; Casey L. Doolette; Helen Hou; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Characterization and thermal removal of organophosphorus pesticides in soils from a former agrochemical factory - W. Han; Y. Ye; S. Liu; J. Sima (International Journal of Environmental Science and Technology, 2022)

Tectonic controls on geomorphological dynamics and sediment dispersal in source-to-sink systems in the Qingdong Sag, Bohai Bay Basin - Z. Han; S. Dai; H. Jia; T. Liu; Z. Jiang (Australian Journal of Earth Sciences, 2022)

Development and characterization of microsatellite markers for the rubber tree powdery mildew pathogen Oidium heveae - Qiaohui Han; Yongxiang He; Haiyan Che; Daquan Luo; Jonathan S. West; Xueren Cao (European Journal of Plant Pathology, 2022)

Sustained-release ketamine-loaded lipid-particulate system: in vivo assessment in mice - Weizhi Xu; Faheem Maqbool; Vinod Kumar; James R. Falconer; Cedric S. Cui; Trent M. Woodruff; Karin Borges; Andrew K. Whittaker; Maree T. Smith; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Spray-Dried and Spray-Freeze-Dried Powder Formulations of an Anti-Interleukin-4Rα Antibody for Pulmonary Delivery - Harry W. Pan; Han Cong Seow; Jason C. K. Lo; Jinlin Guo; Lingqiao Zhu; Susan W. S. Leung; Chenghai Zhang; Jenny K. W. Lam (Pharmaceutical Research, 2022)

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables - Jessica L. Gronniger; Zhao Wang; Genevieve R. Brandt; Christopher S. Ward; Despina Tsementzi; Han Mu; Junyao Gu; Zackary I. Johnson; Konstantinos T. Konstantinidis; Dana E. Hunt (Environmental Microbiology, 2022)
Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest week‐over‐week changes in the microbiome (i.e. identifying disturbance as events that alter the community composition). In general, these microbiome disturbances were not clearly linked to specific environmental factors and responsive taxa largely differed, aside from SAR11, which generally declined. However, several disturbance metagenomes identified increased phage‐associated genes, suggesting that unexplained community shifts might be caused by increased mortality. Furthermore, a category 1 hurricane, the only event that would likely be classified a priori as an environmental disturbance, was not an outlier in microbiome composition, but did enhance a bloom in seasonally abundant phytoplankton. Thus, as extreme environmental changes intensify, assumptions of what constitutes a disturbance should be re‐examined in the context of ecological history and microbiome responses.

Pore development in terrestrial shale reservoirs: the Permian Lucaogou Formation, Junggar Basin, northwestern China - Y. Jin; J. Tian; C. Han; H. Liu; L. Dong; S. Dan (Australian Journal of Earth Sciences, 2022)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Factors associated with symptoms of poor mental health among women factory workers in China’s supply chain - K. K. Sznajder; S. D. Harlow; J. Wang; L. Tso; Y. Ashagre; C. Han (International Archives of Occupational and Environmental Health, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2022)

Mechanical properties and fracture evolution process of Beishan granite under tensile state - C. S. Wang; J. F. Liu; Y. W. Zhao; S. J. Han (Bulletin of Engineering Geology and the Environment, 2022)

The role of context in identifying linkages between SDG 2 (food) and SDG 6 (water) - Han Su; Maarten S. Krol; Rick J. Hogeboom (Sustainability Science, 2022)
The Sustainable Development Goals (SDGs) of the United Nation’s Agenda 2030 are formulated to promote the development of integrated, multisectoral policies that explicitly consider linkages across SDGs. Although multiple recent studies have tried to identify linkages across SDGs, the role of contextual factors in identifying SDG linkages is neither well described nor understood. For the case of SDG 2 and SDG 6, this study aims to (i) identify linkages—at country and SDG target level—through the application of various quantitative and qualitative identification methods, and (ii) explore contextual factors to explain the differences across identified linkages. Hereto, we first conducted a text analysis of 195 Voluntary National Reviews (VNRs) reported by 159 countries from 2016 to 2020. Next, we synthesized linkages reported by previous qualitative studies and conducted a quantitative (correlation) analysis on the UN’s SDG database. Last, we compared identified linkages across methods, paying special attention to the role of context. From the text analysis, we identified 221 country-specific linkages between 25 SDG target pairs and observed that countries increasingly report SDG linkages in their VNRs over time. Comparing text analysis, existing qualitative studies, and our quantitative correlation analysis, we found substantial differences between the number and nature of linkages identified. These differences can be explained in part by methodological considerations, but to a significant extent also by contextual factors, such as project design, technology application, phase of interventions, and project scale. We conclude by discussing the strengths and limitations of the methods involved, and suggestions for future studies.

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Adrenal hypofunction associated with ashwagandha (Withania somnifera) supplementation: a case report - Christopher H. Fry; David Fluck; Thang S. Han (Toxicology and Environmental Health Sciences, 2022)
Objective The use of herbal medicinal supplements has gained huge popularity world-wide, but scientific evidence of their effectiveness and safety remains scarce. Ashwagandha ( Withania somnifera ) is one such product, claimed to alleviate pain and anxiety by lowering circulating cortisol levels. Withanolides, which are the principal bioactive compounds of ashwagandha, are naturally occurring steroids and may suppress adrenal function. Here, we describe the effect of ashwagandha on adrenal function of a 41-year-old woman with a low body mass index and who suffered chronic pain and lethargy. Methods Adrenal function was assessed by the short Synacthen test (SST) during and after treatment with ashwagandha supplementation. Results Whilst taking daily ashwagandha supplement (21.4 mg of Withanolides), for ten weeks, a SST showed a minimal response to 250 μg of an intramuscular injection of Synacthen (tetracosactide): cortisol levels at T 0min = 287 nmol/l, T 30min = 289 nmol/l, and T 60min = 328 nmol/l; from a morning baseline cortisol level of 480 nmol/l prior to taking the supplement. Ashwagandha was discontinued for two weeks, and a repeat SST was performed showing a completely normal adrenal response: cortisol level at T 0min = 275 nmol/l, T 30min = 623 nmol/l and T 60min = 674 nmol/l. Conclusion Ten weeks of ashwagandha supplementation was associated with adrenal hypofunction, which was reversible after a two-week break. Individuals taking ashwagandha should be aware of this potentially detrimental effect. Future studies are suggested to assess whether long-term treatment with ashwagandha could lead to permanent suppression of adrenal function, and to elucidate the effects of ashwagandha compounds on adrenal steroidogenic pathway and hypothalamic–pituitary–adrenal axis.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Delayed rFGF21 Administration Improves Cerebrovascular Remodeling and White Matter Repair After Focal Stroke in Diabetic Mice - Yinghua Jiang; Jinrui Han; Yadan Li; Yinga Wu; Ning Liu; Samuel X. Shi; Li Lin; Jing Yuan; Shusheng Wang; Ming-Ming Ning; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2022)

Identification and Verification of the Ability of Cdk5 to Phosphorylate Deubiquitinating Enzyme BRCC3 In Vitro - C. H. Zhang; K. Qin; S. L. Tian; Y. Han; S. Y. Xu; X. Y. Shao (Bulletin of Experimental Biology and Medicine, 2022)

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Turnover Time of the East Sea (Sea of Japan) Meridional Overturning Circulation - MyeongHee Han; Yeon S. Chang; Hyoun-Woo Kang; Dong-Jin Kang; Yong Sun Kim (Frontiers in Marine Science, 2021)
The East Sea (ES; Sea of Japan) meridional overturning circulation (MOC) serves as a crucial mechanism for the transportation of dissolved, colloidal, and suspended particulate matters, including pollutants, on the surface to deep waters via thermohaline circulation. Therefore, understanding the structure of the ES MOC is critical for characterizing its temporal and spatial distribution. Numerous studies have estimated these parameters indirectly using chemical tracers, severely limiting the accuracy of the results. In this study, we provide a method for directly estimating the turnover times of the ES MOC using the stream functions calculated from HYbrid Coordinate Ocean Model (HYCOM) reanalysis data by averaging the flow pattern in the meridional 2-D plane. Because the flow pattern is not consistent but various over time, three cases of stream function fields were computed over a 20-year period. The turnover time was estimated by calculating the time required for water particles to circulate along the streamlines. In the cases of multiple (two or three) convection cells, we considered all possible scenarios of the exchange of water particles between adjacent cells, so that they circulated over those cells until finally returning to the original position and completing the journey on the ES MOC. Three different cell cases were tested, and each case had different water particle exchange scenarios. The resulting turnover times were 17.91–58.59 years, 26.41–37.28 years, and 8.68–45.44 years for the mean, deep, and shallow convection cases, respectively. The maximum turnover time, namely 58.59 years, was obtained when circulating the water particle over all three cells, and it was approximately half of that estimated by the chemical tracers in previous studies (∼100 years). This underestimation arose because the streamlines and water particle movement were not calculated in the shallow (<300 m) and deep areas (>3,000 m) in this study. Regardless, the results of this study provide insight into the ES MOC dynamics and indicate that the traditional chemical turnover time represents only one of the various turnover scenarios that could exist in the ES.

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

Evaluation of homing pigeon feather tissue as a biomonitor of environmental metal concentrations in China - Jia Cui; Richard S. Halbrook; Shuying Zang; Mary Ann Masdo; Shuang Han (Ecotoxicology, 2021)

Diversity, abundance, and distribution of anammox bacteria in shipping channel sediment of Hong Kong by analysis of DNA and RNA - Xiaowei Zhang; Han Meng; Yuchun Yang; Wensheng Lan; Weidong Wang; Paul K. S. Lam; Xiao-Yan Li; Ji-Dong Gu (Ecotoxicology, 2021)

Eutrophication and Hypoxia in Tropical Negombo Lagoon, Sri Lanka - Hsueh-Han Hsieh; Ming-Hsiu Chuang; Yung-Yen Shih; W. Sanjaya Weerakkody; Wei-Jen Huang; Chin-Chang Hung; François L. L. Muller; R. R. M. K. P. Ranatunga; D. S. Wijethunga (Frontiers in Marine Science, 2021)
Hypoxic events are becoming frequent in some estuaries and coastal waters due to over-enrichment of anthropogenic nutrients, organic matter, and/or due to restricted water circulation. The coastal lagoons and estuaries of Sri Lanka are facing high population pressure and lacking sufficient infrastructure. Coastal lagoons may receive high anthropogenic inputs of natural or untreated nitrogen and phosphorus wastes, and consequently result in hypoxic conditions while sluggish circulation occurred. In this study, we examined the spatiotemporal variability of eutrophication and hypoxia in the Negombo Lagoon, one of the most productive and sensitive coastal ecosystems in Sri Lanka. Based on seasonal measurements of dissolved oxygen, nutrients, chlorophyll- a (Chl- a ), particulate and dissolved organic carbon (POC and DOC), we concluded that eutrophication and hypoxia occurred in both the dry and wet seasons. The main contributing factors were high seawater temperature and poor water circulation in the dry season and high nutrient loading combined with elevated POC and DOC inputs in the wet season.

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Experimental and Numerical Characterization of Lower Huron Shale as a Heterogeneous Material - Ming Fan; Yanhui Han; Xinyu Tan; Liang Fan; Ellen S. Gilliland; Nino Ripepi; Cheng Chen (Rock Mechanics and Rock Engineering, 2021)

Self-reported experiences of discrimination in older black adults are associated with insula functional connectivity - S. Duke Han; Melissa Lamar; Debra Fleischman; Namhee Kim; David A. Bennett; Tené T. Lewis; Konstantinos Arfanakis; Lisa L. Barnes (Brain Imaging and Behavior, 2021)

Genetic diversity and population genetic structure in native Ethiopian donkeys (Equus asinus) inferred from equine microsatellite markers - E. Kefena; S. Rosenbom; A. Beja-Pereira; M. Yusuf Kurtu; J. L. Han; T. Dessie (Tropical Animal Health and Production, 2021)

Drought tolerance in selected aerobic and upland rice varieties is driven by different metabolic and antioxidative responses - Giovanni Melandri; Hamada AbdElgawad; Kristýna Floková; Diaan C. Jamar; Han Asard; Gerrit T. S. Beemster; Carolien Ruyter-Spira; Harro J. Bouwmeester (Planta, 2021)
Main conclusions Sugar-mediated osmotic acclimation and a strong antioxidative response reduce drought-induced biomass loss at the vegetative stage in rice. Abstract A clear understanding of the physiological and biochemical adaptations to water limitation in upland and aerobic rice can help to identify the mechanisms underlying their tolerance to low water availability. In this study, three indica rice varieties-IR64 (lowland), Apo (aerobic), and UPL Ri-7 (upland)-, that are characterized by contrasting levels of drought tolerance, were exposed to drought at the vegetative stage. Drought-induced changes in biomass, leaf metabolites and oxidative stress markers/enzyme activities were analyzed in each variety at multiple time points. The two drought-tolerant varieties, Apo and UPL Ri-7 displayed a reduced water use in contrast to the susceptible variety IR64 that displayed high water consumption and consequent strong leaf dehydration upon drought treatment. A sugar-mediated osmotic acclimation in UPL Ri-7 and a strong antioxidative response in Apo were both effective in limiting the drought-induced biomass loss in these two varieties, while biomass loss was high in IR64, also after recovery. A qualitative comparison of these results with the ones of a similar experiment conducted in the field at the reproductive stage showed that only Apo, which also in this stage showed the highest antioxidant power, was able to maintain a stable grain yield under stress. Our results show that different metabolic and antioxidant adaptations confer drought tolerance to aerobic and upland rice varieties in the vegetative stage. The effectiveness of these adaptations differs between developmental stages. Unraveling the genetic control of these mechanisms might be exploited in breeding for new rice varieties adapted to water-limited environments.

Untapped Knowledge about Water Reuse: the Roles of Direct and Indirect Educational Messaging - Jesse L. Barnes; Anjala S. Krishen; Han-fen Hu (Water Resources Management, 2021)

Genome-wide Identification and Expression Pattern Analysis of the HD-Zip Transcription Factor Family in Pineapple (Ananas Comosus) - Qiao Zhou; Liping Liu; Han Cheng; Zeyun Li; MyatHnin Wai; Tiantian Luo; Xingyue Jin; Heming Zhao; S. V. G. N. Priyadarshani; Yuan Qin (Tropical Plant Biology, 2021)

Diabetes Mellitus/Poststroke Hyperglycemia: a Detrimental Factor for tPA Thrombolytic Stroke Therapy - Yinghua Jiang; Ning Liu; Jinrui Han; Yadan Li; Pierce Spencer; Samuel J. Vodovoz; Ming-Ming Ning; Gregory Bix; Prasad V. G. Katakam; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2021)

Application of two-level design method on subway tunnel crossing active fault: a case study on Urumqi subway tunnel intersected by reverse fault dislocation - S. An; L. J. Tao; X. C. Han; Y. Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

Electrospun Microvasculature for Rapid Vascular Network Restoration - Je-Hyun Han; Ung Hyun Ko; Hyo Jun Kim; Seunggyu Kim; Jessie S. Jeon; Jennifer H. Shin (Tissue Engineering and Regenerative Medicine, 2021)

The Interface Motion and Hydrodynamic Shear of the Liquid Slosh in Syringes - Yuchen Zhang; Dingding Han; Zhongwang Dou; Jean-Christophe Veilleux; Galen H. Shi; David S. Collins; Pavlos P. Vlachos; Arezoo M. Ardekani (Pharmaceutical Research, 2021)

Apple phenology occurs earlier across South Korea with higher temperatures and increased precipitation - Jung Gun Cho; Sunil Kumar; Seung Heui Kim; Jeom-Hwa Han; Catherine S. Durso; Patrick H. Martin (International Journal of Biometeorology, 2021)

Fatigue-Damage Evolution Characteristics of Interbeded Marble Subjected to Dynamic Uniaxial Cyclic Loads - Y. Wang; S. H. Gao; J. Q. Han (Geotechnical and Geological Engineering, 2021)

Neuronal and Non-neuronal Cell Types Displaying Circadian Rhythmicity in the Mammalian Suprachiasmatic Nucleus - S. K. Tahajjul Taufique; Han Wang (Neuroscience Bulletin, 2021)

Dissociable dopaminergic and pavlovian influences in goal-trackers and sign-trackers on a model of compulsive checking in OCD - D. M. Eagle; C. Schepisi; S. Chugh; S. Desai; S. Y. S. Han; T. Huang; J. J. Lee; C. Sobala; W. Ye; A. L. Milton; T. W. Robbins (Psychopharmacology, 2020)
Rationale Checking is a functional behaviour that provides information to guide behaviour. However, in obsessive-compulsive disorder (OCD), checking may escalate to dysfunctional levels. The processes underpinning the transition from functional to dysfunctional checking are unclear but may be associated with individual differences that support the development of maladaptive behaviour. We examined one such predisposition, sign-tracking to a pavlovian conditioned stimulus, which we previously found associated with dysfunctional checking. How sign-tracking interacts with another treatment with emerging translational validity for OCD-like checking, chronic administration of the dopamine D 2 receptor agonist quinpirole, is unknown. Objectives We tested how functional and dysfunctional checking in the rat observing response task (ORT) was affected by chronic quinpirole administration in non-autoshaped controls and autoshaped animals classified as sign-trackers or goal-trackers. Methods Sign-trackers or goal-trackers were trained on the ORT before the effects of chronic quinpirole administration on checking were assessed. Subsequently, the effects on checking of different behavioural challenges, including reward omission and the use of unpredictable reinforcement schedules, were tested. Results Prior autoshaping increased checking. Sign-trackers and goal-trackers responded differently to quinpirole sensitization, reward omission and reinforcement uncertainty. Sign-trackers showed greater elevations in dysfunctional checking, particularly during uncertainty. By contrast, goal-trackers predominantly increased functional checking responses, possibly in response to reduced discrimination accuracy in the absence of cues signalling which lever was currently active. Conclusions The results are discussed in terms of how pavlovian associations influence behaviour that becomes compulsive in OCD and how this may be dependent on striatal dopamine D 2 receptors.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Dietary exposure assessment of cadmium, arsenic, and lead in market rice from Sri Lanka - Lin Liu; Jialiang Han; Xiaohang Xu; Zhidong Xu; Kasun S. Abeysinghe; Anjana J. Atapattu; P. Mangala C. S. De Silva; Qinhui Lu; Guangle Qiu (Environmental Science and Pollution Research, 2020)

Targeting the Aryl Hydrocarbon Receptor in Stem Cells to Improve the Use of Food as Medicine - Huajun Han; Arul Jayaraman; Stephen Safe; Robert S. Chapkin (Current Stem Cell Reports, 2020)

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

The Contribution of Small Phytoplankton Communities to the Total Dissolved Inorganic Nitrogen Assimilation Rates in the East/Japan Sea: An Experimental Evaluation - Panthalil S. Bhavya; Jae Joong Kang; Hyo Keun Jang; HuiTae Joo; Jae Hyung Lee; Jang Han Lee; Jung Woo Park; Kwanwoo Kim; Hyung Chul Kim; Sang Heon Lee (Journal of Marine Science and Engineering, 2020)
As a part of Korean-Russian joint expeditions in the East/Japan Sea during 2012 and 2015, a set of total and small (

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

White matter correlates of scam susceptibility in community-dwelling older adults - Melissa Lamar; Konstantinos Arfanakis; Lei Yu; Shengwei Zhang; S. Duke Han; Debra A. Fleischman; David A. Bennett; Patricia A. Boyle (Brain Imaging and Behavior, 2020)

DNA Polyplexes of a Phosphorylcholine-Based Zwitterionic Polymer for Gene Delivery - Kandarp M. Dave; Linjiang Han; Meredith A. Jackson; Lindsay Kadlecik; Craig L. Duvall; Devika S Manickam (Pharmaceutical Research, 2020)

Anthropogenic Contaminants and Histopathological Findings in Stranded Cetaceans in the Southeastern United States, 2012–2018 - Annie Page-Karjian; Catherine F. Lo; Branson Ritchie; Craig A. Harms; David S. Rotstein; Sushan Han; Sayed M. Hassan; Andreas F. Lehner; John P. Buchweitz; Victoria G. Thayer; Jill M. Sullivan; Emily F. Christiansen; et al. (Frontiers in Marine Science, 2020)

Multiomic immune clockworks of pregnancy - Laura S. Peterson; Ina A. Stelzer; Amy S. Tsai; Mohammad S. Ghaemi; Xiaoyuan Han; Kazuo Ando; Virginia D. Winn; Nadine R. Martinez; Kevin Contrepois; Mira N. Moufarrej; Stephen Quake; David A. Relman; et al. (Seminars in Immunopathology, 2020)
Preterm birth is the leading cause of mortality in children under the age of five worldwide. Despite major efforts, we still lack the ability to accurately predict and effectively prevent preterm birth. While multiple factors contribute to preterm labor, dysregulations of immunological adaptations required for the maintenance of a healthy pregnancy is at its pathophysiological core. Consequently, a precise understanding of these chronologically paced immune adaptations and of the biological pacemakers that synchronize the pregnancy “immune clock” is a critical first step towards identifying deviations that are hallmarks of peterm birth. Here, we will review key elements of the fetal, placental, and maternal pacemakers that program the immune clock of pregnancy. We will then emphasize multiomic studies that enable a more integrated view of pregnancy-related immune adaptations. Such multiomic assessments can strengthen the biological plausibility of immunological findings and increase the power of biological signatures predictive of preterm birth

Ontogenetic niche shifts as a driver of seasonal migration - Wimke Fokkema; Henk P. van der Jeugd; Thomas K. Lameris; Adriaan M. Dokter; Barwolt S. Ebbinge; André M. de Roos; Bart A. Nolet; Theunis Piersma; Han Olff (Oecologia, 2020)
Ontogenetic niche shifts have helped to understand population dynamics. Here we show that ontogenetic niche shifts also offer an explanation, complementary to traditional concepts, as to why certain species show seasonal migration. We describe how demographic processes (survival, reproduction and migration) and associated ecological requirements of species may change with ontogenetic stage (juvenile, adult) and across the migratory range (breeding, non-breeding). We apply this concept to widely different species (dark-bellied brent geese ( Branta b. bernicla ), humpback whales ( Megaptera novaeangliae ) and migratory Pacific salmon ( Oncorhynchus gorbuscha ) to check the generality of this hypothesis. Consistent with the idea that ontogenetic niche shifts are an important driver of seasonal migration, we find that growth and survival of juvenile life stages profit most from ecological conditions that are specific to breeding areas. We suggest that matrix population modelling techniques are promising to detect the importance of the ontogenetic niche shifts in maintaining migratory strategies. As a proof of concept, we applied a first analysis to resident, partial migratory and fully migratory populations of barnacle geese ( Branta leucopsis ). We argue that recognition of the costs and benefits of migration, and how these vary with life stages, is important to understand and conserve migration under global environmental change.

Glycosaminoglycan remodeling during chondrogenic differentiation of human bone marrow−/synovial-derived mesenchymal stem/stromal cells under normoxia and hypoxia - João C. Silva; Xiaorui Han; Teresa P. Silva; Ke Xia; Paiyz E. Mikael; Joaquim M. S. Cabral; Frederico Castelo Ferreira; Robert J. Linhardt (Glycoconjugate Journal, 2020)

Revisiting the plant growth-promoting rhizobacteria: lessons from the past and objectives for the future - Abhinav Aeron; Ekta Khare; Chaitanya Kumar Jha; Vijay Singh Meena; Shadia Mohammed Abdel Aziz; Mohammed Tofazzal Islam; Kangmin Kim; Sunita Kumari Meena; Arunava Pattanayak; Hosahatti Rajashekara; Ramesh Chandra Dubey; Bihari Ram Maurya; et al. (Archives of Microbiology, 2020)

Reciprocal comparison of geodetically sensed and modeled vertical hydrological loading products - Vagner G. Ferreira; Zhiqiang Liu; Henry C. Montecino; Peng Yuan; Caleb I. Kelly; Abubakar S. Mohammed; Lu Y. Han (Acta Geodaetica et Geophysica, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Water-Saving Traits Can Protect Wheat Grain Number Under Progressive Soil Drying at the Meiotic Stage: A Phenotyping Approach - Michele Faralli; Kevin S. Williams; Jiwan Han; Fiona M. K. Corke; John H. Doonan; Peter S. Kettlewell (Journal of Plant Growth Regulation, 2019)

Evaluation of aromatic hydrocarbon decomposition catalyzed by the dioxygenase system and substitution of ferredoxin and ferredoxin reductase - Jun Won Yang; Wooyoun Cho; Yejee Lim; Sungyoon Park; Dayoung Lee; Hyun-A Jang; Han S. Kim (Environmental Science and Pollution Research, 2019)

An acute increase in water temperature can increase free amino acid concentrations in the blood, brain, liver, and muscle in goldfish (Carassius auratus) - Yunhao Wang; Guofeng Han; Cuong V. Pham; Kiyohiko Koyanagi; Yandejia Song; Ryunosuke Sudo; Johan Lauwereyns; John F. Cockrem; Mitsuhiro Furuse; Vishwajit S. Chowdhury (Fish Physiology and Biochemistry, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Requirements for a Coastal Hazards Observing System - Jérôme Benveniste; Anny Cazenave; Stefano Vignudelli; Luciana Fenoglio-Marc; Rashmi Shah; Rafael Almar; Ole Andersen; Florence Birol; Pascal Bonnefond; Jérôme Bouffard; Francisco Calafat; Estel Cardellach; et al. (Frontiers in Marine Science, 2019)

Local Application of Autologous Platelet-Rich Fibrin Patch (PRF-P) Suppresses Regulatory T Cell Recruitment in a Murine Glioma Model - Wojciech K. Panek; Katarzyna C. Pituch; Jason Miska; Julius W. Kim; Aida Rashidi; Deepak Kanojia; Aurora Lopez-Rosas; Yu Han; Dou Yu; Catalina Lee Chang; J. Robert Kane; Peng Zhang; et al. (Molecular Neurobiology, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Tremor in the Degenerative Cerebellum: Towards the Understanding of Brain Circuitry for Tremor - Ruo-Yah Lai; Darya Tomishon; Karla P. Figueroa; Stefan M. Pulst; Susan Perlman; George Wilmot; Christopher M. Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G. Shakkottai; Sarah H. Ying; Theresa Zesiewicz; et al. (The Cerebellum, 2019)

Maternal sensitivity predicts anterior hippocampal functional networks in early childhood - Qiang Wang; Han Zhang; Chong-Yaw Wee; Annie Lee; Joann S. Poh; Yap-Seng Chong; Kok Hian Tan; Peter D. Gluckman; Fabian Yap; Marielle V. Fortier; Anne Rifkin-Graboi; Anqi Qiu (Brain Structure and Function, 2019)

Expression Profiling of Notch Signalling Pathway and Gamma-Secretase Activity in the Brain of Ts1Cje Mouse Model of Down Syndrome - Hadri Hadi Yusof; Han-Chung Lee; Eryse Amira Seth; Xiangzhong Wu; Chelsee A. Hewitt; Hamish S Scott; Pike-See Cheah; Yue-Ming Li; De-Ming Chau; King-Hwa Ling (Journal of Molecular Neuroscience, 2019)

Compositional and structural analysis of glycosaminoglycans in cell-derived extracellular matrices - João C. Silva; Marta S. Carvalho; Xiaorui Han; Ke Xia; Paiyz E. Mikael; Joaquim M. S. Cabral; Frederico Castelo Ferreira; Robert J. Linhardt (Glycoconjugate Journal, 2019)

High frequency and diversity of parechovirus A in a cohort of Malawian children - Lieke Brouwer; Eveliina Karelehto; Alvin X. Han; Xiomara V. Thomas; Andrea H. L. Bruning; Job C. J. Calis; Michaël Boele van Hensbroek; Brenda M. Westerhuis; Darsha Amarthalingam; Sylvie M. Koekkoek; Sjoerd P. H. Rebers; Kamija S. Phiri; et al. (Archives of Virology, 2019)

A Review on the Macromolecular Compositions of Phytoplankton and the Implications for Aquatic Biogeochemistry - P. S. Bhavya; Bo Kyung Kim; Naeun Jo; Kwanwoo Kim; Jae Joong Kang; Jae Hyung Lee; Dabin Lee; Jang Han Lee; HuiTae Joo; So Hyun Ahn; Yewon Kim; Jun-Oh Min; et al. (Ocean Science Journal, 2019)

Fronto-parietal numerical networks in relation with early numeracy in young children - Han Zhang; Chong-Yaw Wee; Joann S. Poh; Qiang Wang; Lynette P. Shek; Yap-Seng Chong; Marielle V. Fortier; Michael J. Meaney; Birit F. P. Broekman; Anqi Qiu (Brain Structure and Function, 2019)

Detecting hydrological consistency between soil moisture and precipitation and changes of soil moisture in summer over the Tibetan Plateau - X. Meng; R. Li; L. Luan; S. Lyu; T. Zhang; Y. Ao; B. Han; L. Zhao; Y. Ma (Climate Dynamics, 2018)

Amyloid-β Increases Tau by Mediating Sirtuin 3 in Alzheimer’s Disease - Junxiang Yin; Pengcheng Han; Melissa Song; Megan Nielsen; Thomas G. Beach; Geidy E. Serrano; Winnie S. Liang; Richard J. Caselli; Jiong Shi (Molecular Neurobiology, 2018)

White matter correlates of temporal discounting in older adults - S. Duke Han; Konstantinos Arfanakis; Debra A. Fleischman; Lei Yu; David A. Bennett; Patricia A. Boyle (Brain Structure and Function, 2018)

Gallaecimonas mangrovi sp. nov., a novel bacterium isolated from mangrove sediment - Wei-Yan Zhang; Ye Yuan; Deng-Quan Su; Xiao-Ping He; Shuai-Bo Han; Slava S. Epstein; Shan He; Min Wu (Antonie van Leeuwenhoek, 2018)

Shake table tests on RC frame infilled by slitted masonry panels - Terry Y. P. Yuen; Han-hui Zhang; J. S. Kuang; Qunxian Huang (Bulletin of Earthquake Engineering, 2018)

Wicking Property of Graft Material Enhanced Bone Regeneration in the Ovariectomized Rat Model - Seunghyun Kim; Taeho Ahn; Myung-Ho Han; Chunsik Bae; Daniel S. Oh (Tissue Engineering and Regenerative Medicine, 2018)

Forward modelling of global gravity fields with 3D density structures and an application to the high-resolution (~ 2 km) gravity fields of the Moon - M. Šprlák; S.-C. Han; W. E. Featherstone (Journal of Geodesy, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Observed and modelled temperature and precipitation extremes over Southeast Asia from 1972 to 2010 - W. K. Cheong; B. Timbal; N. Golding; S. Sirabaha; K. F. Kwan; T. A. Cinco; B. Archevarahuprok; V. H. Vo; D. Gunawan; S. Han (International Journal of Climatology, 2018)
Regional assessments of trends in climate extremes are necessary for countries to make informed decisions about adaptation strategies and to put these changes into a global context. A workshop bringing together several Southeast Asian countries has delivered a new set of daily weather observations suitable to analyse the changes in temperature and precipitation extremes between 1972 and 2010. The use of a consistent and widely tested methodology in this study allows a direct comparison with results from other parts of the world. Trends in a range of climate extremes indices were assessed focusing on spatial variation in these trends. For most locations temperature trends obtained in this study appear broadly consistent with previous assessments; for some locations stronger trends have been detected through the inclusion of new data. In contrast to earlier studies, evidence of trends in precipitation extremes is emerging, with significant increasing trends in both regional and subregional data. In addition, large correlations between regional rainfall extremes and large‐scale features such as El Niño‐Southern Oscillation and the Indian Ocean Dipole were identified. Finally, the observed trends are compared with a regional climate model reconstruction of the historical period. It was found that the model captures very well the trends and spatial variation of temperature extremes across the region, albeit with an underestimation of the more extreme indices. In contrast, the trends in precipitation extremes are largely overestimated, particularly in the western side of Southeast Asia.

A revisit to fishmeal usage and associated consequences in Chinese aquaculture - Dong Han; Xiujuan Shan; Wenbing Zhang; Yushun Chen; Qingyin Wang; Zhongjie Li; Guofan Zhang; Pao Xu; Jiale Li; Shouqi Xie; Kangsen Mai; Qisheng Tang; et al. (Reviews in Aquaculture, 2018)
China has dominated global aquaculture production for more than two decades. Aquaculture production in China increased from 24.6 million metric tons (mmt) in 2000 to 47.5 mmt in 2014, an increment of 93.1%. Along with the fast‐growing aquaculture industry, aquafeed production in China increased from 5.1 mmt in 2000 to 19.0 mmt in 2014, an increment of 272.5%. However, despite the rapid increase in aquafeed production, the fishmeal usage in aquafeeds in China has remained stable over the years. Fishmeal imports into China remained relatively steady at 1.0–1.5 mmt per annum from 2000 to 2014. An often unacknowledged fact is that China contributes more than 60% to the world aquaculture production at a cost of only 25–30% of the world fishmeal output. This review attempts to explain why the fishmeal usage has not increased proportionately with the increasing aquafeed production in China from several angles: (i) the current status of fishmeal usage in Chinese aquaculture; (ii) the relationship between the decreasing dietary inclusions of fishmeal and improved feed techniques, especially the use of alternative protein sources for fishmeal; (iii) the dominance of Chinese aquaculture by low trophic level species of plants, filter feeders, herbivores and omnivores and consequent low demands for fishmeal; and (iv) the increasing price of fishmeal and the management of exploitation of wild fisheries in the main fishmeal exporting countries to China. The trends and prospects of fishmeal usage in the future in Chinese aquaculture and the associated consequences are also addressed. Like other countries, China is now actively developing both resource conservation‐based capture fisheries and environment‐friendly freshwater and marine aquaculture systems. Aquaculture will be the main source of aquatic food in the future and will also indirectly contribute to save the world wild fisheries, and China will be main player that will continue to contribute towards this end.

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Exploiting fruit byproducts for eco-friendly nanosynthesis: Citrus × clementina peel extract mediated fabrication of silver nanoparticles with high efficacy against microbial pathogens and rat glial tumor C6 cells - Rijuta Ganesh Saratale; Han-Seung Shin; Gopalakrishnan Kumar; Giovanni Benelli; Gajanan S. Ghodake; Yuan Yuan Jiang; Dong Su Kim; Ganesh Dattatraya Saratale (Environmental Science and Pollution Research, 2018)

Study on the performance of the micropile-mechanically stabilized earth wall - Zhi-chao Zhang; Ronald Y. S. Pak; Yu-min Chen; Han-long Liu (Journal of Mountain Science, 2018)

Matrix Metalloproteinase-8 Inhibition Prevents Disruption of Blood–Spinal Cord Barrier and Attenuates Inflammation in Rat Model of Spinal Cord Injury - Hemant Kumar; Min-Jae Jo; Hyemin Choi; Manjunatha S. Muttigi; Seil Shon; Byung-Joo Kim; Soo-Hong Lee; In-Bo Han (Molecular Neurobiology, 2018)

Metal concentrations in homing pigeon lung tissue as a biomonitor of atmospheric pollution - Jia Cui; Richard S. Halbrook; Shuying Zang; Shuang Han; Xinyu Li (Ecotoxicology, 2018)

Visco-elastic–Plastic Creep Constitutive Relation of Tunnels in Soft Schist - Y. Y. Zuo; L. Han; H. Hu; S. Y. Luo; Y. Zhang; X. M. Chen (Geotechnical and Geological Engineering, 2018)

Genetic Variants Within Molecular Targets of Antipsychotic Treatment: Effects on Treatment Response, Schizophrenia Risk, and Psychopathological Features - Marco Calabrò; Stefano Porcelli; Concetta Crisafulli; Sheng-Min Wang; Soo-Jung Lee; Changsu Han; Ashwin A. Patkar; Prakash S. Masand; Diego Albani; Ilaria Raimondi; Gianluigi Forloni; Sofia Bin; et al. (Journal of Molecular Neuroscience, 2018)

African origin and global distribution patterns: Evidence inferred from phylogenetic and biogeographical analyses of ectomycorrhizal fungal genus Strobilomyces - Li H. Han; Bang Feng; Gang Wu; Roy E. Halling; Bart Buyck; Nourou S. Yorou; Sydney T. N. Ebika; Zhu L. Yang (Journal of Biogeography, 2018)
Aim The ectomycorrhizal genus Strobilomyces is widely distributed throughout many parts of the world, but its origin, divergence and distribution patterns remain largely unresolved. In this study, we aim to explore the species diversity, distribution and evolutionary patterns of Strobilomyces on a global scale by establishing a general phylogenetic framework with extensive sampling. Location Africa, Australasia, East Asia, Europe, North America, Central America and Southeast Asia. Methods The genealogical concordance phylogenetic species recognition method was used to delimit phylogenetic species. Divergence times were estimated using a Bayesian uncorrelated lognormal relaxed molecular clock. The ancestral area and host of Strobilomyces were inferred via the programs rasp and mesquite . The change of diversification rate over time was estimated using Ape, Laser and Bammtools software packages. Results We recognize a novel African clade and 49 phylogenetic species with morphological evidence, including 18 new phylogenetic species and 23 previously described ones. Strobilomyces probably originated in Africa, in association with Detarioideae/Phyllanthaceae/Monotoideae during the early Eocene. The dispersal to Southeast Asia can be explained by Wolfe's “Boreotropical migration” hypothesis. East Asia, Australasia, Europe and North/Central America are primarily the recipients of immigrant taxa during the Oligocene or later. A rapid radiation implied by one diversification shift was inferred within Strobilomyces during the Miocene. Main conclusions An unexpected phylogenetic species diversity within Strobilomyces was uncovered. The highest diversity, resulting probably from a rapid radiation, was found in East Asia. Dispersal played an important role in the current distribution pattern of Strobilomyces . The Palaeotropical disjunction is explained by species dispersal from Africa to Southeast Asia through boreotropical forests during the early Eocene. Species from the Northern Hemisphere and Australasia are largely derived from immigrant ancestors from Southeast Asia.

ccaA and FBP/SBPase Derived From Cyanobacteria Improved Photosynthetic Capacity in Rice - Han Y. Gong; Yang Li; Gen Fang; Dao H. Hu; Zhao H. Wang; Guang H. Yu; Yang S. Li (Plant Molecular Biology Reporter, 2017)

Correction to: Detectable Neuropsychological Differences in Early Preclinical Alzheimer’s Disease: a Meta-Analysis - S. Duke Han; Caroline P. Nguyen; Nikki H. Stricker; Daniel A. Nation (Neuropsychology Review, 2017)

Detectable Neuropsychological Differences in Early Preclinical Alzheimer’s Disease: A Meta-Analysis - S. Duke Han; Caroline P. Nguyen; Nikki H. Stricker; Daniel A. Nation (Neuropsychology Review, 2017)

Causes for the reversal of North Indian Ocean decadal sea level trend in recent two decades - U. Srinivasu; M. Ravichandran; Weiqing Han; S. Sivareddy; H. Rahman; Yuanlong Li; Shailesh Nayak (Climate Dynamics, 2017)

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Removal of Cr(VI) and phenol coupled with the reduction of sulfate by sulfate-reducing bacteria sludge - X. Han; T.-X. Zhou; S.-W. Xu; Y. Li; Y.-F. Wang; Y. Liu (International Journal of Environmental Science and Technology, 2017)

Widespread generalist clones are associated with range and niche expansion in allopolyploids of Pacific Northwest Hawthorns ( Crataegus L.) - J. M. Coughlan; S. Han; S. Stefanović; T. A. Dickinson (Molecular Ecology, 2017)
Range and niche expansion are commonly associated with transitions to asexuality, polyploidy and hybridity (allopolyploidy) in plants. The ability of asexual polyploids to colonize novel habitats may be due to widespread generalist clones, multiple ecologically specialized clones, or may be a neutral by‐product of multiple, independent origins of asexual polyploids throughout the range. We have quantified niche size and divergence for hawthorns of the Pacific Northwest using data from herbarium vouchers with known cytotypes. We find that all polyploid niches diverge from that of the diploid range, and allopolyploids have the broadest niches. Allotetraploids have the largest niche and the widest geographic distribution. We then assessed the genetic mechanism of range expansion by surveying the ecological and geographic distribution of genotypes within each cytotype from sites in which fine‐scale habitat assessments were completed. We find no isolation by either geographic or ecological distance in allopolyploids, suggesting high dispersal and colonization ability. In contrast, autotriploids and diploids show patterns of isolation by geographic distance. We also compared the geographic and ecological distributions of clonal genotypes with those of randomly drawn sites of the most widespread cytotype. We found that most clones are geographically widespread and occur in a variety of habitats. We interpret these findings to suggest that patterns of range and niche expansion in Pacific Northwest Hawthorns may stem from these widespread, ecologically generalist clones of hybrid origin.

Identifying functional groups and ecological roles of tropical and subtropical freshwater Cladocera in Asia - Eric Zeus C. Rizo; Yangliang Gu; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2017)

Evaluating the impact of varied compliance to lung cancer screening recommendations using a microsimulation model - Summer S. Han; S. Ayca Erdogan; Iakovos Toumazis; Ann Leung; Sylvia K. Plevritis (Cancer Causes & Control, 2017)

Performance of IUCN proxies for generation length - Han Chi Fung; Robin S. Waples (Conservation Biology, 2017)
One of the criteria used by the International Union for Conservation of Nature (IUCN) to assess threat status is the rate of decline in abundance over 3 generations or 10 years, whichever is longer. The traditional method for calculating generation length ( T ) uses age‐specific survival and fecundity, but these data are rarely available. Consequently, proxies that require less information are often used, which introduces potential biases. The IUCN recommends 2 proxies based on adult mortality rate, = α + 1/ d , and reproductive life span, = α + z * RL, where α is age at first reproduction, d is adult mortality rate, RL is reproductive life span, and z is a coefficient derived from data for comparable species. We used published life tables for 78 animal and plant populations to evaluate precision and bias of these proxies by comparing and with true generation length. Mean error rates in estimating T were 31% for and 20% for , but error rates for were 16% when we subtracted 1 year ( ), as suggested by theory; also provided largely unbiased estimates regardless of the true generation length. Performance of depends on compilation of detailed data for comparable species, but our results suggest taxonomy is not a reliable indicator of comparability. All 3 proxies depend heavily on a reliable estimate of age at first reproduction, as we illustrated with 2 test species. The relatively large mean errors for all proxies emphasized the importance of collecting the detailed life‐history information necessary to calculate true generation length. Unfortunately, publication of such data is less common than it was decades ago. We identified generic patterns of age‐specific change in vital rates that can be used to predict expected patterns of bias from applying .

Study on the application of an activator for steel slag powder–cement in muddy soil - Y. K. Wu; X. S. Hu; R. Hu; T. Han; J. L. Yu (European Journal of Environmental and Civil Engineering, 2017)

Metabolites from the co-culture of nigranoic acid and Umbelopsis dimorpha SWUKD3.1410, an endophytic fungus from Kadsura angustifolia - L. Wang; D. Qin; K. Zhang; Q. Huang; S. Liu; M. J. Han; J. Y. Dong (Natural Product Research, 2017)

The Initial Symptom and Motor Progression in Spinocerebellar Ataxias - Lan Luo; Jie Wang; Raymond Y Lo; Karla P Figueroa; Stefan M Pulst; Pei-Hsin Kuo; Susan Perlman; George Wilmot; Christopher M Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G Shakkottai; et al. (The Cerebellum, 2017)

Magnetically recoverable TiO2-WO3 photocatalyst to oxidize bisphenol A from model wastewater under simulated solar light - S. Dominguez; M. Huebra; C. Han; P. Campo; M.N. Nadagouda; M.J. Rivero; I. Ortiz; D. D. Dionysiou (Environmental Science and Pollution Research, 2017)

In vitro cytotoxicity assessment of a West Virginia chemical spill mixture involving 4-methylcyclohexanemethanol and propylene glycol phenyl ether - Alice A. Han; Emily B. Fabyanic; Julie V. Miller; Maren S. Prediger; Nicole Prince; Julia A. Mouch; Jonathan Boyd (Environmental Monitoring and Assessment, 2017)

Molecular response of Sargassum vulgare to acidification at volcanic CO 2 vents: insights from de novo transcriptomic analysis - Amit Kumar; Immacolata Castellano; Francesco Paolo Patti; Massimo Delledonne; Hamada Abdelgawad; Gerrit T. S. Beemster; Han Asard; Anna Palumbo; Maria Cristina Buia (Molecular Ecology, 2017)
Ocean acidification is an emerging problem that is expected to impact ocean species to varying degrees. Currently, little is known about its effect on molecular mechanisms induced in fleshy macroalgae. To elucidate genome wide responses to acidification, a transcriptome analysis was carried out on Sargassum vulgare populations growing under acidified conditions at volcanic CO 2 vents and compared with populations in a control site. Several transcripts involved in a wide range of cellular and metabolic processes were differentially expressed. No drastic changes were observed in the carbon acquisition processes and RuBis CO level. Moreover, relatively few stress genes, including those for antioxidant enzymes and heat‐shock proteins, were affected. Instead, increased expression of transcripts involved in energy metabolism, photosynthetic processes and ion homeostasis suggested that algae increased energy production to maintain ion homeostasis and other cellular processes. Also, an increased allocation of carbon to cell wall and carbon storage was observed. A number of genes encoding proteins involved in cellular signalling, information storage and processing and transposition were differentially expressed between the two conditions. The transcriptional changes of key enzymes were largely confirmed by enzymatic activity measurements. Altogether, the changes induced by acidification indicate an adaptation of growth and development of S. vulgare at the volcanic CO 2 vents, suggesting that this fleshy alga exhibits a high plasticity to low pH and can adopt molecular strategies to grow also in future more acidified waters.

Herbivore exclusion promotes a more stochastic plant community assembly in a natural grassland - Juan Alberti; Elisabeth S. Bakker; Roel van Klink; Han Olff; Christian Smit (Ecology, 2017)
Both bottom‐up (e.g., nutrients) and top‐down (e.g., herbivory) forces structure plant communities, but it remains unclear how they affect the relative importance of stochastic and deterministic processes in plant community assembly. Moreover, different‐sized herbivores have been shown to have contrasting effects on community structure and function, but their effects on the processes governing community assembly (i.e., how they generate the impacts on structure) remain largely unknown. We evaluated the influence of bottom‐up and top‐down forces on the relative importance of deterministic and stochastic processes during plant community assembly. We used the data of a 7‐yr factorial experiment manipulating nutrient availability (ambient and increased) and the presence of vertebrate herbivores (>1 kg) of different body size in a floodplain grassland in The Netherlands. We used a null model that describes a community composition expected by chance (i.e., stochastic assembly) and compared the plant community composition in the different treatments with this null model (the larger the difference, the more deterministically assembled). Our results showed that herbivore exclusion promoted a more stochastic plant community assembly, whereas increased nutrients played a relatively minor role in determining the relative importance of stochasticity in community assembly. Large herbivores facilitated intermediate‐sized mammal herbivores, resulting in synergistic effects of enhanced grazing pressure and a more deterministic and convergent plant community assembly. We conclude that herbivores can act as strong deterministic forces during community assembly in natural systems. Our results also reveal that although large‐ and intermediate‐sized mammal herbivores often have contrasting effects on many community and ecosystem properties, they can also synergistically homogenize plant communities.

The Next Decade of Big Data in Ecosystem Science - S. L. LaDeau; B. A. Han; E. J. Rosi-Marshall; K. C. Weathers (Ecosystems, 2017)

Development of high-density interspecific genetic maps for the identification of QTLs conferring resistance to Valsa ceratosperma in apple - Yi Tan; Song Lv; Xinying Liu; Ting Gao; Tianhong Li; Yi Wang; Ting Wu; Xinzhong Zhang; Yuepeng Han; Schuyler S. Korban; Zhenhai Han (Euphytica, 2017)

Mechanical Properties of High Entropy Alloy Al0.1CoCrFeNi for Peripheral Vascular Stent Application - Karthik Alagarsamy; Aleksandra Fortier; Mageshwari Komarasamy; Nilesh Kumar; Atif Mohammad; Subhash Banerjee; Hai-Chao Han; Rajiv S. Mishra (Cardiovascular Engineering and Technology, 2016)

Contribution of GABRG2 Polymorphisms to Risk of Epilepsy and Febrile Seizure: a Multicenter Cohort Study and Meta-analysis - Batoul Sadat Haerian; Larry Baum; Patrick Kwan; Stacey S. Cherny; Jae-Gook Shin; Sung Eun Kim; Bok-Ghee Han; Hui Jan Tan; Azman Ali Raymond; Chong Tin Tan; Zahurin Mohamed (Molecular Neurobiology, 2016)

A self-contained GIM-aided Abel retrieval method to improve GNSS-Radio Occultation retrieved electron density profiles - S. Tulasi Ram; Shin-Yi Su; Lung-Chi Tsai; Chao Han Liu (GPS Solutions, 2016)

Persistent infiltration and pro-inflammatory differentiation of monocytes cause unresolved inflammation in brain arteriovenous malformation - Rui Zhang; Zhenying Han; Vincent Degos; Fanxia Shen; Eun-Jung Choi; Zhengda Sun; Shuai Kang; Michael Wong; Wan Zhu; Lei Zhan; Helen M. Arthur; S. Paul Oh; et al. (Angiogenesis, 2016)

Outbreak of hirame rhabdovirus infection in cultured spotted sea bass Lateolabrax maculatus on the western coast of Korea - H‐G Seo; J W Do; S H Jung; H‐J Han (Journal of Fish Diseases, 2016)
In this study, we determined the cause of a disease outbreak in spotted sea bass, Lateolabrax maculatus reared in culture cages on the western coast of Korea in 2013. The major signs in the diseased fish exhibited were haemorrhaging on the membranes of the abdomen, gastrointestinal organs and opercular gills, as well as an enlarged spleen. No external morphological signs of infection were visible, except for a darkening in colour. No parasites or pathological bacteria were isolated from the diseased fish; however, epithelioma papulosum cyprini ( EPC ) cells inoculated with tissue homogenates from the diseased fish showed cytopathic effects ( CPE s). Virus particles in the EPC cells were bullet‐shaped, 185–225 nm long and 70–80 nm wide, characteristic of Rhabdoviridae. Polymerase chain reaction analyses of homogenized tissues from the diseased fish and supernatants of cell cultures with CPE s indicated specific, 553‐bp‐long fragments corresponding to the matrix protein gene of the hirame rhabdovirus ( HIRRV ). Phylogenetically, the HIRRV phosphoprotein gene of spotted sea bass was more closely related to phosphoproteins from Chinese and Polish HIRRV strains than from other Korean strains. To our knowledge, this is the first report of HIRRV infection in cultured spotted sea bass.

Experimental Investigation on Mechanical Behavior and Permeability Evolution of a Porous Limestone Under Compression - B. Han; S. Y. Xie; J. F. Shao (Rock Mechanics and Rock Engineering, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Determinants of cancer screening in Asian-Americans - Quoc-Dien Trinh; Hanhan Li; Christian P. Meyer; Julian Hanske; Toni K. Choueiri; Gally Reznor; Stuart R. Lipsitz; Adam S. Kibel; Paul K. Han; Paul L. Nguyen; Mani Menon; Jesse D. Sammon (Cancer Causes & Control, 2016)

Application of Microneedle Arrays for Enhancement of Transdermal Permeation of Insulin: In Vitro Experiments, Scaling Analyses and Numerical Simulations - V. Leeladurga; U. Chandra Teja; S. K. Ashraf Sultana; K. Sudeep; V. Sai Sri Anusha; Tao Han; Buchi N. Nalluri; Diganta B. Das (AAPS PharmSciTech, 2016)

The distribution and elevated solubility of lead, arsenic and cesium in contaminated paddy soil enhanced with the electrokinetic field - X. Mao; F. X. Han; X. Shao; K. Guo; J. McComb; S. Njemanze; Z. Arslan; Z. Zhang (International Journal of Environmental Science and Technology, 2016)

A homozygous truncating mutation in PUS3 expands the role of tRNA modification in normal cognition - Ranad Shaheen; Lu Han; Eissa Faqeih; Nour Ewida; Eman Alobeid; Eric M. Phizicky; Fowzan S. Alkuraya (Human Genetics, 2016)

Autism spectrum disorder prevalence and associations with air concentrations of lead, mercury, and arsenic - Aisha S. Dickerson; Mohammad H. Rahbar; Amanda V. Bakian; Deborah A. Bilder; Rebecca A. Harrington; Sydney Pettygrove; Russell S. Kirby; Maureen S. Durkin; Inkyu Han; Lemuel A. Moyé; Deborah A. Pearson; Martha Slay Wingate; et al. (Environmental Monitoring and Assessment, 2016)

Fine Mapping of qDor7, a Major QTL Affecting Seed Dormancy in Sorghum (Sorghum bicolor (L.) Moench) - Pan Li; Emma S. Mace; Yan Guo; Lijie Han; Mumu Wang; Yanfang He; Jun Chen; Nana Yuyama; David R. Jordan; Hongwei Cai (Tropical Plant Biology, 2016)

Grey matter correlates of susceptibility to scams in community-dwelling older adults - S. Duke Han; Patricia A. Boyle; Lei Yu; Konstantinos Arfanakis; Bryan D. James; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Perverted Head-Shaking and Positional Downbeat Nystagmus in Essential Tremor - Young Eun Kim; Ji Soo Kim; Hui-Jun Yang; Ji Young Yun; Han-Joon Kim; Gwanhee Ehm; Jong-Min Kim; Beom S. Jeon (The Cerebellum, 2016)

Construction of a high density linkage map and its application in the identification of QTLs for soluble sugar and organic acid components in apple - Baiquan Ma; Shuang Zhao; Benhong Wu; Dongmei Wang; Qian Peng; Albert Owiti; Ting Fang; Liao Liao; Collins Ogutu; Schuyler S. Korban; Shaohua Li; Yuepeng Han (Tree Genetics & Genomes, 2016)

Binding, fractionation, and distribution of Cs, Co, and Sr in a US coastal soil under saturated and field capacity moisture regimes - Leondra S. Lawson; Jacqueline Q. McComb; Ruipong Dong; Fengxiang X. Han; Christian Roger; Zikri Arslan; Hongtao Yu (Journal of Soils and Sediments, 2016)

Characterization of the disposition of fostamatinib in Japanese subjects including pharmacokinetic assessment in dry blood spots: results from two phase I clinical studies - Paul Martin; S. Y. Amy Cheung; Mark Yen; David Han; Michael Gillen (European Journal of Clinical Pharmacology, 2016)

Noncovalent and covalent immobilization of oxygenase on single-walled carbon nanotube for enzymatic decomposition of aromatic hydrocarbon intermediates - Yanasinee Suma; Christina S. Kang; Han S. Kim (Environmental Science and Pollution Research, 2016)

Belowground competition among invading detritivores - Chih‐Han Chang; Katalin Szlavecz; Timothy Filley; Jeffrey S. Buyer; Michael J. Bernard; Scott L. Pitz (Ecology, 2016)
The factors regulating soil animal communities are poorly understood. Current theory favors niche complementarity and facilitation over competition as the primary forms of non‐trophic interspecific interaction in soil fauna; however, competition has frequently been suggested as an important community‐structuring factor in earthworms, ecosystem engineers that influence belowground processes. To date, direct evidence of competition in earthworms is lacking due to the difficulty inherent in identifying a limiting resource for saprophagous animals. In the present study, we offer the first direct evidence of interspecific competition for food in this dominant soil detritivore group by combining field observations with laboratory mesocosm experiments using 13 C and 15 N double‐enriched leaf litter to track consumption patterns. In our experiments, the Asian invasive species Amynthas hilgendorfi was a dominant competitor for leaf litter against two European species currently invading the temperate deciduous forests in North America. This competitive advantage may account for recent invasion success of A. hilgendorfi in forests with established populations of European species, and we hypothesize that specific phenological differences play an important role in determining the outcome of the belowground competition. In contrast, Eisenoides lonnbergi , a common native species in the Eastern United States, occupied a unique trophic position with limited interactions with other species, which may contribute to its persistence in habitats dominated by invasive species. Furthermore, our results supported neither the hypothesis that facilitation occurs between species of different functional groups nor the hypothesis that species in the same group exhibit functional equivalency in C and N translocation in the soil. We propose that species identity is a more powerful approach to understand earthworm invasion and its impacts on belowground processes.

Cognition and Depression Following Deep Brain Stimulation of the Subthalamic Nucleus and Globus Pallidus Pars Internus in Parkinson’s Disease: A Meta-Analysis - Hannah L. Combs; Bradley S. Folley; David T. R. Berry; Suzanne C. Segerstrom; Dong Y. Han; Amelia J. Anderson-Mooney; Brittany D. Walls; Craig van Horne (Neuropsychology Review, 2015)

Fate and toxic effects of environmental stressors: environmental control - Jie Zhuang; Han-Qing Yu; Theodore B. Henry; Gary S. Sayler (Ecotoxicology, 2015)

Analysis and Potential Alternatives for the Disputed South China Sea from Ocean Governance in the Polar Regions - Ray Tsung-Han Tai; Nathaniel S. Pearre; Shih-Ming Kao (Coastal Management, 2015)

Fine mapping of qGW1, a major QTL for grain weight in sorghum - Lijie Han; Jun Chen; Emma S. Mace; Yishan Liu; Mengjiao Zhu; Nana Yuyama; David R. Jordan; Hongwei Cai (Theoretical and Applied Genetics, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

The Fresnel–Fizeau effect and the atmospheric time delay in geodetic VLBI - S. M. Kopeikin; W.-B. Han (Journal of Geodesy, 2015)

Identification of QTL for adult plant resistance to stripe rust in Chinese wheat landrace Caoxuan 5 - X. L. Zhou; Y. Zhang; Q. D. Zeng; X. M. Chen; D. J. Han; L. L. Huang; Z. S. Kang (Euphytica, 2015)

The Domain II S4-S5 Linker in Nav1.9: A Missense Mutation Enhances Activation, Impairs Fast Inactivation, and Produces Human Painful Neuropathy - Chongyang Han; Yang Yang; Bianca T. A. de Greef; Janneke G. J. Hoeijmakers; Monique M. Gerrits; Camiel Verhamme; Jian Qu; Giuseppe Lauria; Ingemar S. J. Merkies; Catharina G. Faber; Sulayman D. Dib-Hajj; Stephen G. Waxman (NeuroMolecular Medicine, 2015)

Purification and characterization of a novel α-glucosidase from Malbranchea cinnamomea - Q. J. Yan; P. Han; S. Q. Yang; Z. Q. Jiang (Biotechnology Letters, 2015)

A new modeling approach estimates the relative importance of different community assembly processes - Fons van der Plas; Thijs Janzen; Alejandro Ordonez; Wimke Fokkema; Josephine Reinders; Rampal S. Etienne; Han Olff (Ecology, 2015)
The relative importance of niche‐based (e.g., competitive or stress‐based) and stochastic (e.g., random dispersal) processes in structuring ecological communities is frequently analyzed by studying trait distributions of co‐occurring species. While filtering processes, such as the exclusion of stress‐intolerant species from particular habitats, increase the trait similarity between co‐occurring species, other processes, such as resource competition, can limit the similarity of co‐occurring species. Comparing the observed trait distribution patterns in communities to null expectations from randomized communities (e.g., a draw of the same observed richness from the regional pool) therefore gives a first indication of the dominant process driving community assembly. However, such comparisons do not inform us about the relative contribution of these different processes in shaping community compositions in case of their joint operation (a likely scenario). Using an Approximate Bayesian Computation approach, we develop a new method that allows inference of the relative importance of dispersal, filtering, and limiting similarity processes for the assembly of observed communities with known species and trait composition. We applied this approach to a tree community data set, collected across 20 plots along strong rainfall and fire gradients in a South African savanna. Based on comparisons with simulations, we find that our new approach is powerful in identifying which community assembly scenario has the highest probability to generate the observed trait distribution patterns, while traditional null model comparisons perform poorly in detecting signs of limiting similarity. For the studied savanna tree communities, our analysis yields that dispersal processes are most important in shaping the functional trait distribution patterns. Furthermore, our models indicate that filtering processes were relatively most important in areas with high fire frequencies, while limiting similarity processes were relatively most important in areas with low fire frequency and high rainfall. We conclude that our new method is a promising improvement on current approaches to estimate the relative importance of community assembly processes across different species groups, ecosystems, and biomes. Future model modifications (e.g., the inclusion of individual‐based processes) could provide further steps in uncovering the underlying assembly processes behind observed community patterns.

Profiling the Role of Deacylation-Reacylation in the Lymphatic Transport of a Triglyceride-Mimetic Prodrug - Sifei Han; Luojuan Hu; Tim Quach; Jamie S. Simpson; Natalie L. Trevaskis; Christopher J. H. Porter (Pharmaceutical Research, 2015)

Application of a high-surface-area schwertmannite in the removal of arsenate and arsenite - J. Song; S.-Y. Jia; H.-T. Ren; S.-H. Wu; X. Han (International Journal of Environmental Science and Technology, 2015)

Comparative Mechanisms of Protein Transduction Mediated by Cell-Penetrating Peptides in Prokaryotes - Betty Revon Liu; Yue-Wern Huang; Robert S. Aronstam; Han-Jung Lee (The Journal of Membrane Biology, 2015)

Social stress and escalated drug self-administration in mice I. Alcohol and corticosterone - Kevin J. Norman; Jacob A. Seiden; Jacob A. Klickstein; Xiao Han; Lara S. Hwa; Joseph F. DeBold; Klaus A. Miczek (Psychopharmacology, 2015)

Gastric cancer in three relatives of a patient with a biallelic IL12RB1 mutation - Ingrid P. Vogelaar; Rachel S. van der Post; Esther van de Vosse; J. Han J. M. van Krieken; Nicoline Hoogerbrugge; Marjolijn J. L. Ligtenberg; Encarna Gómez García (Familial Cancer, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

Impact of ubiquitous computing technologies on changing travel and land use patterns - S. H. Lee; Y. T. Leem; J. H. Han (International Journal of Environmental Science and Technology, 2014)

Between-subject variability: should high be the new normal? - Hesham S. Al-Sallami; Song Lim Cheah; Shiou Yii Han; Joel Liew; Jin Lim; Mary Anne Ng; Hayneil Solanki; Run Jie Soo; Victoria Tan; Stephen B. Duffull (European Journal of Clinical Pharmacology, 2014)

Gray-matter macrostructure in cognitively healthy older persons: associations with age and cognition - Debra A. Fleischman; Sue Leurgans; Konstantinos Arfanakis; Zoe Arvanitakis; Lisa L. Barnes; Patricia A. Boyle; S. Duke Han; David A. Bennett (Brain Structure and Function, 2014)

VEGF neutralization can prevent and normalize arteriovenous malformations in an animal model for hereditary hemorrhagic telangiectasia 2 - Chul Han; Se-woon Choe; Yong Hwan Kim; Abhinav P. Acharya; Benjamin G. Keselowsky; Brian S. Sorg; Young-Jae Lee; S. Paul Oh (Angiogenesis, 2014)

Enhancement of nitrogen and phosphorus removal from eutrophic water by economic plant annual ryegrass (Lolium multiflorum) with ion implantation - Miao Li; Guo-ping Sheng; Yue-jin Wu; Zeng-liang Yu; Gary S. Bañuelos; Han-qing Yu (Environmental Science and Pollution Research, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Short- and long-term response of phytoplankton to ENSO in Prydz Bay, Antarctica: Evidences from field measurements, remote sensing data and stratigraphic biomarker records - Jun Zhao; Hans-Ulrich Peter; Haisheng Zhang; Zhengbing Han; Chuanyu Hu; Peisong Yu; Bing Lu; Thomas S. Bianchi (Journal of Ocean University of China, 2014)

Synthesis of water soluble copper(II) complexes: crystal structures, DNA binding, oxidative DNA cleavage, and in vitro anticancer studies - Tan Yi Han; Teoh Siang Guan; Muhammad Adnan Iqbal; Rosenani A. Haque; K. Sharmila Rajeswari; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid (Medicinal Chemistry Research, 2014)

No fitness cost of glyphosate resistance endowed by massive EPSPS gene amplification in Amaranthus palmeri - Martin M. Vila-Aiub; Sou S. Goh; Todd A. Gaines; Heping Han; Roberto Busi; Qin Yu; Stephen B. Powles (Planta, 2014)

Cellular mechanisms in intermittent hypoxia-induced cardiac damage in vivo - Qian Han; Sze C. Yeung; Mary S. M. Ip; Judith C. W. Mak (Journal of Physiology and Biochemistry, 2014)

Optimization of sono-assisted dilute sulfuric acid process for simultaneous pretreatment and saccharification of rice straw - M. S. U. Rehman; I. Kim; K. H. Kim; J.-I. Han (International Journal of Environmental Science and Technology, 2014)

Keratinocyte growth factor and thiazolidinediones and linolenic acid differentiate characterized mammary fat pad adipose stem cells isolated from prepubertal Korean black goat to epithelial and adipogenic lineage - A. M. M. T Reza; S. Shiwani; N. K. Singh; J. D. Lohakare; S. J. Lee; D. K. Jeong; J. Y. Han; D. Rengaraj; B. W. Lee (In Vitro Cellular & Developmental Biology - Animal, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Molecular mapping of a stripe rust resistance gene in wheat cultivar Wuhan 2 - X. L. Zhou; D. J. Han; H. L. Gou; Q. L. Wang; Q. D. Zeng; F. P. Yuan; G. M. Zhan; L. L. Huang; Z. S. Kang (Euphytica, 2014)
Stripe rust (or yellow rust), caused by Puccinia striiformis f. sp. tritici , is one of the most destructive diseases of wheat worldwide. Growing resistant cultivars is the best approach to control the disease. To identify and map genes for stripe rust resistance in wheat cultivar ‘Wuhan 2', an F 2 population was developed from a cross between the cultivar and susceptible cultivar Mingxian 169. The parents, 179 F 2 plants and their derived F 2:3 lines were evaluated for responses to Chinese races CYR30 and CYR31 of the pathogen in a greenhouse. A recessive gene for resistance was identified. DNA bulked segregant analysis was applied and resistance gene analog polymorphism (RGAP) and simple sequence repeat (SSR) techniques were used to identify molecular markers linked to the resistance gene. A genetic map consisting of five RGAP and six SSR markers was constructed. The recessive gene, designated Yrwh2 , was located on the short arm of chromosome 3B and flanked by SSR markers Xwmc540 and Xgwm566 at 5.9 and 10.0 cM, respectively. The chromosomal location of the resistance gene and its close marker suggest that the locus is different from previously reported stripe rust resistance genes Yr30 , QYr.ucw - 3BS , Yrns - B1 , YrRub and QYrex.wgp - 3BL previously mapped to chromosome 3B. Yrwh2 and its closely linked markers are potentially useful for developing stripe rust resistance wheat cultivars if used in combination with other genes.

Identification of Quantitative Trait Loci (QTLs) for Fruit Quality Traits in Apple - Sarah M. Potts; M. Awais Khan; Yuepeng Han; Mosbah M. Kushad; Schuyler S. Korban (Plant Molecular Biology Reporter, 2014)

The value of multiple earthquake missions: the EEFIT L’Aquila Earthquake experience - T. Rossetto; D. D’Ayala; F. Gori; R. Persio; J. Han; V. Novelli; S. M. Wilkinson; D. Alexander; M. Hill; S. Stephens; S. Kontoe; G. Elia; et al. (Bulletin of Earthquake Engineering, 2014)

A Novel Approach to Evaluate the Pharmacokinetic Biocomparability of a Monoclonal Antibody Derived from Two Different Cell Lines Using Simultaneous Crossover Design - Chao Han; Thomas S. McIntosh; Brian J. Geist; Trina Jiao; Thomas A. Puchalski; Kenneth M. Goldberg; Tong-Yuan Yang; Charles E. Pendley; Honghui Zhou; Hugh M. Davis (The AAPS Journal, 2014)

CXCR4 pathway associated with family history of melanoma - Wen-Qing Li; Jiali Han; Hans R. Widlund; Mick Correll; Yaoyu E. Wang; John Quackenbush; Martin C. Mihm; Alvaro Laga Canales; Shaowei Wu; Todd Golub; Yujin Hoshida; David J. Hunter; et al. (Cancer Causes & Control, 2014)

Natural antisense transcripts of UL123 packaged in human cytomegalovirus virions - Cui-Qing Yang; Ling-Feng Miao; Xing Pan; Cong-Cong Wu; Simon Rayner; Edward S. Mocarski; Han-Qing Ye; Min-Hua Luo (Archives of Virology, 2014)

Applications of capillary electrophoresis for rapidly separating and characterizing water-soluble proteins of wheat grains - C. Han; Z. Yu; S. Feng; D. Lv; X. Yan; G. Chen; X. Li; W. Ma; Y. Yan (Cereal Research Communications, 2013)

The C‐terminal cysteine of turbot Scophthalmus maximus translationally controlled tumour protein plays a key role in antioxidation and growth‐promoting functions - Z.‐X. Zhang; D.‐Y. Geng; Q. Han; S.‐D. Liang; H.‐R. Guo (Journal of Fish Biology, 2013)
The translationally controlled tumour protein (TCTP) of turbot Scophthalmus maximus ( SmTCTP ) contains only one cysteine (Cys 170 ) at the C‐terminal end. The biological role of this C‐terminal Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP was examined by site‐directed mutation of C170A (Cys 170 →Ala 170 ). It was found that C170A mutation not only obviously decreased the antioxidation capacity of the mutant‐ smtctp ‐transformed bacteria exposed to 0·22 mM hydrogen peroxide, but also significantly interrupted the normal growth and survival of the mutant‐ smtctp ‐transformed bacteria and flounder Paralichthys olivaceus gill ( FG ) cells, indicating a key role played by Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP . This study also suggested that the self‐dimerization or dimerization with other interacting proteins is critical to the growth‐promoting function of SmTCTP .

More breast cancer patients prefer BRCA-mutation testing without prior face-to-face genetic counseling - Aisha S. Sie; Wendy A. G. van Zelst-Stams; Liesbeth Spruijt; Arjen R. Mensenkamp; Marjolijn J. L. Ligtenberg; Han G. Brunner; Judith B. Prins; Nicoline Hoogerbrugge (Familial Cancer, 2013)

Pathogenesis of type 1 (European genotype) porcine reproductive and respiratory syndrome virus in male gonads of infected boar - K. Han; H. W. Seo; Y. Oh; I. Kang; C. Park; J. H. Han; S.-H. Kim; C. Chae (Veterinary Research Communications, 2013)

Erratum to: Regulation of Phytohormone Biosynthesis and Accumulation in Arabidopsis Following Treatment with Commercial Extract from the Marine Macroalga Ascophyllum nodosum - Owen S. D. Wally; Alan T. Critchley; David Hiltz; James S. Craigie; Xiumei Han; L. Irina Zaharia; Suzanne R. Abrams; Balakrishnan Prithiviraj (Journal of Plant Growth Regulation, 2013)

Regulation of Phytohormone Biosynthesis and Accumulation in Arabidopsis Following Treatment with Commercial Extract from the Marine Macroalga Ascophyllum nodosum - Owen S. D. Wally; Alan T. Critchley; David Hiltz; James S. Craigie; Xiumei Han; L. Irina Zaharia; Suzanne R. Abrams; Balakrishnan Prithiviraj (Journal of Plant Growth Regulation, 2013)

Temporal variability in water quality parameters—a case study of drinking water reservoir in Florida, USA - Gurpal S. Toor; Lu Han; Craig D. Stanley (Environmental Monitoring and Assessment, 2013)

Evaluation of organic contamination in urban groundwater surrounding a municipal landfill, Zhoukou, China - D. M. Han; X. X. Tong; M. G. Jin; Emily Hepburn; C. S. Tong; X. F. Song (Environmental Monitoring and Assessment, 2013)

Artificial and enhanced humification of soil organic matter using microwave irradiation - Min Chan Kim; Han S. Kim (Environmental Science and Pollution Research, 2013)

A new caryolane sesquiterpene from Heteropappus altaicus (Willd.) Novopokr. - H. Huang; X.J. Gao; J. Liu; S. Li; Y.F. Han; B.C. Zhou; M. Xia (Natural Product Research, 2013)

Simultaneous analysis of 17 diuretics in dietary supplements by HPLC and LC-MS/MS - H. Woo; J.W. Kim; K.M. Han; J.H. Lee; I.S. Hwang; J.H. Lee; J. Kim; S.J. Kweon; S. Cho; K.R. Chae; S.Y. Han; J. Kim (Food Additives & Contaminants: Part A, 2013)

Erratum to: The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Anne Battisti-Charbonney; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; et al. (Pflügers Archiv - European Journal of Physiology, 2013)

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes - C. C. Han; J. W. Wang; Z. X. Pan; H. Tang; S. X. Xiang; J. Wang; L. Li; F. Xu; S. H. Wei (Molecular and Cellular Biochemistry, 2013)

Choice of microsatellite markers for identifying homozygosity of mitotic gynogenetic diploids in Japanese flounder Paralichthys olivaceus - Y. X. Liu; H. Z. Han; Q. L. Wang; L. Jiang; S. L. Wang; X. Y. Zhang; Y. Liu; Y. F. Wang; Y. J. Liu; H. J. Liu (Journal of Fish Biology, 2013)
A set of 72 microsatellite markers distributed evenly among 24 linkage groups were selected from the published genetic linkage maps of Japanese flounder Paralichthys olivaceus . In two normal diploid full‐sib families, the test for Mendelian inheritance showed that genotypic segregation deviations were not significant at all analysed loci. To estimate microsatellite‐centromere map distances, four meiotic gynogenetic diploid lines were produced by the activation of eggs using UV irradiated sperm of red seabream Pagrus major and cold‐shock treatment to block the extrusion of the second polar body. Under the assumption of complete interference, 21 markers were located in the centromeric region, 39 in the telomeric region and the rest in the intermediate region of linkage groups. A total of 192 mitotic gynogenetic diploids from one spawn were identified by these markers. Genotype analysis showed that the number of homozygous individuals decreased as microsatellite‐centromere map distance increased on each linkage group.

Cross‐habitat interactions among bivalve species control community structure on intertidal flats - Serena Donadi; Tjisse van der Heide; Els M. van der Zee; Johan S. Eklöf; Johan van de Koppel; Ellen J. Weerman; Theunis Piersma; Han Olff; Britas Klemens Eriksson (Ecology, 2013)
Increasing evidence shows that spatial interactions between sedentary organisms can structure communities and promote landscape complexity in many ecosystems. Here we tested the hypothesis that reef‐forming mussels ( Mytilus edulis L.), a dominant intertidal ecosystem engineer in the Wadden Sea, promote abundances of the burrowing bivalve Cerastoderma edule L. (cockle) in neighboring habitats at relatively long distances coastward from mussel beds. Field surveys within and around three mussel beds showed a peak in cockle densities at 50–100 m toward the coast from the mussel bed, while cockle abundances elsewhere in the study area were very low. Field transplantation of cockles showed higher survival of young cockles (2–3 years old) and increased spat fall coastward of the mussel bed compared to within the bed and to areas without mussels, whereas growth decreased within and coastward of the mussel bed. Our measurements suggest that the observed spatial patterns in cockle numbers resulted from (1) inhibition effects by the mussels close to the beds due to preemptive algal depletion and deteriorated sediment conditions and (2) facilitation effects by the mussels farther away from the beds due to reduction of wave energy. Our results imply that these spatial, scale‐dependent interactions between reef‐forming ecosystem engineers and surrounding communities of sedentary benthic organisms can be an important determinant of the large‐scale community structure in intertidal ecosystems. Understanding this interplay between neighboring communities of sedentary species is therefore essential for effective conservation and restoration of soft‐bottom intertidal communities.

Enhanced drought and salt tolerance by expression of AtGSK1 gene in poplar - M. S. Han; E. W. Noh; S. H. Han (Plant Biotechnology Reports, 2013)

Complex Evolutionary Relationships Among Four Classes of Modular RNA-Binding Splicing Regulators in Eukaryotes: The hnRNP, SR, ELAV-Like and CELF Proteins - Yue Hang Tang; Siew Ping Han; Karin S. Kassahn; Adam Skarshewski; Joseph A. Rothnagel; Ross Smith (Journal of Molecular Evolution, 2012)

Construction of a linkage map for quantitative trait loci associated with economically important traits in creeping bentgrass (Agrostis stolonifera L.) - Tifu Zhang; Min Ge; Xiaoqing Ye; Suleiman S. Bughrara; Han Zhao (Euphytica, 2012)

Beta amyloid, tau, neuroimaging, and cognition: sequence modeling of biomarkers for Alzheimer’s Disease - S. Duke Han; Jonathan Gruhl; Laurel Beckett; Hiroko H. Dodge; Nikki H. Stricker; Sarah Farias; Dan Mungas (Brain Imaging and Behavior, 2012)

CSF biomarker associations with change in hippocampal volume and precuneus thickness: implications for the Alzheimer’s pathological cascade - Nikki H. Stricker; Hiroko H. Dodge; N. Maritza Dowling; S. Duke Han; Elena A. Erosheva; William J. Jagust (Brain Imaging and Behavior, 2012)

Water Maze Spatial Learning Enhances Social Recognition Ability in Aged Rats - Q. Zeng; J. Han; B. Wang; Sh. An; Y. Duan; S. Dong; J. Ma; L. Yang; X. Cao (Neurophysiology, 2012)

Sequence-stratigraphic comparison of the upper Cambrian Series 3 to Furongian succession between the Shandong region, China and the Taebaek area, Korea: high variability of bounding surfaces in an epeiric platform - Jitao Chen; S. K. Chough; Jeong-Hyun Lee; Zuozhen Han (Geosciences Journal, 2012)

Massive invasion of Arctodiaptomus dorsalis (Copepoda, Calanoida, Diaptomidae) in Philippine lakes: a threat to Asian zooplankton biodiversity? - Rey Donne S. Papa; Huiming Li; Dino T. Tordesillas; Boping Han; Henri J. Dumont (Biological Invasions, 2012)

Testing the metabolic theory of ecology - Charles A. Price; Joshua S Weitz; Van M. Savage; James Stegen; Andrew Clarke; David A. Coomes; Peter S. Dodds; Rampal S. Etienne; Andrew J. Kerkhoff; Katherine McCulloh; Karl J. Niklas; Han Olff; et al. (Ecology Letters, 2012)
The metabolic theory of ecology (MTE) predicts the effects of body size and temperature on metabolism through considerations of vascular distribution networks and biochemical kinetics. MTE has also been extended to characterise processes from cellular to global levels. MTE has generated both enthusiasm and controversy across a broad range of research areas. However, most efforts that claim to validate or invalidate MTE have focused on testing predictions. We argue that critical evaluation of MTE also requires strong tests of both its theoretical foundations and simplifying assumptions. To this end, we synthesise available information and find that MTE's original derivations require additional assumptions to obtain the full scope of attendant predictions. Moreover, although some of MTE's simplifying assumptions are well supported by data, others are inconsistent with empirical tests and even more remain untested. Further, although many predictions are empirically supported on average, work remains to explain the often large variability in data. We suggest that greater effort be focused on evaluating MTE's underlying theory and simplifying assumptions to help delineate the scope of MTE, generate new theory and shed light on fundamental aspects of biological form and function.

Z-Ligustilide Potentiates the Cytotoxicity of Dopamine in Rat Dopaminergic PC12 Cells - Hongyi Qi; Jia Zhao; Yifan Han; Allan S. Y. Lau; Jianhui Rong (Neurotoxicity Research, 2012)

The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; Joseph A. Fisher; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Non-steroidal anti-inflammatory drugs, acetaminophen, and risk of skin cancer in the Nurses’ Health Study - J. M. Jeter; J. Han; M. E. Martinez; D. S. Alberts; A. A. Qureshi; D. Feskanich (Cancer Causes & Control, 2012)

Desulfohalophilus alkaliarsenatis gen. nov., sp. nov., an extremely halophilic sulfate- and arsenate-respiring bacterium from Searles Lake, California - Jodi Switzer Blum; Thomas R. Kulp; Sukkyun Han; Brian Lanoil; Chad W. Saltikov; John F. Stolz; Laurence G. Miller; Ronald S. Oremland (Extremophiles, 2012)

Insects perceive local sex ratio in the absence of tactile or visual sex-specific cues - Chang S. Han; Chang-Ku Kang; Hong-Sup Shin; Jeong-Hyun Lee; Mi-Rye Bae; Sang-Im Lee; Piotr G. Jablonski (Behavioral Ecology and Sociobiology, 2012)

Genetic Diversity and Characterization of a Core Collection of Malus Germplasm Using Simple Sequence Repeats (SSRs) - Sarah M. Potts; Yuepeng Han; M. Awais Khan; Mosbah M. Kushad; A. Lane Rayburn; Schuyler S. Korban (Plant Molecular Biology Reporter, 2012)

Adsorption of bisphenol A on lignin: effects of solution chemistry - W. Han; L. Luo; S. Zhang (International Journal of Environmental Science and Technology, 2012)

Evaluation of Genetic Diversity in Chinese Wild Apple Species Along with Apple Cultivars Using SSR Markers - Qiong Zhang; Jing Li; Yongbo Zhao; Schuyler S. Korban; Yuepeng Han (Plant Molecular Biology Reporter, 2012)

Increased Expression of Alpha-Synuclein by SNCA Duplication is Associated with Resistance to Toxic Stimuli - Han-Joon Kim; Beom S. Jeon; Min-Yung Yoon; Sung-Sup Park; Kwang-Woo Lee (Journal of Molecular Neuroscience, 2012)

177Lu–DO3A–HSA–ZEGFR:1907: characterization as a potential radiopharmaceutical for radionuclide therapy of EGFR-expressing head and neck carcinomas - Susan Hoppmann; Shibo Qi; Zheng Miao; Hongguang Liu; Han Jiang; Cathy S. Cutler; Ande Bao; Zhen Cheng (JBIC Journal of Biological Inorganic Chemistry, 2012)

Spatially Extended Habitat Modification by Intertidal Reef-Building Bivalves has Implications for Consumer-Resource Interactions - Els M. van der Zee; Tjisse van der Heide; Serena Donadi; Johan S. Eklöf; Britas Klemens Eriksson; Han Olff; Henk W. van der Veer; Theunis Piersma (Ecosystems, 2012)

Comparative changes in density and demography of large herbivores in the Masai Mara Reserve and its surrounding human-dominated pastoral ranches in Kenya - Nina Bhola; Joseph O. Ogutu; Hans-Peter Piepho; Mohamed Y. Said; Robin S. Reid; N. Thompson Hobbs; Han Olff (Biodiversity and Conservation, 2012)

Isolation and Characterization of a Lytic Myoviridae Bacteriophage PAS-1 with Broad Infectivity in Aeromonas salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; D. H. Kang; C. Oh; S. J. Heo; S. C. Park (Current Microbiology, 2012)

Behavioral, Ecological, and Evolutionary Aspects of Meat-Eating by Sumatran Orangutans (Pongo abelii) - Madeleine E. Hardus; Adriano R. Lameira; Astri Zulfa; S. Suci Utami Atmoko; Han de Vries; Serge A. Wich (International Journal of Primatology, 2012)

An intronic MYLK variant associated with inflammatory lung disease regulates promoter activity of the smooth muscle myosin light chain kinase isoform - Yoo Jeong Han; Shwu-Fan Ma; Michael S. Wade; Carlos Flores; Joe G. N. Garcia (Journal of Molecular Medicine, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Application of tyramide signal amplification‐fluorescence in situ hybridisation and flow cytometry to detection of Heterosigma akashiwo (Raphidophyceae) in natural waters - J Lee; T Katano; M Chang; M‐S Han (New Zealand Journal of Marine and Freshwater Research, 2012)
We developed protocols to analyse the cell cycle of Heterosigma akashiwo in the natural phytoplankton assemblage using tyramide signal amplification‐fluorescence in situ hybridisation (TSA‐FISH) and flow cytometry. We determined the optimum probe and formamide concentrations for the species‐specific TSA‐FISH probe to be 0.5 ng µL −1 and 40%, respectively. The probe did not hybridise to non‐target phytoplankton including Chattonella sp., which is closely related to Heterosigma and has high sequence similarity to it. We could successfully identify G1‐ and G2‐phase cells and the diel cell cycle of H. akashiwo not only in the laboratory but also in the field after TSA‐FISH. These results demonstrate that TSA‐FISH for H. akashiwo in natural coastal waters could serve as a powerful tool for understanding their bloom mechanism using flow cytometry.

Starvation reduces the heat shock protein responses in white sturgeon larvae - Dong Han; Susie S. Y. Huang; Wei-Fang Wang; Dong-Fang Deng; Silas S. O. Hung (Environmental Biology of Fishes, 2012)

Complete genomic sequence of a T4-like bacteriophage, phiAS4, infecting Aeromonas salmonicida subsp. salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Genomic sequence of infectious hypodermal and hematopoietic necrosis virus (IHHNV) KLV-2010-01 originating from the first Korean outbreak in cultured Litopenaeus vannamei - J. H. Kim; H. K. Kim; V. G. Nguyen; B. K. Park; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Prevalence and different characteristics of two serotypes of Streptococcus parauberis isolated from the farmed olive flounder, Paralichthys olivaceus (Temminck and Schlegel), in Korea - S Y Han; B K Kang; B J Kang; S P Shin; B H Soen; J M Kim; J H Kim; C H Choresca; J E Han; J W Jun; S C Park (Journal of Fish Diseases, 2011)
The prevalence of two serotypes of Streptococcus parauberis isolated from the olive flounder, Paralichthys olivaceus , was evaluated in a total of 29 isolates between 2003 and 2010 in Korea. Streptococcus parauberis isolates were divided into two serologically distinct types (serotype 1 and serotype 2), except for one strain (S1091), using an agglutination assay with rabbit antiserum, and serotype 1 was identified as the dominant type (24 of 29 isolates) in this study. To identify the characteristics of the two serotypes of S. parauberis , we conducted a biochemical test using the API 20 Strep kit, a transmission electron microscopy (TEM) assay, sequence analysis of 16S‐23S rRNA intergenic spacer region (ISR) and a pathogenicity test. In TEM, both serotypes possessed polysaccharide capsule layers around the cell surface when bacterial cells were treated with a homologous serotype of rabbit antiserum. However, we were unable to discriminate serotype‐specific biochemical characteristics and genetic characteristics of 16S‐23S rRNA ISR between the two serotypes. In the pathogenicity test, the serotype 1 strains induced significantly higher mortality than the serotype 2 strains in olive flounder when experimentally inoculated via the intraperitoneal route.

Individual and combined effects of multiple pathogens on Pacific treefrogs - John M. Romansic; Pieter T. J. Johnson; Catherine L. Searle; James E. Johnson; Tate S. Tunstall; Barbara A. Han; Jason R. Rohr; Andrew R. Blaustein (Oecologia, 2011)

Severe anisakiasis and cutaneous myxoma in a California yellowtail, Seriola lalandi Valenciennes - M Keller; S Han; K Snekvik (Journal of Fish Diseases, 2011)

Orchestrating T-cell receptor α gene assembly through changes in chromatin structure and organization - Han-Yu Shih; Bingtao Hao; Michael S. Krangel (Immunologic Research, 2011)

Atypical Aeromonas salmonicida infection in the black rockfish, Sebastes schlegeli Hilgendorf , in Korea - H‐J Han; D‐Y Kim; W‐S Kim; C‐S Kim; S‐J Jung; M‐J Oh; D‐H Kim (Journal of Fish Diseases, 2011)
Cultured black rockfish, Sebastes schlegeli , suffered mass mortalities during winter 2008 and spring 2009 in Korea, showing clinical signs of ulcer lesions and haemorrhages over their body surface. The aetiological agent was identified as Aeromonas salmonicida (strains RFAS‐1, ‐2 and ‐3), which is a non‐pigmented, slow‐growing bacterium. Phenotypes of RFAS strains showed variation, while 16S rRNA, gyrB , rpoD , dnaJ and recA gene sequences of all the strains were affiliated to A. salmonicida. In particular, vapA gene sequences of the strains were most closely related to one of the five subspecies of A. salmonicida subsp. masoucida (=KCCM 40239 T ). LD 50 values of RFAS‐1 for intraperitoneal and intramuscular injection were 1.5 × 10 5.25 and 1.5 × 10 6.4 cfu/rockfish, respectively. However, A. salmonicida strains KCCM 40239 T and SAS‐1, which originate from masou and chum salmon, respectively, were not pathogenic to black rockfish. RFAS strains, possessing A‐layer protein on their surface, exhibited β‐haemolytic activity against rockfish erythrocytes and capability to survive in rockfish serum, which seem to be associated with virulence.

A Matched Asymptotic Expansion Analysis of Highly Unsteady Porous Media Flows - S. Y. Han; D. Hansen; G. C. Kember (Transport in Porous Media, 2010)

Nicotinic acetylcholine receptor genes on chromosome 15q25.1 are associated with nicotine and opioid dependence severity - Porat M. Erlich; Stuart N. Hoffman; Margaret Rukstalis; John J. Han; Xin Chu; W. H. Linda Kao; Glenn S. Gerhard; Walter F. Stewart; Joseph A. Boscarino (Human Genetics, 2010)

Microfluidics for cell separation - Ali Asgar S. Bhagat; Hansen Bow; Han Wei Hou; Swee Jin Tan; Jongyoon Han; Chwee Teck Lim (Medical & Biological Engineering & Computing, 2010)

The genome of the Gram‐positive metal‐ and sulfate‐reducing bacterium Desulfotomaculum reducens strain MI‐1 - Pilar Junier; Thomas Junier; Sheila Podell; David R. Sims; John C. Detter; Athanasios Lykidis; Cliff S. Han; Nicholas S. Wigginton; Terry Gaasterland; Rizlan Bernier‐Latmani (Environmental Microbiology, 2010)
Summary Spore‐forming, Gram‐positive sulfate‐reducing bacteria (SRB) represent a group of SRB that dominates the deep subsurface as well as niches in which resistance to oxygen and dessication is an advantage. Desulfotomaculum reducens strain MI‐1 is one of the few cultured representatives of that group with a complete genome sequence available. The metabolic versatility of this organism is reflected in the presence of genes encoding for the oxidation of various electron donors, including three‐ and four‐carbon fatty acids and alcohols. Synteny in genes involved in sulfate reduction across all four sequenced Gram‐positive SRB suggests a distinct sulfate‐reduction mechanism for this group of bacteria. Based on the genomic information obtained for sulfate reduction in D. reducens , the transfer of electrons to the sulfite and APS reductases is proposed to take place via the quinone pool and heterodisulfide reductases respectively. In addition, both H 2 ‐evolving and H 2 ‐consuming cytoplasmic hydrogenases were identified in the genome, pointing to potential cytoplasmic H 2 cycling in the bacterium. The mechanism of metal reduction remains unknown.

Sensitivity of MEG and EEG to Source Orientation - Seppo P. Ahlfors; Jooman Han; John W. Belliveau; Matti S. Hämäläinen (Brain Topography, 2010)

Evaluation of Ocean Tide Models Used for Jason-2 Altimetry Corrections - H. S. Fok; H. Baki Iz; C. K. Shum; Yuchan Yi; Ole Andersen; Alexander Braun; Yi Chao; Guoqi Han; C. Y. Kuo; Koji Matsumoto; Y. Tony Song (Marine Geodesy, 2010)

Does larval duration contribute to population genetic isolation of the Japanese eel Anguilla japonica ? - Y. S. HAN; C. L. HUNG; Y. IIZUKA; H. C. CHANG; B. J. CHANG; H. C. HO; J. C. SHIAO (Fisheries Management and Ecology, 2010)

Human Enteric Viruses in Groundwater - S. H. Park; E. J. Kim; T. H. Yun; J. H. Lee; C. K. Kim; Y. H. Seo; S. A. Oh; S. S. Choi; S. J. Cho; M. S. Kim; G. Y. Han; M. Y. Kim; et al. (Food and Environmental Virology, 2010)

Role of body size in dominance interactions between male water striders, Aquarius paludum - Chang S. Han; Piotr G. Jablonski (Journal of Ethology, 2010)

Population structure of the olive flounder ( Paralichthys olivaceus ) in Korea inferred from microsatellite marker analysis - W.‐J. Kim; K.‐K. Kim; H.‐S. Han; B.‐H. Nam; Y.‐O. Kim; H.‐J. Kong; J.‐K. Noh; M. Yoon (Journal of Fish Biology, 2010)
The population structure of olive flounder Paralichthys olivaceus was estimated using nine polymorphic microsatellite (MS) loci in 459 individuals collected from eight populations, including five wild and three hatchery populations in Korea. Genetic variation in hatchery (mean number of alleles per locus, A = 10·2–12·1; allelic richness, A R = 9·3–10·1; observed heterozygosity, H O = 0·766–0·805) and wild (mean number of alleles per locus, A = 11·8–19·6; allelic richness, A R = 10·9–16·1; observed heterozygosity, H O = 0·820–0·888) samples did not differ significantly, suggesting a sufficient level of genetic variation in these well‐managed hatchery populations, which have not lost a substantial amount of genetic diversity. Neighbour‐joining tree and principal component analyses showed that genetic separation between eastern and pooled western and southern wild populations in Korea was probably influenced by restricted gene flow between regional populations due to the barrier effects of sea currents. The pooled western and southern populations are genetically close, perhaps because larval dispersal may depend on warm currents. One wild population (sample from Wando) was genetically divergent from the main distribution, but it was genetically close to hatchery populations, indicating that the genetic composition of the studied populations may be affected by hydrographic conditions and the release of fish stocks. The estimated genetic population structure and potential applications of MS markers may aid in the proper management of P. olivaceus populations.

Toxicoproteomic analysis of phalloidin-induced cholestasis in mouse liver - Sun Hee Heo; Jung-Hwa Oh; Han-Jin Park; Myung-Sang Kwon; Suresh V. S. Rana; Seokjoo Yoon (Molecular & Cellular Toxicology, 2010)

Characterization of chikusaku-eki and mokusaku-eki and its inhibitory effect on sapstaining fungal growth in laboratory scale - N. Velmurugan; S. S. Chun; S. S. Han; Y. S. Lee (International Journal of Environmental Science and Technology, 2009)

Estimated PBDE and PBB Congeners in Soil from an Electronics Waste Disposal Site - H.-M. Wang; Y.-J. Yu; M. Han; S.-W. Yang; Q. li; Y. Yang (Bulletin of Environmental Contamination and Toxicology, 2009)

Molecular characterization of hepatitis A virus isolated from acute gastroenteritis patients in the Seoul region of Korea - S.-H. Park; E.-J. Kim; J.-H. Lee; S.-S. Choi; M.-S. Kim; S.-S. Jung; G.-Y. Han; H.-S. Yun; D.-S. Chun; S.-S. Oh; H.-S. Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

Improved Sugar Conversion and Ethanol Yield for Forage Sorghum (Sorghum bicolor L. Moench) Lines with Reduced Lignin Contents - Bruce S. Dien; Gautam Sarath; Jeffrey F. Pedersen; Scott E. Sattler; Han Chen; Deanna L. Funnell-Harris; Nancy N. Nichols; Michael A. Cotta (BioEnergy Research, 2009)

Genetic relationships between preharvest sprouting and dormancy in barley - S. E. Ullrich; H. Lee; J. A. Clancy; I. A. del Blanco; V. A. Jitkov; A. Kleinhofs; F. Han; D. Prada; I. Romagosa; J. L. Molina-Cano (Euphytica, 2009)

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Monitoring large herbivore diversity at different scales: comparing direct and indirect methods - Joris P. G. M. Cromsigt; Susan J. van Rensburg; Rampal S. Etienne; Han Olff (Biodiversity and Conservation, 2009)

Identification of a novel chimeric gene, orf725, and its use in development of a molecular marker for distinguishing among three cytoplasm types in onion (Allium cepa L.) - Sunggil Kim; Eul-Tai Lee; Dong Youn Cho; Taeho Han; Haejeen Bang; Bhimanagouda S. Patil; Yul Kyun Ahn; Moo-Kyoung Yoon (Theoretical and Applied Genetics, 2009)

Estimation of the gross primary production of an old‐growth temperate mixed forest using eddy covariance and remote sensing - J. B. Wu; X. M. Xiao; D. X. Guan; T. T. Shi; C. J. Jin; S. J. Han (International Journal of Remote Sensing, 2009)

Resistance to race 2 and cross-resistance to race 1 of Kabatiella caulivora in Trifolium subterraneum and T. purpureum - Hua Li; P. G. H. Nichols; S. Han; K. J. Foster; K. Sivasithamparam; M. J. Barbetti (Australasian Plant Pathology, 2009)

Neural network determination of cloud attenuation to estimate insolation using MTSAT‐1R data - J.‐M. Yeom; K.‐S. Han; Y.‐S. Kim; J.‐D. Jang (International Journal of Remote Sensing, 2008)

The complete genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ) - Elizabeth Pierce; Gary Xie; Ravi D. Barabote; Elizabeth Saunders; Cliff S. Han; John C. Detter; Paul Richardson; Thomas S. Brettin; Amaresh Das; Lars G. Ljungdahl; Stephen W. Ragsdale (Environmental Microbiology, 2008)
Summary This paper describes the genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ), which is the model acetogenic bacterium that has been widely used for elucidating the Wood–Ljungdahl pathway of CO and CO 2 fixation. This pathway, which is also known as the reductive acetyl‐CoA pathway, allows acetogenic (often called homoacetogenic) bacteria to convert glucose stoichiometrically into 3 mol of acetate and to grow autotrophically using H 2 and CO as electron donors and CO 2 as an electron acceptor. Methanogenic archaea use this pathway in reverse to grow by converting acetate into methane and CO 2 . Acetogenic bacteria also couple the Wood–Ljungdahl pathway to a variety of other pathways to allow the metabolism of a wide variety of carbon sources and electron donors (sugars, carboxylic acids, alcohols and aromatic compounds) and electron acceptors (CO 2 , nitrate, nitrite, thiosulfate, dimethylsulfoxide and aromatic carboxyl groups). The genome consists of a single circular 2 628 784 bp chromosome encoding 2615 open reading frames (ORFs), which includes 2523 predicted protein‐encoding genes. Of these, 1834 genes (70.13%) have been assigned tentative functions, 665 (25.43%) matched genes of unknown function, and the remaining 24 (0.92%) had no database match. A total of 2384 (91.17%) of the ORFs in the M. thermoacetica genome can be grouped in orthologue clusters. This first genome sequence of an acetogenic bacterium provides important information related to how acetogens engage their extreme metabolic diversity by switching among different carbon substrates and electron donors/acceptors and how they conserve energy by anaerobic respiration. Our genome analysis indicates that the key genetic trait for homoacetogenesis is the core acs gene cluster of the Wood–Ljungdahl pathway.

An overview of the apple genome through BAC end sequence analysis - Yuepeng Han; Schuyler S. Korban (Plant Molecular Biology, 2008)

Suggestion of Potential Stent Design Parameters to Reduce Restenosis Risk driven by Foreshortening or Dogboning due to Non-uniform Balloon-Stent Expansion - Dohyung Lim; Seung-Kwan Cho; Won-Pil Park; Anders Kristensson; Jai-Young Ko; S. T. S. Al-Hassani; Han-Sung Kim (Annals of Biomedical Engineering, 2008)

Isolation and characterization of cold-regulated transcriptional activator LpCBF3 gene from perennial ryegrass (Lolium perenne L.) - Han Zhao; Suleiman S. Bughrara (Molecular Genetics and Genomics, 2008)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Control and possible applications of a novel carrot-spoilage basidiomycete, Fibulorhizoctonia psychrophila - Ronald P. de Vries; Elvira S. de Lange; Han A. B. Wösten; Joost A. Stalpers (Antonie van Leeuwenhoek, 2008)

Enhanced Mobilization of Field Contaminated Soil-bound PAHs to the Aqueous Phase under Anaerobic Conditions - Han S. Kim; Katherine S. Lindsay; Frederic K. Pfaender (Water, Air, & Soil Pollution, 2008)

Changes in Chlorophyll Fluorescence in Maize Plants with Imposed Rapid Dehydration at Different Leaf Ages - Z. Z. Xu; G. S. Zhou; Y. L. Wang; G. X. Han; Y. J. Li (Journal of Plant Growth Regulation, 2008)

Use of bioluminescent imaging to investigate the role of nuclear factor-κΒ in experimental non-small cell lung cancer metastasis - Georgios T. Stathopoulos; Taylor P. Sherrill; Wei Han; Ruxana T. Sadikot; Vasiliy V. Polosukhin; Barbara Fingleton; Fiona E. Yull; Timothy S. Blackwell (Clinical & Experimental Metastasis, 2008)

Characterization of a Homogentisate Dioxygenase Mutant in Pseudomonas chlororaphis O6 - B. R. Kang; S. H. Han; S. M. Cho; A. J. Anderson; I. S. Kim; S. K. Park; Y. C. Kim (Current Microbiology, 2008)

Characteristics of reactive nitrogen compounds and other relevant trace gases in the atmosphere at urban and rural areas of Korea during May–June, 2004 - Z.-H. Shon; G. Lee; S.-K. Song; M. Lee; J. Han; D. Lee (Journal of Atmospheric Chemistry, 2007)

A novel gene, Pi40(t), linked to the DNA markers derived from NBS-LRR motifs confers broad spectrum of blast resistance in rice - J. U. Jeung; B. R. Kim; Y. C. Cho; S. S. Han; H. P. Moon; Y. T. Lee; K. K. Jena (Theoretical and Applied Genetics, 2007)

Monitoring of Aerial Pollutants Emitted from Swine Houses in Korea - Ki Y. Kim; Han J. Ko; Hyeon T. Kim; Yoon S. Kim; Young M. Roh; Cheol M. Lee; Chi N. Kim (Environmental Monitoring and Assessment, 2007)

Changes of chemical and nutrient composition of porcine blood during fermentation by Aspergillus oryzae - J. Z. Wang; M. Zhang; F. Z. Ren; B. Z. Han; L. Wang; S. W. Chen; A. Humera (World Journal of Microbiology and Biotechnology, 2007)

Genomic isolation of genes encoding starch branching enzyme II (SBEII) in apple: toward characterization of evolutionary disparity in SbeII genes between monocots and eudicots - Yuepeng Han; Elise Bendik; Feng-Jie Sun; Ksenija Gasic; Schuyler S. Korban (Planta, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cytology and pollen grain fertility in creeping bentgrass interspecific and intergeneric hybrids - Han Zhao; Suleiman S. Bughrara; Yuexia Wang (Euphytica, 2007)

Spectral reflectance and leaf internal structure changes of barley plants due to phytoextraction of zinc and cadmium - B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Monitoring the effects of arsenic and chromium accumulation in Chinese brake fern ( Pteris vittata ) - Maruthi B. B. Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Making carbon sequestration a paying proposition - Fengxiang X. Han; Jeff S. Lindner; Chuji Wang (The Science of Nature, 2007)

Effect of Bioaccumulation of Cs and Sr Natural Isotopes on Foliar Structure and Plant Spectral Reflectance of Indian Mustard (Brassica Juncea) - Yi Su; B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts (Water, Air, & Soil Pollution, 2007)

Atmospheric Cu and Pb Deposition and Transport in Lake Sediments in a Remote Mountain Area, Northern China - Yongming Han; Zhangdong Jin; Junji Cao; Eric S. Posmentier; Zhisheng An (Water, Air, & Soil Pollution, 2007)

Removal of Alachlor and Pretilachlor by Laboratory-Synthesized Zerovalent Iron in Pesticide Formulation Solution - H. Y. Kim; I. K. Kim; J. H. Shim; Y.-C. Kim; T.-H. Han; K.-C. Chung; P. I. Kim; B.-T. Oh; I. S. Kim (Bulletin of Environmental Contamination and Toxicology, 2006)

Soil Nitrification and Denitrification Potentials in a Wheat Field Soil as Affected by Elevated Atmospheric CO2 and Rice Straw Incorporation - Y. Shi; S. Y. Wang; L. Han; J. Yue; L. X. Yang; Y. L. Wang; J. G. Zhu (Bulletin of Environmental Contamination and Toxicology, 2006)

Pathogenicity of Edwardsiella tarda to olive flounder, Paralichthys olivaceus (Temminck & Schlegel) - H‐J Han; D‐H Kim; D‐C Lee; S‐M Kim; S‐I Park (Journal of Fish Diseases, 2006)
The LD 50 and cytotoxic and enzymatic activities of both cells and extracellular products (ECPs) of eight Edwardsiella tarda strains were determined and their bacterial superoxide dismutase gene (sodB) and catalase gene (katB) were sequenced. Strains were also examined for their ability to resist the immune responses of olive flounder, Paralichthys olivaceus . LD 50 values of strains (FSW910410, KE1, 2, 3, 4, 5 and 6) in olive flounder ranged between 10 2.5 and 10 5.3 cfu (colony forming units) per fish. Unlike the avirulent strain SU100 (LD 50 ≥ 10 7 ), all pathogenic strains were able to survive in flounder serum and head kidney leucocytes (except for KE2). The virulent strains possessed type I sodB and katB, whereas SU100 had type II sodB but not katB. However, there was no difference between avirulent and virulent strains in haemolytic and cytotoxic activities. The results of this study demonstrated that the ability of E. tarda to resist complement activity and phagocytosis is conferred by its superoxide dismutase and catalase, which thus play an essential role in the pathogenicity of this bacterium. In addition genotyping of sodB and kat B proved to be a very useful tool to distinguish virulent from avirulent strains.

Coordination between manganese and nitrogen within the ligands in the manganese complexes facilitates the reconstitution of the water-oxidizing complex in manganese-depleted photosystem II preparations - Shuqin Li; Guiying Chen; Guangye Han; Lin Ling; Deguang Huang; A. A. Khorobrykh; S. K. Zharmukhamedov; Qiutian Liu; V. V. Klimov; Tingyun Kuang (JBIC Journal of Biological Inorganic Chemistry, 2006)

Herbivore impact on grassland plant diversity depends on habitat productivity and herbivore size - Elisabeth S. Bakker; Mark E. Ritchie; Han Olff; Daniel G. Milchunas; Johannes M. H. Knops (Ecology Letters, 2006)
Mammalian herbivores can have pronounced effects on plant diversity but are currently declining in many productive ecosystems through direct extirpation, habitat loss and fragmentation, while being simultaneously introduced as livestock in other, often unproductive, ecosystems that lacked such species during recent evolutionary times. The biodiversity consequences of these changes are still poorly understood. We experimentally separated the effects of primary productivity and herbivores of different body size on plant species richness across a 10‐fold productivity gradient using a 7‐year field experiment at seven grassland sites in North America and Europe. We show that assemblages including large herbivores increased plant diversity at higher productivity but decreased diversity at low productivity, while small herbivores did not have consistent effects along the productivity gradient. The recognition of these large‐scale, cross‐site patterns in herbivore effects is important for the development of appropriate biodiversity conservation strategies.

Genetic diversity of avian infectious bronchitis coronavirus strains isolated in China between 1995 and 2004 - S. W. Liu; Q. X. Zhang; J. D. Chen; Z. X. Han; X. Liu; L. Feng; Y. H. Shao; J. G. Rong; X. G. Kong; G. Z. Tong (Archives of Virology, 2006)

Bile salt hydrolase and cholesterol removal effect by Bifidobacterium bifidum NRRL 1976 - S. Parvez; Hong-Yeoul Kim; Han-Chang Lee; Dae-Sun Kim (World Journal of Microbiology and Biotechnology, 2006)

Leaching of Copper from an Industrial Sludge Applied on a Soil Column - J. Xu; S. Dai; X. Han; S. Sun; P. Zhang (Bulletin of Environmental Contamination and Toxicology, 2006)

N-acetylphytosphingosine-induced apoptosis of Jurkat cells is mediated by the conformational change in Bak - Y. Han; Y. Kim; H. Kang; S. H. Hong; Y. H. Kim; D. -S. Lim; C. Park; Y. -S. Yun; J. -Y. Song (Apoptosis, 2006)

Pioglitazone, a synthetic ligand for PPARγ, induces apoptosis in RB-deficient human colorectal cancer cells - C. J. Lee; J. S. Han; C. Y. Seo; T. H. Park; H. C. Kwon; J. S. Jeong; I. H. Kim; J. Yun; Y. S. Bae; J. Y. Kwak; J. I. Park (Apoptosis, 2006)

Advances in the Use of Tocols as Drug Delivery Vehicles - Panayiotis P. Constantinides; Jihong Han; Stanley S. Davis (Pharmaceutical Research, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

Delineating the northern part of the Socotra Basin, offshore Korea, using marine magnetics - M. Suh; T. F. Abdallatif; J. Han; S. Choi; J. Oh (Geo-Marine Letters, 2005)

Meprin β metalloprotease gene polymorphisms associated with diabetic nephropathy in the Pima Indians - Alexander R. Red Eagle; Robert L. Hanson; Weiping Jiang; Xiaoli Han; Gail L. Matters; Giuseppina Imperatore; William C. Knowler; Judith S. Bond (Human Genetics, 2005)

Leaching Behavior of Copper (II) in a Soil Column Experiment - J. Xu; X. Han; S. Sun; F. Meng; S. Dai (Bulletin of Environmental Contamination and Toxicology, 2005)

The influence of muscle type and dystrophin deficiency on murine expression profiles - Judith N. Haslett; Peter B. Kang; Mei Han; Alvin T. Kho; Despina Sanoudou; Jay M. Volinski; Alan H. Beggs; Isaac S. Kohane; Louis M. Kunkel (Mammalian Genome, 2005)

The Oryza Map Alignment Project: The Golden Path to Unlocking the Genetic Potential of Wild Rice Species - Rod A. Wing; Jetty S. S. Ammiraju; Meizhong Luo; HyeRan Kim; Yeisoo Yu; Dave Kudrna; Jose L. Goicoechea; Wenming Wang; Will Nelson; Kiran Rao; Darshan Brar; Dave J. Mackill; et al. (Plant Molecular Biology, 2005)

Seasonal Variation of Chemical Composition in Fine Particles at Gosan, Korea - J. S. Han; K. J. Moon; B. J. Kong; S. J. Lee; J. E. Kim; Y. J. Kim (Environmental Monitoring and Assessment, 2005)

Interactions of mechanical stimuli and sex pheromone information in antennal lobe neurons of a male moth, Spodoptera littoralis - Qian Han; Bill S. Hansson; Sylvia Anton (Journal of Comparative Physiology A, 2005)

Confronting different models of community structure to species‐abundance data: a Bayesian model comparison - Rampal S. Etienne; Han Olff (Ecology Letters, 2005)
Species abundances are undoubtedly the most widely available macroecological data, but can we use them to distinguish among several models of community structure? Here we present a Bayesian analysis of species‐abundance data that yields a full joint probability distribution of each model's parameters plus a relatively parameter‐independent criterion, the posterior Bayes factor, to compare these models. We illustrate our approach by comparing three classical distributions: the zero‐sum multinomial (ZSM) distribution, based on Hubbell's neutral model, the multivariate Poisson lognormal distribution (MPLN), based on niche arguments, and the discrete broken stick (DBS) distribution, based on MacArthur's broken stick model. We give explicit formulas for the probability of observing a particular species‐abundance data set in each model, and argue that conditioning on both sample size and species count is needed to allow comparisons between the two distributions. We apply our approach to two neotropical communities (trees, fish). We find that DBS is largely inferior to ZSM and MPLN for both communities. The tree data do not allow discrimination between ZSM and MPLN, but for the fish data ZSM (neutral model) overwhelmingly outperforms MPLN (niche model), suggesting that dispersal plays a previously underestimated role in structuring tropical freshwater fish communities. We advocate this approach for identifying the relative importance of dispersal and niche‐partitioning in determining diversity of different ecological groups of species under different environmental conditions.

Phosphorus characteristics correlate with soil fertility of albic luvisols - X. Z. Han; C. Tang; C. Y. Song; S. Y. Wang; Y. F. Qiao (Plant and Soil, 2005)

Agrobacterium-mediated transformation of bottle gourd (Lagenaria siceraria Standl.) - J.-S. Han; C. K. Kim; S. H. Park; K. D. Hirschi; I.- G. Mok (Plant Cell Reports, 2005)

Effects of Acid Precipitation and Aluminum on Carbohydrate Metabolism in Mycorrhizae of Pinus massioniana - J. K. Tan; F. X. Kong; H. S. Cao; Y. Yu; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2005)

Time Course Biochemical Responses of Green Algae Scenedesmus obliquus to Aluminum and Low pH - S. A. Jusu; F. X. Kong; B. Q. Qing; J. K. Tan; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Efficient plant regeneration from cotyledon explants of bottle gourd (Lagenaria siceraria Standl.) - J-S. Han; D-G. Oh; I-G. Mok; H-G. Park; C. K. Kim (Plant Cell Reports, 2004)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Nonylphenol Induced Apoptosis in Rat Testis Through the Fas/FasL Pathway - X. Han; Z. Tu; X. Wang; S. Shen; Y. Hou (Bulletin of Environmental Contamination and Toxicology, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Design and Evaluation of an Emulsion Vehicle for Paclitaxel. I. Physicochemical Properties and Plasma Stability - Jihong Han; Stanley S. Davis; Catherine Papandreou; Colin D. Melia; Clive Washington (Pharmaceutical Research, 2004)

Experimental investigation of the mammary gland tumour phantom for multifrequency microwave radio-thermometers - J. W. Lee; S. M. Lee; K. S. Kim; W. T. Han; G. Yoon; L. A. Pasmanik; I. A. Ulyanichev; A. V. Troitsky (Medical & Biological Engineering & Computing, 2004)

Bacterial enteritis and the development of the larval digestive tract in olive flounder, Paralichthys olivaceus (Temminck & Schlegel) - D‐H Kim; H‐J Han; S‐M Kim; D‐C Lee; S‐I Park (Journal of Fish Diseases, 2004)
Three bacterial isolates obtained from diseased olive flounder larvae, Paralichthys olivaceus , were identified as Vibrio ichthyoenteri based on the results of phenotypic characterization and 16S rRNA gene sequencing studies. Bacterial enteritis was reproduced in 16 and 22 days post‐hatch (dph) larvae by administering brine shrimp nauplii, Artemia salina , dosed with the environmental isolates and reference strains of V. ichthyoenteri . To investigate the effect of the disease on development of the stomach, a pepsin activity assay and reverse transcription‐polymerase chain reaction (RT‐PCR) analysis of the expression of the pepsinogen gene were performed. Expression of olive flounder pepsinogen was detected from 30‐dph larvae and the increased level of pepsin activity coincided with reduced susceptibility to the disease. Growth rates of V. ichthyoenteri , V. anguillarum and Edwardsiella tarda were tested in artificial stomach conditions using HCl and porcine pepsin. All the strains of V. ichthyoenteri were inhibited by low pH conditions which corresponded with an increase in pepsin levels. This suggests that differentiation of the stomach in olive flounder larvae and juveniles, an essential physiological development, also provides the host with a non‐immunological defence mechanism.

Fine mapping of a malting-quality QTL complex near the chromosome 4H S telomere in barley - W. Gao; J. A. Clancy; F. Han; B. L. Jones; A. Budde; D. M. Wesenberg; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2004)

Activation of a rice endogenous retrotransposon Tos17 in tissue culture is accompanied by cytosine demethylation and causes heritable alteration in methylation pattern of flanking genomic regions - Z. L. Liu; F. P. Han; M. Tan; X. H. Shan; Y. Z. Dong; X. Z. Wang; G. Fedak; S. Hao; Bao Liu (Theoretical and Applied Genetics, 2004)

Genotyping Possible Polymorphic Variants of Human Mismatch Repair Genes in Healthy Korean Individuals and Sporadic Colorectal Cancer Patients - Jin C. Kim; Seon A. Roh; Kum H. Koo; In H. Ka; Hee C. Kim; Chang S. Yu; Kang H. Lee; Jung S. Kim; Han I. Lee; Walter F. Bodmer (Familial Cancer, 2004)

Development of Oligonucleotide Primers for the Detection of Harmful Microcystis in Water - J.-E. Cho; S.-W. Bang; M.-S. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Developing gene-tagged molecular markers for functional analysis of starch-synthesizing genes in rice (Oryza sativa L.) - Xinyan Liu; Minghong Gu; Yuepeng Han; Qing Ji; Jufei Lu; Shiliang Gu; Rong Zhang; Xin Li; Jianmin Chen; Schuyler S. Korban; Mingliang Xu (Euphytica, 2004)

Characteristics of Ion Components and Trace Elements of Fine Particles at Gosan, Korea in Spring time from 2001 to 2002 - J. S. Han; K. J. Moon; J. Y. Ahn; Y. D. Hong; Y. J. Kim; S. Y. Ryu; S. S. Cliff; T. A. Cahill (Environmental Monitoring and Assessment, 2004)

A novel genealogical approach to neutral biodiversity theory - Rampal S. Etienne; Han Olff (Ecology Letters, 2004)
Current neutral theory in community ecology views local biodiversity as a result of the interplay between speciation, extinction and immigration. Simulations and a mean‐field approximation have been used to study this neutral theory. As simulations have limitations of convergence and the mean‐field approximation ignores dependencies between species’ abundances when applied to species‐abundance data, there is still no final conclusion whether the neutral theory or the traditional lognormal model describes community structure best. We present a novel analytical framework, based on the genealogy of individuals in the local community, to overcome the problems of previous approaches, and show, using Bayesian statistics, that the lognormal model provides a slightly better fit to the species‐abundance distribution of a much‐discussed tropical tree community. A key feature of our approach is that it shows the tight link between genetic and species diversity, which creates important perspectives to future integration of evolutionary and community ecological theory.

Tyrosine kinase inhibition differentially regulates heterologously expressed HCN channels - Han-Gang Yu; Zhongju Lu; Zongming Pan; Ira S. Cohen (Pflügers Archiv - European Journal of Physiology, 2004)

Effect of temperature on the pathogenicity of entomopathogenic nematodes (Steinernema and Heterorhabditis spp.) to Delia radicum - S. Chen; J. Li; X. Han; M. Moens (BioControl, 2003)

Determination of Semivolatile Compounds in Drinking Water by Tandem Mass Spectrometric Detection - L. Wang; Z. Huang; W. Zhou; C. Zhou; S. Han; A. Zhang; F. Feng; C. Liu (Bulletin of Environmental Contamination and Toxicology, 2003)

Some technical aspects of magnetic stimulation coil design with the ferromagnetic effect - B. H. Han; S. Y. Lee; J. H. Kim; J. H. Yi (Medical & Biological Engineering & Computing, 2003)

The pristine rain forest? Remnants of historical human impacts on current tree species composition and diversity - Barend S. van Gemerden; Han Olff; Marc P.E. Parren; Frans Bongers (Journal of Biogeography, 2003)
Aim Tropical rain forests are often regarded as pristine and undisturbed by humans. In Central Africa, community‐wide disturbances by natural causes are rare and therefore current theory predicts that natural gap phase dynamics structure tree species composition and diversity. However, the dominant tree species in many African forests recruit poorly, despite the presence of gaps. To explain this, we studied the disturbance history of a species‐rich and structurally complex rain forest. Location Lowland rain forest in Southern Cameroon. Methods We identified the recruitment conditions of trees in different diameter classes in 16 ha of species‐rich and structurally complex ‘old growth’ rain forest. For the identification of recruitment preference we used independent data on the species composition along a disturbance gradient, ranging from shifting cultivation fields (representing large‐scale disturbance), to canopy gaps and old growth forest. Results In nine of sixteen 1‐ha forest plots the older trees preferred shifting cultivation fields for recruitment while younger trees preferred gaps and closed forest conditions. This indicates that these nine sites once experienced large‐scale disturbances. Three lines of evidence suggest that historical agricultural use is the most likely disturbance factor: (1) size of disturbed and undisturbed patches, (2) distribution of charcoal and (3) historical accounts of human population densities. Main conclusions Present‐day tree species composition of a structurally complex and species‐rich Central African rain forest still echoes historical disturbances, most probably caused by human land use between three to four centuries ago. Human impact on African rain forest is therefore, contrary to common belief, an issue not of the last decades only. Insights in historical use will help to get a more balanced view of the ‘pristine rain forest’, acknowledging that the dualism between ‘old growth’ and ‘secondary’ forest may be less clear than previously thought.

Molecular dissection of a dormancy QTL region near the chromosome 7 (5H) L telomere in barley - W. Gao; J. A. Clancy; F. Han; D. Prada; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2003)

Recovery of conservation values in Central African rain forest after logging and shifting cultivation - Barend S. Van Gemerden; Gideon N. Shu; Han Olff (Biodiversity and Conservation, 2003)

Distribution and Sources of PAHs in Saemangeum Reclaimed Tidal Lands of Central Korea - J. Y. Cho; K. W. Han; J. H. Kim; J. K. Son; K. S. Yoon (Bulletin of Environmental Contamination and Toxicology, 2003)

Application of an Enhanced Electrokinetic Ion Injection System to Bioremediation - S. S. Kim; S. J. Han (Water, Air, & Soil Pollution, 2003)

Effects of fish introduction on the length of the tail of cryptomonads in mesocosm experiments - B. H. Kim; M.-S. Han; N. Takamura (Oecologia, 2003)

Predicting atmospheric biases for real-time ambiguity resolution in GPS/GLONASS reference station networks - L. Dai; J. Wang; C. Rizos; S. Han (Journal of Geodesy, 2003)

Degradation of Ethoprophos in Three Physicochemically Different Soils Treated with Composted Manure and Chemical Fertilizer - S.-H. Yoo; K.-H. Han; C.-S. Kim; H.-M. Ro; S.-M. Lee (Bulletin of Environmental Contamination and Toxicology, 2003)

Right Stereoisomers for Sex Pheromone Components of the Apple Leafminer, Lyonetia prunifoliella, in Korea - J. H. Park; K. S. Han; K. Mori; K. S. Boo (Journal of Chemical Ecology, 2002)

Nucleotide sequence and taxonomy of Cycas necrotic stunt virus - S. S. Han; A. V. Karasev; H. Ieki; T. Iwanami (Archives of Virology, 2002)

Perturbations of Population Growth in a Microcosm by Industrial Metal Plating and Ice Cream Mills Wastewater and Landfill Leachate - S.-U. Wui; K. Cho; Y. Inamori; J.-S. Lee; M.-S. Han; J.-B. Lee (Bulletin of Environmental Contamination and Toxicology, 2002)

Cadmium-Induced Apoptosis in H9c2, A7r5, and C6-Glial Cell - M. K. Choi; B. H. Kim; Y. Y. Chung; M. S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Response-Surface Analysis for the Inhibition Toxicity of Benzene Derivatives to Yeast Saccharomyces cerevisiae - X. Wang; Y. Wang; X. Dai; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Mass production of Siberian ginseng plantlets through large-scale tank culture of somatic embryos - Choi Y.-E.; Lee K.-S.; Kim E.-Y.; Kim Y.-S.; Han J.-Y.; Kim H.-S.; Jeong J.-H.; Ko S.-K. (Plant Cell Reports, 2002)

The exotic American eel in Taiwan: ecological implications - Y.‐S. Han; C.‐H. Yu; H.‐T. Yu; C.‐W. Chang; I‐C. Liao; W.‐N. Tzeng (Journal of Fish Biology, 2002)
Six American eels Anguilla rostrata were identified in the Kaoping River of south‐western Taiwan by sequencing the mitochondrial cytochrome b gene ( mtCyt‐b ). This was the first record of an exotic eel species in the natural waters of Taiwan. The exotic eels may have been imported from North America at the elver stage for aquaculture and escaped from culture ponds.

Pathogenicity and vaccine efficacy of a thymidine kinase gene deleted infectious laryngotracheitis virus expressing the green fluorescent protein gene - M. G. Han; C. H. Kweon; I. P. Mo; S. J. Kim (Archives of Virology, 2002)

Comparative Inhibition and Quantitative Structure-Activity Relationships (QSARs) of Substituted Phenols to Germination Rate of Cucumis sativus - X. Wang; X. Yang; Y. Wang; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Nucleotide sequence of a Japanese isolate of Squash mosaic virus - S. S. Han; K. Yoshida; A. V. Karasev; T. Iwanami (Archives of Virology, 2002)

An Assessment of the RAIM Performance of a Combined Galileo/GPS Navigation System Using the Marginally Detectable Errors (MDE) Algorithm - W. Y. Ochieng; K. F. Sheridan; K. Sauer; X. Han; P. A. Cross; S. Lannelongue; N. Ammour; K. Petit (GPS Solutions, 2002)

Morphology and sinking velocities of fecal pellets of copepod, molluscan, euphausiid, and salp taxa in the northeastern tropical Atlantic - Yoon W.; Kim S.; Han K. (Marine Biology, 2001)

Complex control of the developmental regulatory locus brlA in Aspergillus nidulans - S. Han; T. Adams (Molecular Genetics and Genomics, 2001)

From simulation to implementation: low-cost densification of permanent GPS networks in support of geodetic applications - H.-Y. Chen; C. Rizos; S. Han (Journal of Geodesy, 2001)

Correlation of Reversed-Phase Retention Factors for α-Branched Phenylsulfonyl Acetates with Octanol/Water Partition Coefficients and Quantum Chemical Descriptors - X. Liu; D. Wei; C. Wu; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

Workshop on Bioanalytical Methods Validation for Macromolecules: Summary Report - Krys J. Miller; Ronald R. Bowsher; Abbie Celniker; Jacqueline Gibbons; Shalini Gupta; Jean W. Lee; Steve J. Swanson; Wendell C. Smith; Russell S. Weiner; Daan J. A. Crommelin; Ira Das; Binodh S. DeSilva; et al. (Pharmaceutical Research, 2001)

Physical and Chemical Properties of a Winter-Time Yellow Sand Event in Northeast Asia - B. G. Kim; J. Y. Ahn; H. R. Noh; C. J. Park; J. S. Han; S. U. Park (Water, Air, & Soil Pollution, 2001)

Sequence diversity and interrelationships among isolates of satsuma dwarf-related viruses - T. Iwanami; Y. Kondo; M. Kobayashi; S. S. Han; A. V. Karasev (Archives of Virology, 2001)

Accurate absolute GPS positioning through satellite clock error estimation - S.-C. Han; J. H. Kwon; C. Jekeli (Journal of Geodesy, 2001)

Functional characterization of β-ketoacyl-CoA synthase genes from Brassica napus L. - Jixiang Han; Wilfried Lühs; Karin Sonntag; Ulrich Zähringer; Dorothea S. Borchardt; Frank P. Wolter; Ernst Heinz; Margrit Frentzen (Plant Molecular Biology, 2001)

Identification of rice black-streaked dwarf fijivirus in maize with rough dwarf disease in China - S. Fang; J. Yu; J. Feng; C. Han; D. Li; Y. Liu (Archives of Virology, 2001)

Sequence variants and functional analysis of human papillomavirus type 16 E5 gene in clinical specimens - C.-H. Hsieh; Y.-P. Tsao; C.-H. Wang; C.-P. Han; J.-L. Chang; J.-Y. Lee; S.-L. Chen (Archives of Virology, 2000)

Adaptive filtering of continuous GPS results - L. Ge; H.-Y. Chen; S. Han; C. Rizos (Journal of Geodesy, 2000)

Structure-phytotoxicity relationship: Comparative inhibition of selected nitrogen containing aromatics to root elongation of Cucumis sativus - X. Wang; Y. Dong; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 2000)

Angiotensin II induces gene transcription through cell-type-dependent effects on the nuclear factor-κB (NF-κB) transcription factor - Allan R. Brasier; M. Jamaluddin; Youqui Han; Cam Patterson; Marschall S. Runge (Molecular and Cellular Biochemistry, 2000)

Quantitative Structure-Activity Relationships for the Toxicity to the Tadpole Rana japonica of Selected Phenols - X. Wang; Y. Dong; S. Xu; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2000)

Quantitative Structure-Activity Relationships for the Toxicity to the Tadpole Rana japonica of Selected Phenols - X. Wang; Y. Dong; S. Xu; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

An Agrobacterium tumefaciens transformation protocol effective on a variety of cottonwood hybrids (genus Populus ) - K.-H. Han; R. Meilan; C. Ma; S. H. Strauss (Plant Cell Reports, 2000)

Degradation of chlorinated and brominated hydrocarbons by Methylomicrobium album BG8 - J. -I. Han; S. Lontoh; J. D. Semrau (Archives of Microbiology, 1999)

Genetic transformation of Cymbidium orchid by particle bombardment - J. Yang; H.-J. Lee; D. H. Shin; S. K. Oh; J. H. Seon; K. Y. Paek; K.-H. Han (Plant Cell Reports, 1999)

Roles of cyclin D1 and related genes in growth inhibition, senescence and apoptosis - E. K.-H. Han; S.-C. Ng; N. Arber; M. Begemann; I. B. Weinstein (Apoptosis, 1999)

QSAR for Polychlorinated Organic Compounds (PCOCs). I. Prediction of Partition Properties for PCOCs Using Quantum Chemical Parameters - J. Dai; C. Sun; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 1999)

Increased mRNAs for procollagens and key regulating enzymes in rat skeletal muscle following downhill running - Xiao-Yan Han; W. Wang; Satu O. A. Koskinen; Vuokko Kovanen; T. E. S. Takala; Jyrki Komulainen; Veikko Vihko; Philip C. Trackman (Pflügers Archiv - European Journal of Physiology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

Response of The Lacewing Chrysopa cognata to Pheromones of its Aphid Prey - K. S. Boo; I. B. Chung; K. S. Han; J. A. Pickett; L. J. Wadhams (Journal of Chemical Ecology, 1998)

Influence of Different Fat Emulsion-Based Intravenous Formulations on the Pharmacokinetics and Pharmacodynamics of Propofol - Eugene H. Cox; Catherijne A. J. Knibbe; Victorine S. Koster; Mariska W. E. Langemeijer; Erica E. Tukker; Rogier Lange; Paul F. M. Kuks; Han J. M. Langemeijer; Loraine Lie-A-Huen; Meindert Danhof (Pharmaceutical Research, 1998)

Organization of convection and monsoon forecasts - T. N. Krishnamurti; H. S. Bedi; Wei Han (Meteorology and Atmospheric Physics, 1998)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Strategies for the improvement of salidroside production in cell suspension cultures of Rhodiola sachalinensis - J. F. Xu; C. B. Liu; A. M. Han; P. S. Feng; Z. G. Su (Plant Cell Reports, 1998)

cGMP facilitates calcium current via cGMP-dependent protein kinase in isolated rabbit ventricular myocytes - J. Han; Euiyong Kim; S. H. Lee; S. Yoo; Won-Kyung Ho; Y. E. Earm (Pflügers Archiv - European Journal of Physiology, 1998)

A dynamic statistical experiment for atmospheric interactions - Devdutta S. Niyogi; Sethu Raman; Kiran Alapaty; Jongil Han (Environmental Modeling & Assessment, 1997)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

lonization and Solubilization of 4 Alkyl Benzole Acids and 4 Alkyl Anilines in Sodium Taurodeoxycholate Solutions - Timothy S. Wiedmann; Kristen Kvanbeck; Chien-Hsuan Han; Vikram Roongta (Pharmaceutical Research, 1997)

Fine structure mapping of the barley chromosome-1 centromere region containing malting-quality QTLs - F. Han; S. E. Ullrich; A. Kleinhofs; B. L. Jones; P. M. Hayes; D. M. Wesenberg (Theoretical and Applied Genetics, 1997)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

Quality-control issues relating to instantaneous ambiguity resolution for real-time GPS kinematic positioning - S. Han (Journal of Geodesy, 1997)

210 Pb-derived sediment accumulation rates in the southwestern East Sea (Sea of Japan) - G. H. Hong; S. H. Kim; C. S. Chung; D.-J. Kang; D.-H. Shin; H. J. Lee; S.-J. Han (Geo-Marine Letters, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Human Papillomavirus is More Prevalent in First Trimester Spontaneously Aborted Products of Conception Compared to Elective Specimens - P L Hermonat; L Han; P J Wendel; J G Quirk; S Stern; C L Lowery; T M Rechtin (Virus Genes, 1997)

Developmental patterns of aluminum and five essential mineral elements in the central nervous system of the fetal and infant guinea pig - Mari S. Golub; Bin Han; Carl L. Keen (Biological Trace Element Research, 1996)

Mitochondrial DNA restriction map for the mediterranean fruit fly,Ceratitis capitata - Bruce A. McPheron; Gail E. Gasparich; Ho-Yeon Han; Gary J. Steck; Walter S. Sheppard (Biochemical Genetics, 1994)

Nucleotide sequence of the human? 1-globin gene - J. M. Gonzalez-Redondo; I. S. Han; Y. -C. Gu; T. H. J. Huisman (Biochemical Genetics, 1988)

Mirex in human milk in upstate New York - B. Bush; J. Snow; S. Connor; L. Rueckert; Y. Han; P. Dymerski; D. Hilker (Archives of Environmental Contamination and Toxicology, 1983)